Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 108014697 species occurrences available in GBIF matching the query: { "and" : [ "Country is one of (Andorra, Albania, Armenia, Austria, Åland Islands, Azerbaijan, Bosnia and Herzegovina, Belgium, Bulgaria, Belarus, Switzerland, Cyprus, Czechia, Germany, Denmark, Algeria, Estonia, Egypt, Spain, Finland, Faroe Islands, France, United Kingdom of Great Britain and Northern Ireland, Georgia, Guernsey, Gibraltar, Greece, Croatia, Hungary, Ireland, Israel, Isle of Man, Iceland, Italy, Jersey, Lebanon, Liechtenstein, Lithuania, Luxembourg, Latvia, Libya, Morocco, Monaco, Moldova, Republic of, Montenegro, North Macedonia, Malta, Netherlands, Norway, Poland, Portugal, Romania, Serbia, Russian Federation, Sweden, Slovenia, Svalbard and Jan Mayen, Slovakia, San Marino, Syrian Arab Republic, Tunisia, Türkiye, Ukraine, Holy See, Kosovo)", "BasisOfRecord is one of (Human Observation, Living Specimen, Machine Observation, Observation, Literature Occurrence, Material sample)", "EventDate is not null", "VerbatimScientificName is one of ('Candidatus Liberibacter solanacearum', 'Candidatus Phytoplasma asteris', 'Candidatus Phytoplasma brasiliense', 'Candidatus Phytoplasma cirsii', 'Candidatus Phytoplasma convolvuli', 'Candidatus Phytoplasma cynodontis', 'Candidatus Phytoplasma fragariae', 'Candidatus Phytoplasma fraxini', 'Candidatus Phytoplasma mali', 'Candidatus Phytoplasma pini', 'Candidatus Phytoplasma pruni', 'Candidatus Phytoplasma prunorum', 'Candidatus Phytoplasma pyri', 'Candidatus Phytoplasma rhamni', 'Candidatus Phytoplasma rubi', 'Candidatus Phytoplasma solani', 'Candidatus Phytoplasma spartii', 'Candidatus Phytoplasma trifolii', 'Candidatus Phytoplasma ulmi', 'Candidatus Phytoplasma ziziphi', ‘Candidatus Liberibacter psyllaurous’, A. orientalis takanosimensis, Aansevieria craigii, Abacosa dumetorum, Abax parallelus, Abbotia filiformis, Abelia x grandiflora, Abelicea serrata, Abgrallaspis cyanophylli, Abida illyrica, Abida polyodon, Abies alba subsp. apennina, Abies alba var. cephalonica, Abies alba, Abies albertiana, Abies alpestris, Abies amabilis, Abies americana, Abies apollinis, Abies araucana, Abies arctica, Abies argentea, Abies aromatica, Abies atlantica, Abies baldensis, Abies balsamea f. balsamea, Abies balsamea f. hudsonia, Abies balsamea f. nana, Abies balsamea f. phanerolepis, Abies balsamea subsp. phanerolepis, Abies balsamea var. balsamea, Abies balsamea var. brachylepis, Abies balsamea var. longifolia, Abies balsamea var. macrocarpa, Abies balsamea var. nana, Abies balsamea var. phanerolepis, Abies balsamea, Abies balsamifera, Abies bifolia, Abies bridgesii, Abies canadensis var. gracilis, Abies canadensis, Abies candicans, Abies carpatica, Abies cedrus, Abies cephalonica subsp. apollinis, Abies cephalonica subsp. peloponnesiaca, Abies cephalonica var. apollinis, Abies cephalonica var. appolinis, Abies cephalonica var. arcadica, Abies cephalonica var. graeca, Abies cephalonica var. heterophylla, Abies cephalonica var. parnassica, Abies cephalonica var. peloponnesiaca, Abies cephalonica var. reginae-amaliae, Abies cephalonica var. submutica, Abies cephalonica, Abies chlorocarpa, Abies cinerea, Abies clambrasiliana, Abies clanbrassiliana, Abies coerulea, Abies coerulescens, Abies columbaria, Abies commutata, Abies concolor, Abies conica, Abies cupressoides, Abies curvifolia, Abies denticulata, Abies deodara, Abies duplex, Abies eichleri, Abies elegans, Abies engelmannii, Abies eremita, Abies erythrocarpa, Abies excelsa, Abies excelsior, Abies extrema, Abies falcata, Abies finedonensis, Abies fraseri var. hudsonia, Abies fraseri var. nana, Abies fraseri, Abies gigantea, Abies gmelinii, Abies gordoniana, Abies grandis f. johnsonii, Abies grandis subsp. idahoensis, Abies grandis var. idahoensis, Abies grandis, Abies gregoryana, Abies heterophylla, Abies hispanica, Abies hudsonia, Abies humilis, Abies intermedia, Abies inverta, Abies kaempferi, Abies kamtschatica, Abies krylovii, Abies lasiocarpa, Abies laxa, Abies ledebourii, Abies leioclada, Abies lemoniana, Abies leptolepis, Abies mariana, Abies medioxima, Abies merkiana, Abies mertensiana, Abies metensis, Abies microcarpa, Abies microphylla, Abies miniata, Abies minor, Abies minuta, Abies montana, Abies nigra, Abies nobilis, Abies nordmanniana var. speciosa, Abies nordmanniana, Abies obovata, Abies occidentalis, Abies omorika, Abies orientalis, Abies pardei, Abies parlatorei, Abies parsonii, Abies parsonsiana, Abies parvula, Abies pattoniana, Abies pattonii, Abies picea, Abies pichta, Abies pinsapo, Abies procera, Abies rinzii, Abies sibirica, Abies sitchensis, Abies subalpina, Abies subarctica, Abies taxifolia, Abies tenuirifolia, Abies trigona, Abies veitchii, Abies viminalis, Abies virescens, Abies vulgaris, Abies williamsonii, Abies wittmanniana, Abies x beissneriana, Abies x insignis f. beissneriana, Abies x insignis f. kentiana, Abies x insignis f. mastersiana, Abies x insignis f. speciosa, Abies x insignis var. beissneriana, Abies x insignis var. kentiana, Abies x insignis var. mastersiana, Abies x insignis var. pendula, Abies x insignis var. speciosa, Abies x insignis, Abies x kentiana, Abies x mastersiana, Abies x phanerolepis, Abildgaardia capillaris, Ablattaria laevigata, Ablerus chionaspidis, Ablerus clisiocampae, Ablerus perspeciosus, Abramidopsis leuckartii, Abramis argyreus, Abramis balleropsis, Abramis bjoerkna, Abramis brama bergi, Abramis brama danubii, Abramis brama orientalis, Abramis brama sinegorensis, Abramis brama, Abramis gehini, Abramis leuckartii, Abramis media, Abramis melaenus, Abramis microlepidotus, Abramis pekinensis, Abramis sapa aralensis, Abramis sapa bergi, Abramis schreibersii, Abramis terminalis, Abramis vetula, Abramis vimba, Abramis vulgaris, Abramocephalus microlepis, Abronia fragrans var. glaucescens, Abronia fragrans, Abrotanum ambiguum, Abrotanum brachylobium, Abrotanum congestum, Abrotanum pauciflorum, Abrotanum pedunculare, Abrotanum rhodanicum, Absinthium arborescens, Absinthium camphoratum, Absinthium canariense, Absinthium candidum, Absinthium corymbosum, Absinthium frigidum, Absinthium officinale, Absinthium ponticum, Absinthium spicatum, Absinthium tenuifolium, Absinthium trifidum, Absinthium virgatum, Absinthium vulgare, Abudefduf caudobimaculatus, Abudefduf hoefleri, Abudefduf quinquilineatus, Abudefduf sexfasciatus, Abudefduf vaigiensis, Aburria cumanensis, Abutilodes carolinianum, Abutilon abutilon, Abutilon albidum, Abutilon arnottianum, Abutilon avicennae, Abutilon grandifolium, Abutilon kauaiense, Abutilon molle, Abutilon mollissimum, Abutilon permolle, Abutilon pictum, Abutilon sonneratianum, Abutilon sordidum, Abutilon striatum, Abutilon theophrasti, Abutilon tortuosum, Abutilon umtaliense, Abutilon x hybridum, Abyla carina, Abyla peruana, Abyla schmidti, Abyla totttoni, Abyla trigona, Acabaria erythraea, Acachmena cuspidata, Acacia acicularis, Acacia affinis, Acacia albida, Acacia americana, Acacia angustisiliqua, Acacia arcuata, Acacia baileyana, Acacia botrycephala, Acacia brachyloba, Acacia bracteata, Acacia campbellii, Acacia cultrata, Acacia cultriformis, Acacia cumanensis, Acacia cyanophylla, Acacia cyclops, Acacia cyclopsis, Acacia dealbata, Acacia decurrens var. dealbata, Acacia decurrens var. mollis, Acacia dekindtiana, Acacia depauperata, Acacia derwentii, Acacia discolor var. glabra, Acacia discolor var. maritima, Acacia discolor, Acacia eburnea, Acacia eglandulosa, Acacia elata, Acacia falcinella, Acacia farnesiana var. lenticellata, Acacia farnesiana, Acacia fragrans, Acacia frondosa, Acacia glandulosa, Acacia glauca, Acacia glaucifolia, Acacia glaucophylla, Acacia horrida, Acacia inconflagrabilis, Acacia indica, Acacia inermis, Acacia juliflora, Acacia karoo, Acacia karroo, Acacia laevis, Acacia latifolia, Acacia leiophylla, Acacia lenticellata, Acacia leptosperma, Acacia leucocephala, Acacia ligulata, Acacia lindleyi, Acacia longifolia subsp. sophorae, Acacia longifolia var. sophorae, Acacia longifolia, Acacia longissima, Acacia lophantha, Acacia maritima, Acacia mearnsii, Acacia melanoxylon, Acacia melanoxylum, Acacia minuta subsp. densiflora, Acacia minuta subsp. minuta, Acacia minuta, Acacia minutifolia, Acacia mirbelii, Acacia mollissima, Acacia natalitia, Acacia nemu, Acacia neriifolia, Acacia pallidiramosa, Acacia papuliformis, Acacia penninervis var. angustata, Acacia petiolaris, Acacia propinqua, Acacia provincialis, Acacia pseudowightii, Acacia puberula, Acacia pycnantha var. petiolaris, Acacia pycnantha, Acacia retinodes var. floribunda, Acacia retinodes var. retinodes, Acacia retinodes, Acacia retinoides, Acacia rhetinoides, Acacia rostellifera, Acacia roxburghii, Acacia salicina var. typica, Acacia salicina var. varians, Acacia salicina, Acacia saligna, Acacia salinarum, Acacia salix-tristis, Acacia scapuliformis, Acacia semperflorens, Acacia smallii, Acacia sophora, Acacia sophorae, Acacia sophorina, Acacia terminalis, Acacia triacanthosAcacia triacanthos, Acacia varians, Acacia verticillata subsp. verticillata, Acacia verticillata var. angusta, Acacia verticillata var. glabra, Acacia verticillata var. latifolia, Acacia verticillata, Acacia virgata, Acacia westoni, Acacia westonii, Acaena anserinifolia, Acaena elegans, Acaena hirsuta, Acaena inermis, Acaena micranthera, Acaena microphylla var. inermis, Acaena microphylla, Acaena novae-zelandiae, Acaena ovalifolia subsp. elegans, Acaena ovalifolia var. chubutensis, Acaena ovalifolia var. elegans, Acaena ovalifolia, Acaena sanguisorbae subsp. novae-zelandiae, Acaena tenuipila, Acalypha amentacea subsp. wilkesiana, Acalypha australis var. glareosa, Acalypha australis var. lanceolata, Acalypha australis var. velutina, Acalypha australis, Acalypha bailloniana, Acalypha brevipes, Acalypha caroliniana, Acalypha chinensis, Acalypha compacta, Acalypha crenulata, Acalypha cupamenii, Acalypha decidua, Acalypha digyneia, Acalypha echinata, Acalypha fimbriata, Acalypha gemina var. genuina, Acalypha gemina var. lanceolata, Acalypha gemina, Acalypha godseffiana, Acalypha hamiltoniana, Acalypha indica, Acalypha lanceolata, Acalypha macafeeana, Acalypha minima, Acalypha musaica, Acalypha pauciflora var. glareosa, Acalypha pauciflora, Acalypha sessilis, Acalypha somalensis, Acalypha somalium, Acalypha spicata, Acalypha tricolor, Acalypha triumphans, Acalypha virgata, Acalypha virginea, Acalypha virginica var. genuina, Acalypha virginica var. virginica, Acalypha virginica, Acalypha wilkesiana, Acalyptris platani, Acanalonia conica, Acanos spina, Acantharctus posteli, Acanthaster echinites, Acanthaster echinus, Acanthaster ellisi, Acanthaster mauritiensis, Acanthaster planci, Acanthaster pseudoplanci, Acanthaster solaris, Acanthium onopordon, Acanthocephalus lucii, Acanthochaetodon imperator, Acanthochaetodon nicobariensis, Acanthocheilonema perstans, Acanthocinus aedilis, Acanthocinus griseus, Acanthocinus reticulatus, Acanthocnemus nigricans, Acanthococcus agropyri, Acanthococcus micracanthus, Acanthoderes jaspidea, Acantholyda erythrocephala, Acantholyda laricis, Acanthomysis strauchi, Acanthopagrus bifasciatus, Acanthopanax asperatus, Acanthopanax senticosus, Acanthophora delilei, Acanthophora nayadiformis, Acanthopleura gemmata, Acanthopleura haddoni, Acanthopleura vaillanti, Acanthoscelides irresectus fåhraeus, Acanthoscelides obtectus, Acanthoscelides pallidipennis, Acanthoscelides tetricus gyllenhal, Acanthoscurria geniculata, Acanthospermum hispidum, Acanthospermum humile var. hispidum, Acanthospermum humile, Acanthostyles buniifolius, Acanthotheca dentata, Acanthoxanthium ambrosioides, Acanthoxanthium spinosum, Acanthoxyla geisovii, Acanthoxyla inermis, Acanthoxyla prasina geisovii, Acanthoxyla prasina inermis, Acanthurus chirurgus, Acanthurus coeruleus, Acanthurus flavescens, Acanthurus hepatus, Acanthurus phlebotomus, Acanthurus sohal, Acanthurus theuthis, Acanthurus xanthurus, Acanthus caroli-alexandri, Acanthus latifolius, Acanthus lusitanicus, Acanthus mollis, Acanthus spinosissimus, Acanthus spinosus subsp. spinosissimus, Acanthus spinosus, Acanthus spinulosus, Acaphylla theae, Acar plicata, Acara faceta, Acara ocellatus, Acaricalus hederae, Acarna leucographa, Acartia (Acanthacartia) fossae, Acartia (Acartiura) omorii, Acartia (Odontacartia) centrura, Acartia centrura, Acartia fossae, Acartia omorii, Acartia tonsa, Acaudaleyrodes rachiphora, Acca sellowiana, Accipiter gentilis, Accipiter nisus, Acer affin, Acer amoenum, Acer austriacum, Acer bedoei, Acer campestre subs phebecarpum, Acer campestre subsp. leiocarpum, Acer campestre, Acer cappadocicum subsp. lobelii, Acer cappadocicum, Acer circinatum f. fulvum, Acer circinatum var. fulvum, Acer circinatum, Acer colchicum, Acer collinum, Acer commutatum, Acer cucullobracteatum, Acer dasycarpum, Acer decompositum, Acer dedyle, Acer dieckii, Acer dissectum, Acer fallax, Acer formosum, Acer friederici-guillelmii, Acer ginnala, Acer heldreichii f. cruciatum, Acer heldreichii f. macropterum., Acer heldreichii f. obtentum, Acer heldreichii subsp. visianii, Acer heldreichii var. macropterum, Acer heldreichii, Acer hispidum, Acer incisum, Acer jucundum, Acer laciniatum, Acer lactescens, Acer laetum, Acer leiocarpum, Acer lobelii, Acer lobergii, Acer microcarpon, Acer molle, Acer monspessulanum, Acer montanum, Acer neapolitanum, Acer negundo, Acer nikoense, Acer obtusatum, Acer opalus subsp. obtusatum, Acer ornatum, Acer palmatum, Acer palmifolium, Acer parviflorum, Acer pensylvanicum var. tegmentosum, Acer platanifolium, Acer platanoides var. schwedleri, Acer platanoides, Acer pseudoplatanus f. albertsii, Acer pseudoplatanus f. albomarmoratum, Acer pseudoplatanus var. acuminatum, Acer pseudoplatanus, Acer pumilum, Acer quinquelobum, Acer reitenbachii, Acer rotundum, Acer rufinerve, Acer rugelii, Acer saccharinum f. ahlesii, Acer saccharinum var. laciniatum, Acer saccharinum var. wieri, Acer saccharinum, Acer saccharophorum, Acer saccharum, Acer schwedleri, Acer spicatum, Acer tataricum subsp. ginnala, Acer tataricum subsp. tataricum, Acer tegmentosum, Acer villosum, Acer vitifolium, Aceratoneuromyia indica, Aceria alpestris, Aceria ambrosiae, Aceria byersi, Aceria caliberberis, Aceria erinea, Aceria kuko, Aceria ligustri, Aceria loewi, Aceria mangiferae, Aceria neocynarae, Aceria paradianthi, Aceria petanovicae, Aceria sawatchense, Aceria sheldoni, Aceria stefanii, Aceria tamaricis, Aceria tristriata, Acerina cernua, Acerina czekanowskii, Acerina fischeri, Acerina vulgaris, Acerophagus angelicus, Acerophagus maculipennis, Acerophagus malinus, Acetosa alpina, Acetosa bucephalophora, Acetosa conglomerata, Acetosa digyna, Acetosa lunaria, Acetosa pratensis, Acetosa rugosa, Acetosa sanguinea, Acetosa scutata, Acetosa vesicaria, Acetosella antucensis, Acetosella articulata, Acetosella bakeriana, Acetosella catharinensis, Acetosella cernua, Acetosella chinensis, Acetosella corniculata, Acetosella crenata, Acetosella debilis, Acetosella fontana, Acetosella grandifolia, Acetosella hapalconidea, Acetosella herpestica, Acetosella incarnata, Acetosella martiana, Acetosella palustris, Acetosella platensis, Acetosella purpurea, Acetosella rosea, Acetosella stricta, Acetosella tetraphylla, Acetosella tuberosa, Acetosella valdiviensis, Achaearanea acoreensis, Achaearanea tabulata, Achaearanea tepidariorum, Achaearanea veruculata, Achaeta geniculata, Acharia stimulea, Achariterium arvense, Achatina achatina, Achatina acicula, Achatina crotallaria, Achatina fulica, Achatina gredleri, Achatina janii, Achatina lhotelleriana, Achatina lubrica, Achatina mamillata, Achatina marginata, Achatina novenaria, Achatina oblitterata, Achatina octona, Achatina panamensis, Achatina perdix, Achatina tincta, Achatina variegata, Achatina veneta, Achelia sawayai s.l., Acheta domesticus, Achillea ageratum, Achillea albida, Achillea alpicola, Achillea ambigua, Achillea anethifolia, Achillea angustissima, Achillea arabica, Achillea arenicola, Achillea aromatica, Achillea asplenifolia, Achillea aspleniifolia, Achillea banatica, Achillea biaristata, Achillea bicolor, Achillea borealis subsp. arenicola, Achillea borealis subsp. californica, Achillea borealis subsp. typica, Achillea borealis var. arenicola, Achillea borealis var. californica, Achillea borealis, Achillea bulgarica, Achillea californica, Achillea capillaris, Achillea cartilaginea, Achillea ceretanica, Achillea collina, Achillea compacta, Achillea coronopifolia, Achillea corymbifera, Achillea crispa, Achillea crithmifolia, Achillea cuneata, Achillea cylindrica, Achillea decipiens, Achillea dentifera, Achillea distans subsp. stricta, Achillea distans subsp. tanacetifolia, Achillea distans, Achillea doerfleri, Achillea dolopica, Achillea dracunculoides, Achillea eradiata, Achillea eridania, Achillea eupatorium, Achillea filicifolia, Achillea fililoba, Achillea filipendulina, Achillea fragilis, Achillea fusca, Achillea gigantea, Achillea gracilis, Achillea grandifolia, Achillea grata, Achillea haenkeana, Achillea hispanica, Achillea intermedia, Achillea ircutiana, Achillea kummerleana, Achillea lanata, Achillea lanulosa subsp. alpicola, Achillea lanulosa subsp. megacephala, Achillea lanulosa subsp. typica, Achillea lanulosa var. alpicola, Achillea lanulosa var. arachnoidea, Achillea lanulosa var. eradiata, Achillea lanulosa, Achillea latifolia, Achillea laxiflora, Achillea lenensis, Achillea leucanthema, Achillea ligustica, Achillea magna, Achillea marginata, Achillea maritima, Achillea maxima, Achillea megacephala, Achillea micrantha, Achillea millefolium subsp. atrotegula, Achillea millefolium subsp. borealis, Achillea millefolium subsp. collina, Achillea millefolium subsp. lanulosa, Achillea millefolium subsp. millefolium, Achillea millefolium subsp. occidentalis, Achillea millefolium subsp. pallidotegula, Achillea millefolium var. alpicola, Achillea millefolium var. arenicola, Achillea millefolium var. aspleniifolia, Achillea millefolium var. borealis, Achillea millefolium var. californica, Achillea millefolium var. fulva, Achillea millefolium var. fusca, Achillea millefolium var. gigantea, Achillea millefolium var. gracilis, Achillea millefolium var. lanulosa, Achillea millefolium var. litoralis, Achillea millefolium var. maritima, Achillea millefolium var. megacephala, Achillea millefolium var. millefolium, Achillea millefolium var. nigrescens, Achillea millefolium var. occidentalis, Achillea millefolium var. pacifica, Achillea millefolium var. parviligula, Achillea millefolium var. parvula, Achillea millefolium var. puberula, Achillea millefolium var. rosea, Achillea millefolium var. russeolata, Achillea millefolium, Achillea multifida, Achillea nabelekii, Achillea nigrescens, Achillea nobilis, Achillea occidentalis, Achillea ochroleuca, Achillea pacifica, Achillea pallescens, Achillea pannonica, Achillea partheniflora, Achillea paucidentata, Achillea peucedanifolia, Achillea ptarmica, Achillea puberula, Achillea pubescens, Achillea rosea, Achillea roseo-alba, Achillea salicifolia, Achillea salina, Achillea scabra, Achillea schkuhrii, Achillea sedlii, Achillea seidlii, Achillea senecioniflora, Achillea serrulata, Achillea setacea Schwein, Achillea setacea, Achillea sicula, Achillea smithii, Achillea speciosa, Achillea stricta, Achillea subalpina, Achillea subtanacetifolia, Achillea sylvatica, Achillea tanacetifolia, Achillea tenuis, Achillea tomentosa, Achillea viscosa, Achnanthes pseudogroenlandica, Achnatherum argenteum, Achnatherum brachychaetum, Achnatherum bromoides, Achnatherum calamagrostis, Achnatherum fallacinum, Achnatherum halleri, Achnatherum hymenoides, Achnatherum mesatlasicum, Achnatherum miliaceum, Achnatherum papposum, Achnatherum splendens, Achnodon arenarius, Achnodon bellardii, Achnodonton arenarium, Achnodonton bellardi, Achnodonton bellardii, Achnodonton bulbosum, Achnodonton tenue, Achnodonton tenuis, Achrophyllum dentatum, Achuatherum brachychaeta, Achyranthes acuminata, Achyranthes argentea, Achyranthes aspera obtusifolia, Achyranthes aspera, Achyranthes asperoides, Achyranthes australis, Achyranthes canescens, Achyranthes chacoensis, Achyranthes daito-insularis, Achyranthes ellipticifolia, Achyranthes ficoidea, Achyranthes fruticosa, Achyranthes grandifolia, Achyranthes leiantha, Achyranthes linearifolia, Achyranthes lorentzii, Achyranthes obovata, Achyranthes obovatifolia, Achyranthes obtusifolia, Achyranthes okinawensis, Achyranthes paludosa, Achyranthes paronychioides, Achyranthes peploides, Achyranthes philoxeroides, Achyranthes repens, Achyranthes robusta, Achyranthes sessilis, Achyranthes sicula, Achyranthes tenuifolia, Achyranthes ternata, Achyranthes triandra, Achyranthes villosa, Achyrodes aureum, Achyrophorus balbisii, Achyrophorus microcephalus, Acia nivea, Acicula eburnea, Acidanthera capensis, Acidoton flueggeoides, Acidoton ramiflorus, Acidovorax avenae subsp. citrulli, Acidovorax citrulli, Acinipe hesperica, Acinos acuminatus, Acinos arvensis, Acinos grandiflorus, Acinos thymoides, Acinos vulgaris, Acipenser aculeatus, Acipenser aleutensis, Acipenser gueldenstaedti acutirostris, Acipenser gueldenstaedti golis, Acipenser gueldenstaedti longirostris, Acipenser gueldenstaedti scaber, Acipenser gueldenstaedti tanaica, Acipenser gueldenstaedtii colchica, Acipenser gueldenstaedtii gueldenstaedtii, Acipenser gueldenstaedtii scobar, Acipenser gueldenstaedtii x ruthenus, Acipenser gueldenstaedtii, Acipenser macrophthalmus, Acipenser medius, Acipenser pygmaeus, Acipenser ruthensis, Acipenser ruthenus, Acipenser seuruga, Acipenser stellatus, Acipenser sturio, Acipenser transmontanus, Acipenser tuecka, Acipenserobdella volgensis, Acizzia acaciaebaileyanae, Acizzia hollisi, Acizzia jamatonica, Acizzia uncatoides, Aclees cribratus, Acleris undulana, Acleris variegana, Aclypea opaca, Acmaea saccharina, Acmella brasiliensis, Acmella parvifolia, Acmella spilanthoides, Acnida altissima var. prostrata, Acnida altissima var. subnuda, Acnida altissima, Acnida concatenata, Acnida subnuda, Acnida tamariscina var. prostrata, Acnida tamariscina, Acnida tuberculata, Acnistus australis, Acomys minous, Acomys nesiotes, Aconitum altissimum, Aconitum anglicum, Aconitum bauhinii, Aconitum besserianum, Aconitum clusii, Aconitum gracilescens, Aconitum lasianthum, Aconitum lasiostomum, Aconitum linnaeanum, Aconitum lycoctonum subsp. lasiostomum, Aconitum lycoctonum subsp. vulparia, Aconitum napellus subsp. lusitanicum, Aconitum napellus subsp. neomontanum, Aconitum napellus x variegatum, Aconitum napellus, Aconitum neomontanum, Aconitum pallidum, Aconitum pauciflorum, Aconitum penninum, Aconitum puberulum, Aconitum reclinatum, Aconitum rostratum, Aconitum stoerkianum, Aconitum thalianum, Aconitum thelyphonum, Aconitum variegatum subsp. judenbergense, Aconitum variegatum subsp. rostratum, Aconitum variegatum, Aconitum vulparia subsp. croaticum, Aconitum vulparia, Aconitum x cammarum, Aconogonon alaskanum, Aconogonon alpinum, Aconogonon campanulatum, Aconogonon coriarium, Aconogonon divaricatum, Aconogonon polystachyum, Aconogonon savatieri, Aconogonon weyrichii, Aconogonon x fennicum, Aconogonum molle, Aconogonum polystachyum, Acontia candefacta, Acontia crocata, Acorellus laevigatus, Acorellus pallae, Acorus adulterinus, Acorus calamus, Acorus gramineus var. japonica, Acorus gramineus var. macrospadiceus, Acorus gramineus var. pusillus, Acorus gramineus, Acorus humilis, Acorus macrospadiceus, Acorus pusillus, Acorus xiangyeus, Acosta arenaria, Acosta diffusa, Acosta paniculata, Acosta psammogena, Acosta squarrosa, Acosta stoebe, Acosta varnensis, Acremonium cucurbitacearum, Acremonium lindtneri, Acremonium maydis, Acridotheres albocinctus, Acridotheres cristatellus, Acridotheres ginginianus, Acridotheres tristas, Acridotheres tristis, Acritus analis, Acritus nigricornis, Acrocalanus gibber, Acrocentron collinum, Acrocentron orientale, Acrocentron salonitanum, Acrocentron scabiosa, Acrocentron tenuifolium, Acrochaetium codicola, Acrochaetium robustum, Acrochaetium sargassicola, Acrochaetium savianum, Acrochaetium spathoglossi, Acrochaetium subseriatum, Acrocinus longimanus, Acroclinium roseum, Acrocoelia ruficeps, Acroconidiella gracilis, Acrocrypta purpurea, Acrolophus diffusus, Acrolophus mierghii, Acrolophus rigidulus, Acrolophus squarrosus, Acropoma japonicum, Acroptilon angustifolium, Acroptilon australe, Acroptilon obtusifolium, Acroptilon picris, Acroptilon repens, Acroptilon serratum, Acrosporium chrysanthemi, Acrosporium erysiphoides, Acrosporium fructigenum, Acrosporium laxum, Acrosporium lini, Acrosporium oxalidis, Acrosporium tuckeri, Acrosporium verbenae, Acrostichum bifurcatum, Acrostichum calomelanos, Acrostichum ebeneum, Acrostichum siliquosum, Acrostichum tartareum, Acrostichum thalictroides, Acrotelsa collaris, Acrotelsella impudica, Acrothamnion preissii, Acrothamnion pulchellum, Acrothrix gracilis, Acrotona adjuvans, Acrotona dilutipennis, Acrotona parens, Acrotona pseudotenera, Acrotrichis cognata, Acrotrichis henrici, Acrotrichis insularis, Acrotrichis josephi, Acrotrichis sanctaehelenae, Actaea alba, Actaea arguta, Actaea aspleniifolia, Actaea dioica, Actaea erythrocarpa, Actaea racemosa, Actaea rubra, Actaea savignii, Actaeodes tomentosus, Actartife angustifolia, Actartife cuneifolia, Acteocina crithodes, Acteocina mucronata, Actias isabellae, Actinea biternata, Actinella lanata, Actinidia arguta, Actinidia chinensis f. chlorocarpa, Actinidia chinensis var. deliciosa, Actinidia chinensis, Actinidia deliciosa, Actinidia giraldii, Actinidia japonica, Actinidia megalocarpa, Actinidia multipetaloides, Actinidia platyphylla, Actinobacillus rossii, Actinocleidus oculatus, Actinocleidus recurvatus, Actinocyclus normanii, Actinocyclus secundus, Actinodoris tilesii, Actinomeris alata, Actinomeris alternifolia, Actinopteryx fucicola, Actumnus globulus, Actumnus nudus, Acuan depressum, Acuan glandulosa, Acuan glandulosum, Acuan illinoense, Acuan illinoensis, Acuan texanum, Acuan tracyi, Acuan virgatum, Acularia nodosa, Aculops allotrichus, Aculops fuchsiae, Aculops gleditsiae, Aculops lycopersici, Aculops pelekassi, Aculops rhodensis, Aculus hippocastani, Aculus ligustri, Acyrthosiphon auriculae, Acyrthosiphon caraganae, Acyrthosiphon ignotum, Acyrthosiphon kondoi, Acyrthosiphon malvae, Acyrthosiphon pelagonii, Acyrthosiphon pisum, Acyrthosiphon primulae, Acyrthosiphon rosaefoliae, Adamsia scilloides, Adelactaeon amoenus, Adelactaeon fulvus, Adelencyrtus aulacaspidis, Adelges abietis, Adelges cooleyi, Adelges coweni, Adelges laricis, Adelges merkeri, Adelges nordmannianae, Adelges piceae, Adelges prelli, Adelges tsugae, Adelges viridana, Adelges viridis, Adelges viridula, Adelopus balsamicola, Adelopus gaeumannii, Adelopus nudus, Adelosina carinatastriata, Adenocaulon adhaerescens, Adenocaulon himalaicum, Adenogyna sarmentosa, Adenolinum angustifolium, Adenolinum grandiflorum, Adenolinum perenne, Adenoscilla bifolia, Adenoscilla nivalis, Adenoscilla unifolia, Adenosepalum pulchrum, Adenostyles albida, Adenostyles albifrons, Adenostyles alliariae, Adenostyles hirsuta, Adenostyles kerneri, Adhatoda arborea, Adhatoda vasica, Adhatoda zeylanica, Adiantum africanum, Adiantum capillus, Adiantum capillus-veneris var. modestum, Adiantum capillus-veneris var. protrusum, Adiantum capillus-veneris, Adiantum colpodes, Adiantum coriandrifolium, Adiantum cuneatum, Adiantum diaphanum, Adiantum formosum, Adiantum hastatum, Adiantum hispidulum f. strictum, Adiantum hispidulum, Adiantum michelii, Adiantum modestum, Adiantum moorei, Adiantum paradiseae, Adiantum pseudocapillus, Adiantum raddianum, Adiantum remyanum, Adiantum schaffneri, Adiantum setulosum, Adiantum tinctum, Adiantum trifidum, Adiantum werckleanum, Adicea hyalina, Adicea microphylla, Adipera bicapsularis, Adipera corymbosa, Adipera laevigata, Adipera spiciflora, Adipera tomentosa, Adistemia watsoni, Adonis aestivalis subsp. aestivalis, Adonis aestivalis var. citrina, Adonis annua subsp. autumnalis, Adonis annua subsp. baetica, Adonis annua, Adonis anomala, Adonis autumnalis, Adonis baetica, Adonis caudata, Adonis cretica, Adonis dentata subsp. intermedia, Adonis dentata subsp. microcarpa, Adonis flammea subsp. polypetala, Adonis flammea, Adonis intermedia, Adonis involucrata, Adonis microcarpa subsp. intermedia, Adonis microcarpa, Adota maritima, Adoxophyes orana, Adventina ciliata, Adventina parviflora, Adyseton alyssoides, Adyseton calycinum, Adyseton campestre, Adyseton dentatum, Adyseton edentulum, Adyseton gemonense, Adyseton maritimum, Adyseton mutabile, Adyseton petalodes, Adyseton saxatile, Adyseton sibiricum, Adyseton vernale, Aecidium aegopodii, Aecidium anchusae, Aecidium anemones, Aecidium aquilegiae, Aecidium asclepiadeum, Aecidium asperifolii var. asperifolii, Aecidium asperifolii var. cynoglossi, Aecidium asperifolii var. lycopsidis-arvensis, Aecidium asperifolii var. symphyti-tuberosi, Aecidium asperifolii var. urticae, Aecidium asperifolii, Aecidium aviculariae, Aecidium berberidis, Aecidium bunii sensu auct., Aecidium bunii var. poterii, Aecidium bunii var. smyrnii-olusatri, Aecidium calthae, Aecidium cancellatum, Aecidium candidum, Aecidium compositarum var. silphii, Aecidium compositarum var. tussilaginis, Aecidium cornutum, Aecidium crassum var. phillyreae, Aecidium cydoniae, Aecidium deutziae, Aecidium erythronii, Aecidium euphorbiae, Aecidium euphorbiarum, Aecidium ficariae, Aecidium fuscum, Aecidium galii ss ambiguum, Aecidium galii var. galii, Aecidium galii, Aecidium geranii, Aecidium hellebori, Aecidium leguminosarum, Aecidium leucospermum sensu auct., Aecidium limonii, Aecidium luminatum, Aecidium lychnidis schultz, Aecidium lycoctoni, Aecidium menthae, Aecidium ornithogaleum, Aecidium oxalidis, Aecidium patriniae, Aecidium periclymeni, Aecidium petasitidis, Aecidium phyllyreae, Aecidium pimpinellae, Aecidium pini, Aecidium plantaginis, Aecidium poterii, Aecidium punctatum, Aecidium pyrolatum, Aecidium quadrifidum, Aecidium ranunculacearum var. aquilegiae, Aecidium ranunculacearum var. aquilegiae-vulgaris, Aecidium ranunculacearum var. clematidis, Aecidium ranunculacearum var. thalictri, Aecidium ranunculacearum, Aecidium rubellum ss sparsum, Aecidium rubellum, Aecidium rumicis, Aecidium sanguinolentum, Aecidium silphii, Aecidium smyrnii, Aecidium statices, Aecidium strobilinum, Aecidium thalictri, Aecidium thymi, Aecidium tussilaginis, Aecidium umbelliferarum, Aecidium urticae, Aecidium valerianellae, Aecidium violaceum, Aecidium violae, Aedes albopictus, Aedes cinereus, Aedes euochrus, Aedes japonicus, Aedes koreicus, Aedes montcalmi, Aedes vexans, Aegilonearum juvenale, Aegilopodes triuncialis subsp. triuncialis, Aegilopodes triuncialis, Aegilops agropyroides, Aegilops algeriensis, Aegilops aristata, Aegilops aucheri, Aegilops augeri, Aegilops brachyathera, Aegilops calida, Aegilops campicola, Aegilops caudata subsp. cylindrica, aegilops caudata, Aegilops columnaris, Aegilops contracta, Aegilops croatica, Aegilops cylindrica subsp. aristulata, Aegilops cylindrica subsp. pauciaristata, Aegilops cylindrica var. albescens, Aegilops cylindrica var. aristulata, Aegilops cylindrica var. brunnea, Aegilops cylindrica var. ferruginea, Aegilops cylindrica var. flavescens, Aegilops cylindrica var. fuliginosa, Aegilops cylindrica var. kastorianum, Aegilops cylindrica var. multiaristata, Aegilops cylindrica var. pauciaristata, Aegilops cylindrica var. prokhanovii, Aegilops cylindrica var. rubiginosa, Aegilops cylindrica var. rumelica, Aegilops cylindrica, Aegilops divaricata, Aegilops echinata, Aegilops echinus, Aegilops elongata, Aegilops erigens, Aegilops erratica, Aegilops fausii, Aegilops fonsii, Aegilops fragilis, Aegilops geniculata subsp. gibberosa, Aegilops geniculata, Aegilops hordeiformis, Aegilops incurva, Aegilops incurvata, Aegilops juvenalis, Aegilops macrura, Aegilops markgrafii, Aegilops mesantha, Aegilops microstachys, Aegilops neglecta var. contorta, Aegilops neglecta, Aegilops nigricans, Aegilops ovata subsp. atlantica, Aegilops ovata subsp. biuncialis, Aegilops ovata subsp. gibberosa, Aegilops ovata subsp. triaristata, Aegilops ovata var. triaristata, Aegilops ovata, Aegilops parvula, Aegilops persica, Aegilops procera, Aegilops pubiglumis, Aegilops recta, Aegilops saccharinum, Aegilops sicula, Aegilops singularis, Aegilops speltoides, Aegilops squarrosa subsp. squarrosa, Aegilops squarrosa var. anathera, Aegilops squarrosa, Aegilops strangulata, Aegilops subulata, Aegilops tauschii, Aegilops triaristata subsp. contorta, Aegilops triaristata subsp. intermixta, Aegilops triaristata, Aegilops triuncialis subsp. orientalis, Aegilops triuncialis, Aegilops turcomanica, Aegilops vagans, Aegilops ventricosa, Aegilops virescens, Aegilops viridescens, Aegle sepiaria, Aegochloa pungens, Aegochloa torreyi, Aegonychon arvense, Aegonychon purpurocaeruleum, Aegonychon repens, Aegopinella nitens, Aegopinella nitidula, Aegopinella pura, Aegopis verticillus, Aegopodium angelicifolium, Aegopodium podagraria var. variegatum, Aegopodium podagraria, Aegopodium simplex, Aegopodium tribracteolatum, Aegoseris setosa, Aegypius monachus, Aeluropus intermedius, Aeluropus korshinskyi, Aeluropus littoralis, Aeluropus micrantherus, Aeluropus pungens, Aeluropus sinensis, Aenasius flandersi, Aeolidiella indica, Aeolidiella takanosimensis, Aeolis foulisi, Aeolosoma headleyi, Aeolothrips collaris, Aeolothrips fasciatus, Aeolothrips faurei, Aeolothrips ghabni, Aeolothrips linarius, Aeolothrips meridionalis, Aeolothrips tenuicornis, Aeolothrips wittmeri, Aeonium arboreum, Aeonium caespitosum, Aeonium cuneatum, Aeonium decorum, Aeonium doramae, Aeonium glutinosum, Aeonium haworthii, Aeonium manriqueorum, Aeonium simsii, Aequorea conica, Aequorea globosa, Aequorea macrodactyla, Aequorea vitrina, Aerococcus viridans, Aeromonas salmonicida salmonicida, Aeromonas salmonicida subsp. salmonicida, Aeschynomene americana var. depila, Aeschynomene americana var. glandulosa, Aeschynomene americana var. longifolia, Aeschynomene americana, Aeschynomene cachemiriana, Aeschynomene cannabina, Aeschynomene diffusa, Aeschynomene evenia, Aeschynomene glaberrima, Aeschynomene glandulosa, Aeschynomene indica var. punctata, Aeschynomene indica var. viscosa, Aeschynomene indica, Aeschynomene javanica var. luxurians, Aeschynomene kashmiriana, Aeschynomene macropoda, Aeschynomene mexicana, Aeschynomene mimosula, Aeschynomene mimulosa, Aeschynomene montana, Aeschynomene oligantha, Aeschynomene pumila, Aeschynomene punctata, Aeschynomene quadrata, Aeschynomene richardiana, Aeschynomene roxburghii, Aeschynomene sesban, Aeschynomene subviscosa, Aeschynomene tricholoma, Aeschynomene virginica, Aeschynomene viscidula, Aesculus alba, Aesculus asplenifolia, Aesculus austrina, Aesculus carnea, Aesculus discolor flavescens, Aesculus discolor, Aesculus flava, Aesculus hippocastanum, Aesculus humilis, Aesculus indica, Aesculus lutea, Aesculus lyonii, Aesculus macrostachya, Aesculus macrostachys, Aesculus maxima, Aesculus memmingeri, Aesculus mollis, Aesculus octandra var. vestita, Aesculus octandra var. virginica, Aesculus octandra, Aesculus odorata, Aesculus parviflora, Aesculus pavia, Aesculus procera, Aesculus pubescens, Aesculus rubescens, Aesculus rubra, Aesculus septenata, Aesculus splendens, Aesculus versicolor, Aesculus whitleyi, Aesculus x carnea, Aesculus x rubicunda, Aetheorhiza bulbosa, Aethina tumida, Aethionema longistylum, Aethionema saxatile, Aethiopis sclarea, Aethiopis vera, Aethusa agrestis, Aethusa ammi, Aethusa bunius, Aethusa cynapioides, Aethusa cynapium subsp. agrestis, Aethusa cynapium subsp. cynapioides, Aethusa cynapium subsp. cynapium, Aethusa cynapium subsp. elata, Aethusa cynapium subsp. gigantea, Aethusa cynapium subsp. segetalis, Aethusa cynapium var. agrestis, Aethusa cynapium var. domestica, Aethusa cynapium var. gigantea, Aethusa elata, Aethusa leptophylla, Aethusa meum, Aethusa montana, Aethusa segetalis, Aethusa tenuifolium, Aeverrillia setigera, Afrocardium richardi, Afropunctum mermodi, Afropunctum seminium, Agabiformius lentus, Agaloma angustifolia, Agaloma graminifolia, Agaloma marginata, Agama agama, Agama planiceps, Agama stellio, Aganaspis daci, Agapanthus giganteus, Agapanthus medius, Agapanthus multiflorus, Agapanthus orientalis, Agapanthus praecox subsp. orientalis, Agapanthus praecox, Agapanthus variegatus, Agapornis cana, Agapornis canus, Agapornis fischeri, Agapornis lilianae, Agapornis personata, Agapornis personatus, Agapornis pullarius, Agapornis roseicollis, Agardhiella gaudichaudii, Agardhiella subulata, Agaricus adhaerens, Agaricus alphitophorus, Agaricus americanus, Agaricus antillarum, Agaricus birnbaumii, Agaricus bovinus, Agaricus bresadolae, Agaricus cepistipes var. cretaceus, Agaricus cheimonoceps, Agaricus cretaceus var. cretaceus, Agaricus cretaceus, Agaricus dubius, Agaricus edodes, Agaricus esculentus var. aquilus, Agaricus esculentus var. dubius, Agaricus esculentus var. esculentus, Agaricus esculentus var. vernalis, Agaricus esculentus, Agaricus flos-sulphuris, Agaricus fuscus, Agaricus glutinosus, Agaricus granulatus, Agaricus ianthinus, Agaricus luteus, Agaricus maculatus, Agaricus mitratus, Agaricus olearius, Agaricus opuntiae, Agaricus percevalii, Agaricus psammopus, Agaricus rorulentus panizzi, Agaricus squamosus f. aurantiacus, Agaricus straminellus, Agaricus tenacellus, Agaricus thraustus var. aurantiacus, Agaricus velatus, Agaricus viscidus var. atropunctus, Agaricus zeylanicus, Agassiziella angulipennis, Agastache anethiodora, Agastache foeniculum, Agastache glaucifolia, Agastache urticifolia, Agathis brownii, Agathis macrophylla, Agathis obtusa, Agathis vitiensis, Agathomyia wankowiczii, Agathophytum acuminatum, Agathophytum bonus-henricus, Agathophytum crassifolium, Agathophytum glaucum, Agathyrsus macrophyllus, Agathyrsus plumieri, Agathyrsus sibiricus, Agatophyton bonus-henricus, Agave aboriginum, Agave amaniensis, Agave americana subsp. americana, Agave americana var. marginata, Agave americana var. mediopicta, Agave americana var. striata, Agave angustifolia, Agave atrovirens, Agave attenuata, Agave bergeri, Agave bonnetiana, Agave breedlovei, Agave bromeliifolia, Agave bulbosa, Agave canartiana, Agave cernua, Agave coccinea, Agave commelyni, Agave costaricana, Agave cuspidata, Agave deflexispina, Agave donnell-smithii, Agave elongata, Agave endlichiana, Agave excelsa, Agave ferox, Agave flaccida, Agave flavovirens, Agave foetida, Agave fourcroydes var. espiculata, Agave fourcroydes, Agave gigantea, Agave glaucescens, Agave gracilis, Agave houlletii, Agave ixtli, Agave ixtlioides, Agave jacquiniana, Agave kirchneriana, Agave latissima, Agave lespinassei, Agave lurida, Agave macroculmis, Agave madagascariensis, Agave mirabilis, Agave ottonis, Agave owenii, Agave pacifica, Agave panamana, Agave polianthes, Agave prainiana, Agave prolifera, Agave punctata, Agave ragusae, Agave rigida var. elongata, Agave rigida var. sisalana, Agave rigida, Agave salmiana var. ferox, Agave schlechtendahlii, Agave segurae, Agave serrulata, Agave sicifolia, Agave sisalana var. armata, Agave sisalana, Agave sullivanii, Agave tehuacanensis, Agave theoxmuliana, Agave tuberosa, Agave vivipara, Agave wightii, Agave yaquiana, Agave yxtli, Agave zapupe, Agdistis adactyla, Agelaius phoeniceus, Ageniaspis citricola, Ageniaspis fuscicollis, Ageomoron royenii, Ageratina adenophora, Ageratina ageratoides, Ageratina altissima, Ageratina riparia, Ageratina ventillana, Ageratum altissimum, Ageratum houstonianum, Ageratum mexicanum, Ageratum wendlandii, Agerella acinifolia, Agerella arvensis, Agerella verna, Agglutinella compressa, Agglutinella robusta, Aglaospora profusa, Aglaothamnion feldmanniae, Aglaothamnion halliae, Aglaothamnion westbrookiae, Aglaura fulgida, Aglaurides erythraeensis symmetrica, Aglaurides erythraeensis, Aglaurides fulgida, Aglenus brunneus, Aglitheis carinata, Aglitheis ursina, Aglossa caprealis, Aglossa pinguinalis, Aglotoma multiflora, Aglyptinus agathidioides, Agnus-castus robusta, Agnus-castus vulgaris, Agorrhinum orontium, Agostana divaricata, Agraphis campanulata, Agraphis cernua, Agraphis nutans, Agraphis patula, Agraulus anemagrostoides, Agrestis alba, Agrestis hyemalis, Agrestis interrupta, Agrestis polymorpha, Agrestis verticillata, Agrilus angustulus, Agrilus feretrius, Agrilus marcopoli, Agrilus planipennis, Agrilus sinuatus, Agrilus ulmi, Agrimonia acutifolia, Agrimonia agrimonoides, Agrimonia conopsea, Agrimonia convergens, Agrimonia dahurica, Agrimonia davurica, Agrimonia eupatoria subsp. davurica, Agrimonia eupatoria subsp. grandis, Agrimonia eupatoria subsp. odorata, Agrimonia eupatoria subsp. procera, Agrimonia eupatoria var. dahurica, Agrimonia eupatoria var. daurica, Agrimonia eupatoria var. davurica, Agrimonia eupatoria var. grandis, Agrimonia eupatoria var. japonica, Agrimonia eupatoria var. major, Agrimonia eupatoria var. nepalensis, Agrimonia eupatoria var. pilosa, Agrimonia eupatoria var. procera, Agrimonia eupatoria, Agrimonia glabrata, Agrimonia glandulosa, Agrimonia godetiana, Agrimonia gotectiana, Agrimonia graeca, Agrimonia grandis, Agrimonia japonica, Agrimonia lanata, Agrimonia leroyi, Agrimonia nepalensis var. obovata, Agrimonia nepalensis, Agrimonia obtusifolia, Agrimonia odorata var. procera, Agrimonia odorata var. suaveolens, Agrimonia pilosa subsp. japonica, Agrimonia pilosa var. setulosa, Agrimonia pilosa var. viscidula, Agrimonia pilosa, Agrimonia procera, Agrimonia repens, Agrimonia robusta, Agrimonia soropia, Agrimonia sororia, Agrimonia striata subsp. pilosa, Agrimonia suaveolens, Agrimonia suffrutescens var. rotundata, Agrimonia suffrutescens, Agrimonia viscidula var. japonica, Agrimonia viscidula, Agrimonia zeylandica, Agrimonioides stenantha, Agriolimax agrestis, Agriolimax bakurianus, Agriolimax caspius, Agriolimax laevis, Agriolimax lombricoides, Agriolimax melanocephalus, Agriolimax murinus, Agriolimax oertzeni, Agriolimax reticulatus, Agriolimax roseni, Agriolimax schemachensis, Agriolimax sturanyi, Agriolimax thersites, Agriolimax turcicus, Agrionemys horsfieldii, Agriotes sordidus, Agrobacterium radiobacter, Agrobacterium rhizogenes, Agrobacterium tumefaciens, Agrocybe putaminum, Agromyza flaveola, Agromyza flaviventris, Agromyza huidobrensis, Agromyza melampyga, Agromyza phaseolunata, Agromyza simplex, Agromyza subpusilla, Agropsar sturninus, Agropyron angarense, Agropyron angustifolium, Agropyron athericum, Agropyron banaticum, Agropyron biforme, Agropyron bonaepartis, Agropyron brevifolium, Agropyron brevissimum, Agropyron caninum subsp. majus, Agropyron caudatum, Agropyron cristatum subsp. dasyanthum, Agropyron cristatum subsp. desertorum, Agropyron cristatum subsp. fragile, Agropyron cristatum subsp. sibiricum, Agropyron cristatum var. desertorum, Agropyron cristatum var. fragile, Agropyron cristatum, Agropyron dasyanthum, Agropyron desertorum, Agropyron distachyon, Agropyron elongatum, Agropyron fibrosum, Agropyron fragile subsp. sibiricum, Agropyron fragile var. sibiricum, Agropyron fragile, Agropyron geminatum, Agropyron glaucum var. intermedium, Agropyron glaucum var. occidentale, Agropyron glaucum, Agropyron gracile, Agropyron halleri, Agropyron hirsutum, Agropyron hispanicum, Agropyron hispidum, Agropyron intermedium var. intermedium, Agropyron intermedium, Agropyron junceum var. repens, Agropyron kotschyanum, Agropyron latronum, Agropyron litorale, Agropyron longiglume, Agropyron marginatum, Agropyron missuricum, Agropyron molle, Agropyron occidentale var. molle, Agropyron occidentale var. occidentale, Agropyron occidentale var. palmeri, Agropyron occidentale, Agropyron orientale var. medians, Agropyron orientale, Agropyron palmeri, Agropyron patulum, Agropyron pauciflorum subsp. majus, Agropyron pauciflorum, Agropyron pectinatum, Agropyron pinnatum, Agropyron poa, Agropyron prostratum var. biflorum, Agropyron prostratum, Agropyron pubescens, Agropyron pumilum, Agropyron pungens subsp. athericum, Agropyron pycnantum, Agropyron repens f. aristatum, Agropyron repens f. geniculatum, Agropyron repens f. heberhachis, Agropyron repens f. pilosum, Agropyron repens f. repens, Agropyron repens f. setiferum, Agropyron repens f. stoloniferum, Agropyron repens f. trichorrhachis, Agropyron repens f. vaillantianum, Agropyron repens subvar. pubescens, Agropyron repens var. aristatum, Agropyron repens var. glaucum, Agropyron repens var. nemorale, Agropyron repens var. pilosum, Agropyron repens var. pubescens, Agropyron repens var. repens, Agropyron repens var. subulatum, Agropyron repens var. vaillantianum, Agropyron repens var. vulgare, Agropyron repens, Agropyron sachalinense, Agropyron scabrum, Agropyron sibiricum var. desertorum, Agropyron sibiricum, Agropyron sinkiangense, Agropyron smithii f. molle, Agropyron smithii var. molle, Agropyron smithii var. palmeri, Agropyron smithii var. smithii, Agropyron smithii var. typica, Agropyron smithii, Agropyron spicatum var. molle, Agropyron spicatum var. palmeri, Agropyron spicatum var. viride, Agropyron squarrosum, Agropyron subulatum, Agropyron tenerum subsp. majus, Agropyron tenerum subsp. trichocoleum, Agropyron tenerum var. longifolium, Agropyron tenerum, Agropyron tenuiculum, Agropyron tournefortii, Agropyron trachycaulum var. majus, Agropyron trachycaulum var. tenerum, Agropyron trachycaulum var. trachycaulum, Agropyron triticeum, Agropyron turkestanicum, Agropyron unilaterale, Agropyron vaillantianum, Agropyron variegatum, Agropyron villosum, Agropyron violaceum var. major, Agropyron wangii, Agropyron x brevifolium, Agropyrum cristatum subsp. fragile, Agrosinapis arvensis, Agrostemma chalcedonica, Agrostemma coeli-rosea, Agrostemma coronaria, Agrostemma githago subsp. githago, Agrostemma githago subsp. thessalum, Agrostemma githago var. githago, Agrostemma linicola, Agrostemma sylvestris, Agrostis aculeata, Agrostis adscendens, Agrostis aenea, Agrostis africana, Agrostis africanus, Agrostis alascana, Agrostis alashana, Agrostis alaskana var. breviflora, Agrostis alaskana, Agrostis alba alba, Agrostis alba f. alba, Agrostis alba f. aristata, Agrostis alba f. aristigera, Agrostis alba f. maritima, Agrostis alba f. natans, Agrostis alba subsp. castellana, Agrostis alba subsp. decumbens, Agrostis alba subsp. filifolia, Agrostis alba subsp. gigantea, Agrostis alba subsp. maritima, Agrostis alba subsp. stolonifera, Agrostis alba subsp. vulgaris, Agrostis alba subvar. decumbens, Agrostis alba subvar. pumila, Agrostis alba var. albida, Agrostis alba var. aristata, Agrostis alba var. condensata, Agrostis alba var. conferta, Agrostis alba var. decumbens, Agrostis alba var. densiflora, Agrostis alba var. diffusa, Agrostis alba var. dispar, Agrostis alba var. foucaudi, Agrostis alba var. gigantea, Agrostis alba var. glaucescens, Agrostis alba var. gracilis, Agrostis alba var. maior, Agrostis alba var. maritima, Agrostis alba var. minor, Agrostis alba var. olivetorum, Agrostis alba var. pallida, Agrostis alba var. patula, Agrostis alba var. pontica, Agrostis alba var. prorepens, Agrostis alba var. silvatica, Agrostis alba var. straminea, Agrostis alba var. stricta, Agrostis alba var. sylvatica, Agrostis alba var. tenuis, Agrostis alba var. verticillata, Agrostis alba var. vulgaris, Agrostis alba, Agrostis albicans, Agrostis albida, Agrostis alopecuroides, Agrostis ambigua, Agrostis ampla f. monolepis, Agrostis ampla, Agrostis anatolica, Agrostis anemagrostis subsp. interrupta, Agrostis anemagrostis subsp. spica-venti, Agrostis anemagrostis, Agrostis anemagrostoides, Agrostis antecedens, Agrostis apetala, Agrostis aphanes, Agrostis aquatica, Agrostis aristulata, Agrostis articulata, Agrostis arundinacea, Agrostis aspera, Agrostis asperifolia, Agrostis atroviolacea, Agrostis australis, Agrostis avenacea, Agrostis azorica, Agrostis barbata var. senegalensis, Agrostis barbata, Agrostis berlandieri, Agrostis bermudiana, Agrostis billardierei, Agrostis boetica, Agrostis bolivaris, Agrostis brachystachys, Agrostis brevis, Agrostis bromoides, Agrostis bryoides, Agrostis byzantina, Agrostis caespitosa, Agrostis calamagrostis, Agrostis campestris, Agrostis canariensis, Agrostis candollei, Agrostis canescens, Agrostis canina var. aenea, Agrostis canina var. hiemalis, Agrostis canina var. hyemalis, Agrostis canina var. melaleuca, Agrostis capillaris Pollich, Agrostis capillaris subsp. castellana, Agrostis capillaris subsp. olivetorum, Agrostis capillaris var. aristata, Agrostis capillaris var. aristulata, Agrostis capillaris var. nigra, Agrostis capillaris var. olivetorum, Agrostis capillaris var. pumila, Agrostis capillaris x castellana, Agrostis capillaris x gigantea, Agrostis capillaris, Agrostis caryophyllea, Agrostis castellana subsp. byzantina, Agrostis castellana var. hispanica, Agrostis castellana var. olivetorum, Agrostis castellana, Agrostis cavanillesiana, Agrostis ceretana, Agrostis cespitosa, Agrostis chamissonis, Agrostis ciliata, Agrostis cinna, Agrostis collicola, Agrostis comosa, Agrostis compressa, Agrostis condensata, Agrostis congener, Agrostis crinita, Agrostis cryptandra, Agrostis dalmatica, Agrostis debilis, Agrostis decumbens, Agrostis densa, Agrostis densissima, Agrostis depressa, Agrostis diandra, Agrostis difficilis, Agrostis diffusa, Agrostis diluta, Agrostis dispar, Agrostis divaricata, Agrostis dregeana, Agrostis drummondii, Agrostis durangensis, Agrostis elongata var. flaccida, Agrostis elongata, Agrostis epigeios, Agrostis eriantha, Agrostis exarata f. asperifolia, Agrostis exarata subsp. exarata, Agrostis exarata subsp. minor, Agrostis exarata var. aenea, Agrostis exarata var. exarata, Agrostis exarata var. minor, Agrostis exarata var. monolepis, Agrostis exarata var. mutica, Agrostis exarata var. pacifica, Agrostis exarata var. purpurascens, Agrostis exarata, Agrostis exilis, Agrostis fertilis, Agrostis filiculmis, Agrostis filifolia, Agrostis filiformis, Agrostis flava, Agrostis foliosa, Agrostis forsteri, Agrostis frondosa, Agrostis geminata f. exaristata, Agrostis geminata f. geminata, Agrostis geminata, Agrostis gigantea subsp. pontica, Agrostis gigantea var. dispar, Agrostis gigantea var. praticola, Agrostis gigantea, Agrostis glaucescens, Agrostis glutinosa, Agrostis gracilis, Agrostis grandis, Agrostis graniticola, Agrostis gredensis, Agrostis gymnostyla, Agrostis hiemalis var. geminata, Agrostis hiemalis var. laxiflora, Agrostis hiemalis, Agrostis hispanica, Agrostis hispida, Agrostis humifusa, Agrostis huttoniae, Agrostis hyemalis f. exaristata, Agrostis hyemalis f. tuckermanii, Agrostis hyemalis var. geminata, Agrostis hyemalis var. hyemalis, Agrostis hyemalis var. keweenawensis, Agrostis hyemalis var. laxiflora, Agrostis hyemalis var. nutkaensis, Agrostis hyemalis var. scabra, Agrostis hyemalis var. tenuis, Agrostis hyemalis, Agrostis incurvata, Agrostis indica, Agrostis inflata, Agrostis intermedia, Agrostis interrupta, Agrostis jacutica, Agrostis juncea, Agrostis karsensis, Agrostis kauaiensis, Agrostis kitaibelii, Agrostis lachnantha, Agrostis langei, Agrostis lasiantha, Agrostis lateriflora, Agrostis laxa, Agrostis laxiflora var. caespitosa, Agrostis laxiflora var. montana, Agrostis laxiflora var. scabra, Agrostis laxiflora var. tenuis, Agrostis laxiflora, Agrostis lendigera, Agrostis lenta, Agrostis leonii, Agrostis leptos, Agrostis ligulata, Agrostis lithuanica, Agrostis littoralis, Agrostis longiligula var. australis, Agrostis longiligula var. longiligula, Agrostis longiligula, Agrostis lusitanica, Agrostis macrantha, Agrostis maritima var. clementei, Agrostis maritima, Agrostis melaleuca, Agrostis mexicana, Agrostis michauxii var. laxiflora, Agrostis microphylla var. major, Agrostis miliacea, Agrostis milium-comosum, Agrostis minima, Agrostis moldavica, Agrostis monandra, Agrostis muelleri, Agrostis muricata, Agrostis navarroi, Agrostis nebulosa, Agrostis neesii, Agrostis neglecta, Agrostis nemoralis, Agrostis nigra, Agrostis nootkaensis, Agrostis nutkaensis, Agrostis oligantha, Agrostis olivetorum, Agrostis oregonensis, Agrostis orientalis, Agrostis oseroensis, Agrostis pallida, Agrostis palustris var. stolonifera, Agrostis palustris var. stricta, Agrostis palustris, Agrostis panicea, Agrostis parlatorei, Agrostis patula, Agrostis pauciflora, Agrostis pauzhetica, Agrostis peckii, Agrostis pectinata, Agrostis perezii, Agrostis phleoides, Agrostis plumosa, Agrostis polymorpha var. capillaris, Agrostis polymorpha var. pumila, Agrostis polymorpha var. sylvatica, Agrostis polymorpha, Agrostis polypogon, Agrostis pourretii, Agrostis praticola, Agrostis procera, Agrostis prorepens, Agrostis prostrata, Agrostis pseudoalba, Agrostis pseudopungens, Agrostis pumila, Agrostis pungens, Agrostis purpurea, Agrostis pyramidalis, Agrostis pyramidata, Agrostis radiata, Agrostis ramosa, Agrostis ramosissima, Agrostis refracta, Agrostis reptans, Agrostis retroflexa, Agrostis retrofracta, Agrostis rivularis, Agrostis robinsonii, Agrostis robusta, Agrostis rubra var. pumila, Agrostis rubra var. tenella, Agrostis sabulicola, Agrostis salina, Agrostis salmantica, Agrostis scabra f. exaristata, Agrostis scabra f. setigera, Agrostis scabra f. tuckermanii, Agrostis scabra subsp. septentrionalis, Agrostis scabra var. aristata, Agrostis scabra var. geminata, Agrostis scabra var. keweenawensis, Agrostis scabra var. montana, Agrostis scabra var. oreophila, Agrostis scabra var. scabra, Agrostis scabra var. septentrionalis, Agrostis scabra var. tenuis, Agrostis scabra, Agrostis scabrata, Agrostis scabrescens, Agrostis scabrida, Agrostis scabriglumis, Agrostis scabriuscula, Agrostis schottii, Agrostis scouleri, Agrostis seminuda, Agrostis semiverticillata, Agrostis sepium, Agrostis sibirica, Agrostis signata, Agrostis simulans, Agrostis sinaica, Agrostis sokolovskajae, Agrostis solandri, Agrostis spica-venti subsp. interrupta, Agrostis spica-venti var. interrupta, Agrostis spica-venti, Agrostis spicigera, Agrostis sporobolus, Agrostis stipata, Agrostis stolonifera f. alba, Agrostis stolonifera f. diffusa, Agrostis stolonifera f. gracilis, Agrostis stolonifera f. natans, Agrostis stolonifera f. pontica, Agrostis stolonifera subsp. castellana, Agrostis stolonifera subsp. filifolia, Agrostis stolonifera subsp. gigantea, Agrostis stolonifera subsp. maritima, Agrostis stolonifera subsp. stolonifera, Agrostis stolonifera var. alba, Agrostis stolonifera var. angustifolia, Agrostis stolonifera var. bottnica, Agrostis stolonifera var. decumbens, Agrostis stolonifera var. densiflora, Agrostis stolonifera var. diffusa, Agrostis stolonifera var. dulcis, Agrostis stolonifera var. effusa, Agrostis stolonifera var. flagellare, Agrostis stolonifera var. gigantea, Agrostis stolonifera var. hispanica, Agrostis stolonifera var. hispida, Agrostis stolonifera var. major, Agrostis stolonifera var. maritima, Agrostis stolonifera var. minor, Agrostis stolonifera var. patula, Agrostis stolonifera var. prorepens, Agrostis stolonifera var. pumila, Agrostis stolonifera var. stolonifera, Agrostis stolonifera var. straminea, Agrostis stolonifera var. tenella, Agrostis stolonifera var. tenuis, Agrostis stolonifera var. verticillata, Agrostis stolonifera var. viridula, Agrostis stolonifera var. vulgaris, Agrostis stolonifera, Agrostis stolonizans, Agrostis straminea, Agrostis stricta, Agrostis suavis, Agrostis subspicata, Agrostis sylvatica, Agrostis tarda, Agrostis tehuelcha, Agrostis tenacissima, Agrostis tenella, Agrostis tenuis f. aristata, Agrostis tenuis var. aristata, Agrostis tenuis var. hispida, Agrostis tenuis var. nigra, Agrostis tenuis var. pumila, Agrostis tenuis var. tenuis, Agrostis tenuis, Agrostis tenuissima, Agrostis torreyi, Agrostis transcaspica, Agrostis tremula, Agrostis trichotoma, Agrostis tricuspidata, Agrostis trinervata, Agrostis umbrosa, Agrostis vaginiflora, Agrostis valentina, Agrostis varia, Agrostis varians, Agrostis ventosa, Agrostis ventricosa, Agrostis vernalis, Agrostis verticillata, Agrostis vestita, Agrostis villarsii, Agrostis violacea, Agrostis virginica, Agrostis viridis, Agrostis virletii, Agrostis vivipara, Agrostis vulgaris var. alba, Agrostis vulgaris var. aristata, Agrostis vulgaris var. hispida, Agrostis vulgaris var. nigra, Agrostis vulgaris var. pumila, Agrostis vulgaris var. tenella, Agrostis vulgaris, Agrostis welwitschii, Agrostis x bjoerkmanii, Agrostis x bodaibensis, Agrostis x fouilladeana, Agrostis x fouilladei, Agrostis x gigantifera, Agrostis zerovii, Agrostomia barbata, Agrostothrips meridionalis, Ahasverus advena, Ahasverus angustatus, Ahasverus excisus, Ahasverus guerini, Ahasverus musaeorum, Ahasverus striatus, Ahnfeltiopsis flabelliformis, Aichryson laxum, Aidanosagitta neglecta, Aigeiros deltoides, Aigiros balsamifera, Ailanthus altissima, Ailanthus cacodendron, Ailanthus erythrocarpa, Ailanthus esquirolii, Ailanthus giraldii, Ailanthus glandulosa, Ailanthus japonica, Ailanthus peregrina, Ailanthus pongelion, Ailanthus procera, Ailanthus rhodoptera, Ailanthus rubra, Ailanthus vilmoriniana, Aiptasia pulchella, Aiptasiomorpha luciae, Aipyanthus echioides, Aira aetnensis, Aira alpicola, Aira ambigua, Aira andraei, Aira arctica, Aira aristulata, Aira articulata, Aira australis, Aira bottnica, Aira breviaristata, Aira breviculmis, Aira brevifolia, Aira bulbosa, Aira byzantina, Aira caespitosa, Aira calycina, Aira canescens, Aira capensis, Aira capillacea, Aira capillaris subsp. ambigua, Aira capillaris var. ambigua, Aira capillaris, Aira caryophyllea subsp. multiculmis, Aira caryophyllea var. capillaris, Aira caryophyllea var. major, Aira caryophyllea var. minor, Aira caryophyllea, Aira cespitosa, Aira chrysophaena, Aira congener, Aira corsica, Aira cristata, Aira cuprina, Aira curtifolia, Aira dactyloides, Aira danthonioides, Aira divaricata, Aira elegans subsp. ambigua, Aira elegans subsp. notarisiana, Aira elegans, Aira elegantissima subsp. ambigua, Aira elegantissima subsp. hosteana, Aira elegantissima, Aira festucoides, Aira gracilis, Aira hartmaniana, Aira holcus-mollis, Aira laevigata, Aira latigluma, Aira littoralis, Aira macrantha, Aira mollis, Aira mucronata, Aira neutralis, Aira notarisiana, Aira nutans, Aira paludosa, Aira parviflora, Aira poiformis, Aira pulchra, Aira pungens, Aira sabuletorum, Aira sabulonum var. uniflora, Aira sabulonum, Aira semineutra, Aira stolonifera, Aira subulorum, Aira sukatschewii, Aira turczaninowii, Aira varia, Aira variegata, Aira vivipara, Aira wibeliana, Aira wilhelmsii, Airaphilus nasutus, Airella capillaris, Airella caryophyllea, Airella elegans, Airochloa albescens, Airochloa cristata, Airochloa gracilis, Airochloa hispida, Airochloa parviflora, Airopsis brevifolia, Airopsis capillaris, Airopsis caryophyllea, Aix galericulata, Aix sponsa, Aizoanthemum hispanicum, Aizodraba aizoides, Aizoon canariense, Aizoon contaminatum, Aizoon elongatum, Aizoon glinoides, Aizoon hispanicum, Aizoon montevidense, Aizoon procumbens, Aizoon propinquum, Aizoon secundum, Aizoon sessiliflorum, Aizopsis aizoon, Aizopsis ellacombeana, Aizopsis florifera, Aizopsis hybrida, Aizopsis kamtschatica, Ajax asturiensis, Ajax breviflos, Ajax cambricus, Ajax capax, Ajax cernuus, Ajax cuneifolius, Ajax cyclamineus, Ajax fenestralis, Ajax festalis var. plenissimus, Ajax festalis var. plenus, Ajax festalis var. scoticus, Ajax festalis, Ajax festinus, Ajax gayi, Ajax glaucus, Ajax grandiflorus, Ajax hexangularis, Ajax hispanicus, Ajax incomparabilis, Ajax lacinularis, Ajax lobularis, Ajax lusitanicus, Ajax luteus, Ajax major, Ajax montinus, Ajax multicus, Ajax obvallaris, Ajax platylobus, Ajax porrigens, Ajax praelongus, Ajax propinquus, Ajax pygmaeus, Ajax radians, Ajax reflexa, Ajax rudbeckii, Ajax sabiniamus, Ajax serratus var. suavis, Ajax serratus, Ajax sexangularis, Ajax spurius, Ajax telamonius var. grandiplenus, Ajax telamonius var. plenus, Ajax telamonius, Ajax x odorus, Ajuga abnormis, Ajuga alpestris, Ajuga alpicola, Ajuga alpina, Ajuga astolonsa, Ajuga barrelieri, Ajuga breviproles, Ajuga caespitosa, Ajuga candolleana, Ajuga chamaepitys subsp. chia, Ajuga chamaepitys, Ajuga chia, Ajuga comata, Ajuga densiflora, Ajuga foliosa, Ajuga genevensis var. alpicola, Ajuga genevensis var. alpina, Ajuga genevensis var. arida, Ajuga genevensis var. cryptostylon, Ajuga genevensis var. elatior, Ajuga genevensis var. foliosa, Ajuga genevensis var. glabrifolia, Ajuga genevensis var. grossidens, Ajuga genevensis var. integrifolia, Ajuga genevensis var. longistyla, Ajuga genevensis, Ajuga glabra, Ajuga glabrifolia, Ajuga hampeana, Ajuga intermedia, Ajuga interrupta, Ajuga lanata, Ajuga latifolia, Ajuga montana, Ajuga nanti, Ajuga pseudochia, Ajuga pseudopyramidalis, Ajuga pyramidalis, Ajuga repens, Ajuga reptans subvar. densiflora, Ajuga reptans var. albiflora, Ajuga reptans var. alpina, Ajuga reptans, Ajuga rugosa, Ajuga stolonifera, Ajuga trifida, Ajuga trifidifolia, Ajuga vulgaris race candolleana, Ajuga vulgaris subsp. abnormis, Ajuga vulgaris, Akatopora leucocypha, Akebia micrantha, Akebia quinata, Aklema cotinifolia, Aklema scotana, Aklema scotanum, Aklema yavalquahuitl, Akylopsis suaveolens, Alaba semistriata, Alaea substriata, Alauda arvensis, Albersia arenaria, Albersia ascendens, Albersia blitum, Albersia crispa, Albersia deflexa, Albersia emarginata, Albersia livida, Albersia polygonoides, Albersia prostrata, Albertia simplicifolia, Albigo calendulae, Albigo mors-uvae, Albinaria acuticosta, Albinaria adspersa, Albinaria byzantina, Albinaria caerulea, Albinaria centralis, Albinaria chia, Albinaria coa, Albinaria coerulea, Albinaria convexior, Albinaria corrugata inflata, Albinaria cretensis, Albinaria distans, Albinaria dragonarana, Albinaria eudilica, Albinaria extensa, Albinaria farcimen, Albinaria grabusana, Albinaria hippolyti aphrodite, Albinaria hippolyti holtzi, Albinaria humillima, Albinaria idaea, Albinaria insularis, Albinaria interpres, Albinaria janisadana, Albinaria leucoderma, Albinaria maltzani, Albinaria manselli, Albinaria megalostoma, Albinaria microtypica, Albinaria mitis, Albinaria mitylena, Albinaria munda, Albinaria nordsiecki, Albinaria omalica, Albinaria paximadiana, Albinaria phalanga, Albinaria porphyrostoma, Albinaria praeclara parallelifera, Albinaria praeclara praeclara, Albinaria puella, Albinaria samia, Albinaria solidula, Albinaria sphakiota, Albinaria strictecostata, Albinaria strigata, Albinaria subcostata, Albinaria submarginata, Albinaria subvirginea, Albinaria suturalis, Albinaria tenuicostata, Albinaria teres teres, Albinaria venosa, Albinaria vermiculata, Albinaria vesti, Albinaria vexans, Albinaria vianensis, Albinaria virginea, Albizia distachya, Albizia julibrissin, Albizia lophantha, Albizia saman, Albnaria troglodytes, Albonia peregrina, Albovia cretica, Albucea neapolitana, Albucea nutans, Albugo candida, Albugo crucifearum, Albugo leucotricha, Albugo mors-uvae, Albugo petroselini, Alburnus alburnus, Alburnus charusini, Alburnus striatus, Alburnus tarichi, Alburnus timarensis, Alcadia tamsiana appuni, Alcanna spinosa, Alcea aegyptiaca, Alcea ficifolia, Alcea pontica, Alcea rosea, Alcea setosa, Alchemilla acutidens, Alchemilla acutiloba subsp. catillaris, Alchemilla acutiloba subsp. mollis, Alchemilla acutiloba subsp.speciosa, Alchemilla acutiloba var. mollis, Alchemilla acutiloba, Alchemilla alechinii, Alchemilla alpina subsp. assurgens, Alchemilla alpina subsp. conjuncta, Alchemilla alpina subsp. glomerata, Alchemilla alpina var. burnatiana, Alchemilla alpina var. conjuncta, Alchemilla alpina var. debilicaulis, Alchemilla alpina var. glomerata, Alchemilla alpina var. godetii, Alchemilla alpina, Alchemilla aphanes, Alchemilla argentea, Alchemilla arvensis subsp. collina, Alchemilla arvensis subsp. microcarpa, Alchemilla arvensis var. lucronensis, Alchemilla arvensis var. microcarpa, Alchemilla arvensis, Alchemilla baltica, Alchemilla basilii, Alchemilla breviloba, Alchemilla conjuncta, Alchemilla crinita, Alchemilla cuneifolia, Alchemilla cymatophylla, Alchemilla delicatula, Alchemilla fennica, Alchemilla gibberulosa, Alchemilla glabricaulis, Alchemilla glareosa, Alchemilla glaucescens var. alpestris, Alchemilla glaucescens var. alpina, Alchemilla glaucescens, Alchemilla glomerata, Alchemilla gracilis, Alchemilla heptagona, Alchemilla hirsuticaulis, Alchemilla hoppeana subsp. conjuncta, Alchemilla hoppeana var. conjuncta, Alchemilla hungarica, Alchemilla hybrida subsp. glaucescens, Alchemilla hybrida subsp. hirsuticaulis, Alchemilla hybrida subsp. plicata, Alchemilla hybrida subsp. pubescens, Alchemilla hybrida var. glaucescens, Alchemilla hybrida, Alchemilla intermedia subsp. sooi, Alchemilla leiophylla, Alchemilla leptantha, Alchemilla major, Alchemilla micans, Alchemilla microcarpa, Alchemilla mollis, Alchemilla montana, Alchemilla monticola var. hungarica, Alchemilla monticola var. subpastoralis, Alchemilla monticola, Alchemilla multiflora, Alchemilla nebulosa, Alchemilla nigricans, Alchemilla occidentalis, Alchemilla opizii, Alchemilla orbiculata, Alchemilla palmata subsp. micans, Alchemilla palmata subsp. pastoralis, Alchemilla palmata subsp. Subcrenata, Alchemilla pascualis, Alchemilla pastoralis var. subpastoralis, Alchemilla pastoralis, Alchemilla pilosissima, Alchemilla plicata, Alchemilla pratensis var. micans, Alchemilla pratensis var. pastoralis, Alchemilla pratensis, Alchemilla propinqua, Alchemilla pubescens subsp. plicata, Alchemilla pubescens var. plicata, Alchemilla pubescens, Alchemilla rigida, Alchemilla sarmatica, Alchemilla semilunaris, Alchemilla sericata subsp. rigida, Alchemilla sericata subsp. tephroserica, Alchemilla sericata, Alchemilla speciosa, Alchemilla splendens hort., Alchemilla splendens var. bernensis, Alchemilla splendens var. brueggeriana, Alchemilla splendens var. typica, Alchemilla splendens, Alchemilla strigosula var. carelica, Alchemilla strigosula, Alchemilla subcrenata, Alchemilla subglobosa, Alchemilla submamillata, Alchemilla sylvestris var. micans, Alchemilla sylvestris var. pastoralis, Alchemilla sylvestris var. subcrenata, Alchemilla tatricola, Alchemilla tephroserica, Alchemilla triformiloba, Alchemilla triloba, Alchemilla tytthantha, Alchemilla viridicans, Alchemilla vulgaris subsp. acutiloba, Alchemilla vulgaris subsp. micans, Alchemilla vulgaris subsp. monticola, Alchemilla vulgaris subsp. palmata, Alchemilla vulgaris subsp. pastoralis, Alchemilla vulgaris subsp. plicata, Alchemilla vulgaris subsp. subcrenata, Alchemilla vulgaris var. glaucescens, Alchemilla vulgaris var. major, Alchemilla vulgaris var. micans, Alchemilla vulgaris var. pastoralis, Alchemilla vulgaris var. pilosissima, Alchemilla vulgaris var. subcrenata, Alchemilla vulgaris var. subsericea, Alchemilla vulgaris var. trichocalycina, Alchemilla vulgaris, Alchemilla wichurae, Alchemilla xanthochlora, Alchemilla zamelisiana, Alcicornium bifurcatum, Alcyonium schlosseri, Alectoris barbara, Alectoris chukar, Alectoris graeca, Alectoris rufa, Alectoroctonum caracasanum, Alectoroctonum cotinifolium, Alectoroctonum cotinoides, Alectoroctonum riedelianum, Alectoroctonum scotanum, Alectoroctonum willdenowii, Alectoroctonum yavalquahuitl, Alectorolophus borealis, Alectorolophus crista-galli, Alectorolophus drummond-hayi, Alectorolophus facchinii, Alectorolophus kerneri, Alectorolophus major subsp. montanus, Alectorolophus major var. apterus, Alectorolophus minor, Alectorolophus modestus, Alectorolophus montanus, Alectorolophus monticola, Alectorolophus parviflorus, Alectorolophus patulus, Alectorolophus rusticulus, Alectorolophus semleri, Alectorolophus stenophyllus, Alectorolophus sudeticus, Alectryonella plicatula, Aleochara bipustulata, Aleochara clavicornis, Aleochara gaudiuscula, Aleochara puberula, Aleochara sparsa, Alepes djedaba, Alesandrium tamarense, Aletris fragrans, Aletris japonica, Aletris uvaria, Aleuria undata, Aleurocanthus spiniferus, Aleurochiton acerinus, Aleuroclava aucubae, Aleuroclava chittendeni, Aleuroclava hikosanensis, Aleuroclava jasmini, Aleurodicus destructor, Aleurodicus dispersus, Aleurodothrips fasciapennis, Aleurolobus marlatti, Aleurolobus olivinus, Aleuroplatus kewensis, Aleuroplatus perseaphagus, Aleuropteridis filicicola, Aleuropteryx juniperi, Aleurothrixus floccosus, Aleurotrachelus atratus, Aleurotrachelus trachoides, Aleurotulus nephrolepidis, Alexandrium acatenella, Alexandrium affine, Alexandrium angustitabulatum, Alexandrium concavum, Alexandrium excavatum, Alexandrium fukuyoi, Alexandrium insuetum, Alexandrium kutnerae, Alexandrium leei, Alexandrium minutum, Alexandrium monilatum, Alexandrium ostenfeldii, Alexandrium pseudogoniaulax, Alexandrium pseudogonyaulax, Alexandrium taylori, Aleyrodes proletella, Aleyrodes vaporariorum, Algarobia glandulosa, Algarobia juliflora, Alhagi camelorum var. spinis-elongatis, Alhagi camelorum, Alhagi maurorum subsp. maurorum, Alhagi maurorum, Alhagi pseudalhagi subsp. persarum, Alhagi pseudalhagi, Aliculastrum cylindricum, Alinda biplicata, Alisma batrachiocarpum, Alisma dubium, Alisma lanceolatum, Alisma parnassifolium, Alisma ranunculoides, Alisma stenophyllum, Alisma subulatum, Alitubus millefolium, Alitubus pyrenaicus, Alitubus tomentosus, Alkanna alba, Alkanna lycopsoides, Alkekengi officinarum var. franchetii, Alkekengi officinarum, Alkekengi procumbens, Alkekengi pubescens, Allaganthera forsskaolei, Allajulus latestriatus, Allajulus nitidus, Allajulus truncorum, Allamanda aubletii, Allamanda cathartica var. grandiflora, Allamanda cathartica, Allamanda hendersonii, Allamanda latifolia, Allamanda linnaei, Allamanda salicifolia, Allamanda wardleyana, Allamanda williamsii, Allanassa concentrica, Allanassa concinna, Allantodia deflexa, Alleocarpa similis, Allescheria laricis, Alligator sclerops, Allionia nyctaginea, Allium acutangulum, Allium adscendens, Allium aegaeum, Allium aestivum, Allium africanum, Allium afrum, Allium albescens, Allium albopilosum, Allium album var. purpurascens, Allium album, Allium altissimum, Allium amblyopetalum, Allium amoenum, Allium ampeloprasum subsp. atroviolaceum, Allium ampeloprasum subsp. paterfamilias, Allium ampeloprasum var. ampeloprasum, Allium ampeloprasum var. atroviolaceum, Allium ampeloprasum var. margaritaceum, Allium ampeloprasum var. paterfamilias, Allium ampeloprasum var. porrum, Allium ampeloprasum, Allium angolense, Allium anguinum, Allium angulare, Allium angulatum, Allium angulosum, Allium aobanum, Allium approximatum, Allium arenarium, Allium ascalonicum var. condensum, Allium ascalonicum var. fertile, Allium ascalonicum var. sterile, Allium ascendens, Allium asperum, Allium assimile, Allium atropurpureum, Allium atroviolaceum var. caucasicum, Allium atroviolaceum var. firmotunicatum, Allium atroviolaceum var. ruderale, Allium atroviolaceum, Allium aureum, Allium australe, Allium babingtonii, Allium bauerianum, Allium baumannianum, Allium bertolonii, Allium bivalve, Allium bodeanum, Allium borbasii, Allium borbonicum, Allium boryanum, Allium bosniacum, Allium bouddae, Allium brachystemon, Allium byzantinum, Allium calcareum, Allium cambiasii, Allium candidissimum, Allium candidum, Allium carinatum, Allium cepa var. aggregatum, Allium cepa var. anglicum, Allium cepa var. argenteum, Allium cepa var. ascalonicum, Allium cepa var. bifolium, Allium cepa var. bulbiferum, Allium cepa var. cepa, Allium cepa var. crinides, Allium cepa var. flandricum, Allium cepa var. globosum, Allium cepa var. hispanicum, Allium cepa var. jamesii, Allium cepa var. lisboanum, Allium cepa var. luteum, Allium cepa var. multiplicans, Allium cepa var. portanum, Allium cepa var. praecox, Allium cepa var. proliferum, Allium cepa var. rosum, Allium cepa var. sanguineum, Allium cepa var. solaninum, Allium cepa var. tripolitanum, Allium cepa var. viviparum, Allium cepa, Allium cepaeum, Allium chamaemoly, Allium chionanthum, Allium ciliare, Allium ciliatum, Allium cilicicum, Allium clusianum, Allium collinum, Allium commune, Allium compactum, Allium complanatum, Allium confertum, Allium consimile, Allium contortum, Allium controversum, Allium convallarifolium, Allium cowanii, Allium crinitum, Allium cristophii, Allium cumaria, Allium cyrillii, Allium danubiale, Allium densiflorum, Allium denticulatum, Allium descendens, Allium deseglisei, Allium durieuanum, Allium eminens, Allium erectum, Allium esculentum, Allium fallax, Allium fallens, Allium firmotunicatum, Allium fistulosum, Allium flavum Salisb., Allium flavum, Allium flexifolium, Allium flexum, Allium foetidum, Allium fragrans, Allium fuscum, Allium gasparrinii, Allium geminatum, Allium gherardii, Allium gouanii, Allium gracile, Allium gracilescens, Allium grandisceptrum, Allium hollandicum, Allium holmense, Allium humbertii, Allium hyemale, Allium illyricum, Allium incarnatum, Allium inodorum, Allium intermedium, Allium jajlae, Allium karsianum, Allium kashgaricum, Allium kurrat, Allium lacteum, Allium laetum, Allium latifolium, Allium laxiflorum, Allium laxum, Allium leptophyllum, Allium liliflorum, Allium littoreum, Allium loiseleurii, Allium longibulbum, Allium longicuspis, Allium longipetiolatum, Allium loscosii, Allium lusitanicum, Allium macrocephalum, Allium magicum, Allium majale, Allium margaritaceum var. bulbiferum, Allium medium, Allium microdictyum, Allium moly, Allium monserratense, Allium montenegrinum, Allium multibulbosum, Allium napus, Allium neapolitanum, Allium neglectum, Allium nemorale, Allium neopolitanum, Allium nigritanum, Allium nigrum var. atropurpureum, Allium nigrum, Allium nitens, Allium nitschmannii, Allium niveum, Allium obscurum, Allium odoratissimum, Allium odorum, Allium oleraceum, Allium ophioscorodon, Allium opizii, Allium ornithogaloides, Allium oxypetalum, Allium pandatarium, Allium paniculatum subsp. fuscum, Allium paniculatum var. fuscum, Allium paniculatum, Allium parvifolium, Allium paterfamilias, Allium paucibulbosum, Allium pauciflorum, Allium pekinense, Allium pendulinum, Allium petiolatum, Allium plantaginense, Allium plantagineum, Allium porphyroprasum, Allium porraceum, Allium porrum, Allium praescissum, Allium pratense, Allium preslianum, Allium pugetii, Allium pulchrum, Allium purshii, Allium pygmaeum, Allium pylium, Allium regnieri, Allium rilaense, Allium rodundum, Allium roseum, Allium rotundum subsp. erectum, Allium rotundum subsp. jajlae, Allium rotundum subsp. preslianum, Allium rotundum subsp. waldsteinii, Allium rotundum var. cambiasii, Allium rotundum var. erectum, Allium rotundum var. melleum, Allium rotundum var. porphyroprasum, Allium rotundum var. preslianum, Allium rotundum var. rubicundum, Allium rotundum var. scariosum, Allium rotundum var. waldsteinianum, Allium rotundum, Allium rubicundum, Allium ruthenicum, Allium salota, Allium sativum subsp. asiae-mediae, Allium sativum subsp. controversum, Allium sativum subsp. ophioscorodon, Allium sativum subsp. sativum, Allium sativum subsp. subrotundum, Allium sativum var. controversum, Allium sativum var. ophioscorodon, Allium sativum var. pekinense, Allium sativum var. sativum, Allium sativum var. subrotundum, Allium sativum, Allium saxatile, Allium scariosum, Allium schmidtianum, Allium scopulicola, Allium scorodoprasum subsp. jajlae, Allium scorodoprasum subsp. rotundum, Allium scorodoprasum subsp. viviparum, Allium scorodoprasum subsp. waldsteinii, Allium scorodoprasum var. multibulbillatum, Allium scorodoprasum var. multibulbillosum, Allium scorodoprasum var. obscurum, Allium scorodoprasum var. viviparum, Allium scorodoprasum, Allium sellowianum, Allium senescens subsp. montanum, Allium senescens, Allium siculum, Allium sieberianum, Allium spectabile, Allium sphaerocephalon, Allium stipitatum, Allium striatellum, Allium striatum, Allium subalbidum, Allium subbiflorum, Allium subhirsutum subsp. ciliare, Allium subhirsutum subsp. ciliatum, Allium subhirsutum subsp. subhirsutum, Allium subhirsutum subsp. subvillosum, Allium subhirsutum var. canariense, Allium subhirsutum var. ciliatum, Allium subhirsutum var. corbariense, Allium subhirsutum var. hellenicum, Allium subhirsutum var. purpurascens, Allium subhirsutum var. subvillosum, Allium subhirsutum var. vernale, Allium subhirsutum, Allium subvillosum var. clusianum, Allium subvillosum, Allium subvineale, Allium sulcatum, Allium supranisianum, Allium syriacum, Allium tenorei, Allium thessalum, Allium tinei, Allium tmoleum, Allium triquetrum subsp. pendulinum, Allium triquetrum var. bulbiferum, Allium triquetrum var. pendulinum, Allium triquetrum, Allium tuberosum, Allium ucrainicum, Allium unifolium var. lacteum, Allium unifolium, Allium ursinoides, Allium ursinum subsp. ucrainicum, Allium ursinum var. ucrainicum, Allium ursinum, Allium valdense, Allium valdensium, Allium vernale, Allium veronense, Allium victorialis subsp. platyphyllum, Allium victorialis, Allium vincetoxicum, Allium vineale subsp. affine, Allium vineale subsp. asperiflorum, Allium vineale subsp. capsuliferum, Allium vineale subsp. compactum, Allium vineale subsp. kochii, Allium vineale subsp. vineale, Allium vineale var. affine, Allium vineale var. asperiflorum, Allium vineale var. bulbiferum, Allium vineale var. capsuliferum, Allium vineale var. compactum, Allium vineale var. descendens, Allium vineale var. kochii, Allium vineale var. multiflorum, Allium vineale var. nitens, Allium vineale var. purshii, Allium vineale, Allium violaceum, Allium virens, Allium virescens, Allium wakegi, Allium waldsteinianum, Allium waldsteinii, Allium walteri, Allium webbii, Allium x proliferum, Allium zebdanense, Allocasuarina verticillata, Allognathus balearicus, Allognathus hispanicus, Alloiozonium arctotideum, Allolepidapedon fistulariae, Allolobophora parva, Allolobophora rosea, Allolobophora smaragdina, Allolobophoridella eiseni, Allonyx quadrimaculatus, Allopauropus pseudomillotianus, Allopeas clavulinum, Allopeas gracile, Allorhinocoris prasinus, Allosperma tuberosa, Alnaster sinuatus, Alnaster viridis, Alnus alisoviana, Alnus alnobetula subsp. sinuata, Alnus alnobetula, Alnus alnus, Alnus americana, Alnus argentata, Alnus borealis, Alnus canadensis, Alnus cordata, Alnus cordifolia, Alnus crispa subsp. laciniata, Alnus crispa subsp. sinuata, Alnus glauca, Alnus glutinosa x incana, Alnus glutinosa, Alnus harinoki, Alnus incana subsp. rugosa, Alnus incana var. americana, Alnus incana, Alnus intermedia, Alnus japonica, Alnus macrocarpa, Alnus maritima subsp. metoporina, Alnus maritima var. metoporina, Alnus maritima, Alnus metoporina, Alnus minor, Alnus nana, Alnus neapolitana, Alnus nervosus, Alnus obcordata, Alnus oregana, Alnus oregona var. pinnatisecta, Alnus oregona, Alnus plicata, Alnus reginosa, Alnus rubra, Alnus rugosa var. americana, Alnus rugosa, Alnus sinuata, Alnus tirolensis, Alnus viridis subsp. sinuata, Alnus viridis var. sinuata, Alnus viridis, Alnus x ambigua, Alnus x badensis, Alnus x balatonialis, Alnus x beckii, Alnus x hybrida, Alnus x montana, Alnus x pubescens, Alnus x spuria, Alocasia dussii, Alocasia illustris, Alocasia ternata, Alocentron curvirostre, Aloe arborea, Aloe arborescens, Aloe ausana, Aloe barbadensis, Aloe brevifolia, Aloe chinensis, Aloe ciliaris var. ciliaris, Aloe ciliaris var. flanaganii, Aloe ciliaris, Aloe elongata, Aloe ferox, Aloe flava, Aloe foetida, Aloe fragrantissima, Aloe frutescens, Aloe fruticosa, Aloe fulgens, Aloe indica, Aloë latifolia, Aloe longifolia, Aloe maculata, Aloe natalensis, Aloe perfoliata var. vera, Aloe perfoliata vera, Aloe perfoliatum, Aloe plicatilis, Aloe principis, Aloe punctata, Aloe rubescens, Aloe salm-dyckiana, Aloe saponaria, Aloe sigmoidea, Aloe succotrina, Aloe uvaria, Aloe variegata, Aloe vera, Aloe vivipara, Aloe vulgaris, Aloephagus myersi, Aloitis aurea, Alomia spilanthoides, Alonella hamulata, Alonsoa compacta, Alonsoa grandiflora, Alonsoa incisa, Alonsoa incisifolia var. angustifolia, Alonsoa incisifolia var. incisifolia, Alonsoa incisifolia var. latifolia, Alonsoa incisifolia, Alonsoa incissaefolia var. latifolia, Alonsoa meridionalis var. carnea, Alonsoa meridionalis var. cinnabarina, Alonsoa meridionalis var. crocea, Alonsoa meridionalis var. flava, Alonsoa meridionalis var. meridionalis, Alonsoa meridionalis var. micans, Alonsoa meridionalis var. rubra, Alonsoa meridionalis, Alonsoa mutisii, Alonsoa myrtifolia, Alonsoa parviflora, Alonsoa peruviana, Alonsoa procumbens, Alonsoa urticifolia, Alonsoa warscewiczii, Alopecurus aequalis f. fluitans, Alopecurus aequalis f. foliosus, Alopecurus aequalis f. notacens, Alopecurus aequalis f. violaceus, Alopecurus aequalis subsp. aequalis, Alopecurus aequalis subsp. amurensis, Alopecurus aequalis subsp. aristulatus, Alopecurus aequalis subsp. natans, Alopecurus aequalis var. amurensis, Alopecurus aequalis var. aristulatus, Alopecurus aequalis var. fluitans, Alopecurus aequalis var. natans, Alopecurus aequalis var. violaceus, Alopecurus aequalis, Alopecurus agrestis, Alopecurus alpinus f. songaricus, Alopecurus alpinus var. songaricus, Alopecurus altissimus, Alopecurus amurensis, Alopecurus aquaticus, Alopecurus aristatus var. monspeliensis, Alopecurus aristulatus var. merriami, Alopecurus aristulatus var. natans, Alopecurus aristulatus, Alopecurus aristulosus, Alopecurus australis, Alopecurus baptarrhenius, Alopecurus brachyglossus, Alopecurus brachystachyus, Alopecurus brachytrichus, Alopecurus bulbosus, Alopecurus caespitosus, Alopecurus ciliatus, Alopecurus cornucopiae, Alopecurus cucullatus, Alopecurus diandrus, Alopecurus elongatus, Alopecurus fasciculatus, Alopecurus fulvus f. violacea, Alopecurus fulvus var. amurensis, Alopecurus fulvus, Alopecurus geniculatus f. robustior, Alopecurus geniculatus subsp. fulvus, Alopecurus geniculatus var. aequalis, Alopecurus geniculatus var. amurensis, Alopecurus geniculatus var. aquaticus, Alopecurus geniculatus var. aristulatus, Alopecurus geniculatus var. armurensis, Alopecurus geniculatus var. fulvus, Alopecurus geniculatus var. microstachyus, Alopecurus geniculatus var. natans, Alopecurus geniculatus var. robustus, Alopecurus geniculatus, Alopecurus grandiflorus, Alopecurus howellii var. merriamii, Alopecurus howellii var. merrimani, Alopecurus laxiflorus, Alopecurus maritimus, Alopecurus monspeliensis, Alopecurus myosuroides, Alopecurus nothus, Alopecurus obscurus, Alopecurus pallescens, Alopecurus pallidus, Alopecurus paludosus, Alopecurus palustris subsp. fulvus, Alopecurus palustris subsp. geniculatus, Alopecurus paniceus, Alopecurus pratensis f. breviaristatus, Alopecurus pratensis subsp. pratensis, Alopecurus purpurascens, Alopecurus rendlei, Alopecurus scaber, Alopecurus seravschanicus, Alopecurus sericeus, Alopecurus songaricus, Alopecurus subaristatus, Alopecurus trivialis, Alopecurus typhoides, Alopecurus utriculatus, Alopecurus ventricosus, Alopex lagopus, Alopia livida bipalatalis, Alopia monacha, Alopia straminicollis monacha, Alopia straminicollis, Alopochen aegyptiaca, Alopochen aegyptiacus, Alosa alburnus, Aloysia citridora, Aloysia citriodora, Aloysia sleumeri, Aloysia triphylla, Alphestes gembra, Alphestes sambra, Alpheus edwardsii, Alpheus inopinatus, Alpheus migrans, Alpheus rapacida, Alphitobius diaperinus, Alphitobius laevigatus, Alphitomorpha brayana, Alphitomorpha clandestina, Alphitomorpha communis, Alphitomorpha fuliginea, Alphitomorpha heraclei, Alphitomorpha penicillata var. grossularia, Alphitomorpha pisi, Alphitomorpha tridactyla, Alphitomorpha trifoliorum, Alphitophagus bifasciatus, Alpinaria rhododendri, Alpinia cristata, Alpinia fimbriata, Alpinia fluvitialis, Alpinia nutans var. longiramosa, Alpinia nutans, Alpinia schumanniana, Alpinia speciosa, Alpinia zerumbet, Alsinanthe biflora, Alsinanthus balearicus, Alsinanthus biflorus, Alsinanthus montanus, Alsinanthus rotundifolius, Alsinastrum galiifolia, Alsine alsinastrum, Alsine arvensis, Alsine bocconei, Alsine caucasica, Alsine corniculata, Alsine glomerata, Alsine graminea, Alsine hispanica, Alsine hybrida, Alsine laxa, Alsine mantica, Alsine mediterranea, Alsine montana, Alsine pallida, Alsine polycarpa, Alsine procumbens, Alsine saginoides, Alsine salina, Alsine segetalis, Alsine subulata, Alsine tomentosa, Alsine umbellata, Alsine viscosa, Alsinella media, Alsinella procumbens, Alsinella saginoides, Alsinella viscosa, Alsophila cooperi, Alstroemeria araucana, Alstroemeria atrorubra, Alstroemeria aurantiaca, Alstroemeria aurea, Alstroemeria banksiana, Alstroemeria chiloensis, Alstroemeria concolor, Alstroemeria hassleriana, Alstroemeria mutabilis, Alstroemeria peruviana, Alstroemeria psittacina var. longipedunculata, Alstroemeria psittacina, Alstroemeria pulchella, Alstroemeria xanthina, Alternanthera achyrantha, Alternanthera achyranthes, Alternanthera achyranthoides, Alternanthera amoena, Alternanthera angustifolia, Alternanthera austrotrinidadis, Alternanthera brachiata, Alternanthera caracasana, Alternanthera ciliata, Alternanthera denticulata, Alternanthera diffusa, Alternanthera echinata, Alternanthera ficoidea, Alternanthera ficoides, Alternanthera glabra, Alternanthera leiantha, Alternanthera leucantha, Alternanthera lorentzii, Alternanthera major, Alternanthera nana, Alternanthera nodiflora, Alternanthera paronychioides, Alternanthera peploides, Alternanthera philoxerina, Alternanthera philoxeroides, Alternanthera polygonoides, Alternanthera prostrata, Alternanthera pungens, Alternanthera repens, Alternanthera sennii, Alternanthera sessilis, Alternanthera sibirica, Alternanthera tenella, Alternanthera tenuissima, Alternanthera thomensis, Alternanthera triandra, Alternanthera uliginosa, Alternanthera villiflora, Alternanthera virgata, Alternaria alternata f. sp. citri, Alternaria citri, Alternaria gaisen, Alternaria kikuchiana, Alternaria mali, Alternaria padwickii, Alternaria radicina, Alternaria saponariae, Alternaria triticina, Althaea aegyptica, Althaea arborea, Althaea armeniaca, Althaea balearica, Althaea broussonetiifolia, Althaea cannabina subsp. narbonensis, Althaea cannabina, Althaea caribaea, Althaea chinensis, Althaea coromandeliana, Althaea crispa, Althaea ficifolia, Althaea flexuosa, Althaea frutex, Althaea godronii, Althaea hirsuta subsp. longiflora, Althaea hirsuta, Althaea hispida, Althaea hyrcana, Althaea kotschyi, Althaea kragujevacensis, Althaea longiflora, Althaea mauritiana, Althaea meonantha, Althaea mexicana, Althaea micrantha, Althaea microcarpa, Althaea multiflora, Althaea mutica, Althaea narbonensis, Althaea narbonnensis, Althaea nicaeensis, Althaea officinalis subsp. micrantha, Althaea officinalis subsp. pseudoarmeniaca, Althaea officinalis var. pseudoarmeniaca, Althaea officinalis, Althaea parviflora, Althaea plebeia, Althaea pontica, Althaea punctata, Althaea rosea, Althaea setosa, Althaea sinensis, Althaea sublobata, Althaea thuringiaca, Althaea trimestris, Althaea verticillata, Althaea vulgaris, Althaea x taurinensis, Altica ampelophaga, Altica carinthiaca, Alvania dorbignyi, Alveinus miliaceus, Alysium holtingii, Alysium perrini, Alyssanthus sinuatus, Alyssoides sinuata, Alyssum alyssoides, Alyssum amoris, Alyssum argenteum, Alyssum arvaticum, Alyssum atlanticum, Alyssum brasii, Alyssum calycinum, Alyssum caucasicum, Alyssum chalcidicum, Alyssum cheirifolium, Alyssum chlorocarpum, Alyssum ciliatum, Alyssum clypeatum, Alyssum collinum, Alyssum conglobatum, Alyssum cornutum, Alyssum corsicum, Alyssum cuneipetalum, Alyssum cupreum, Alyssum dasycarpum, Alyssum decandolleanum, Alyssum decipiens, Alyssum deltoideum, Alyssum dentatum, Alyssum desertorum var. desertorum, Alyssum desertorum, Alyssum diffusum, Alyssum diversicaule, Alyssum draba, Alyssum edentulum, Alyssum epiroticum, Alyssum erraticum, Alyssum gemonense, Alyssum grintescui, Alyssum heterophyllum, Alyssum hirsutum, Alyssum illyricum, Alyssum incanum, Alyssum inflatum, Alyssum jonthlaspi, Alyssum latifolium, Alyssum libycum, Alyssum linearifolium, Alyssum linifolium, Alyssum longistylum, Alyssum lunarioides, Alyssum lusitanicum, Alyssum maritimum, Alyssum meyerianum, Alyssum micranthum, Alyssum microcarpon, Alyssum micropetalum, Alyssum mimus micranthum, Alyssum mimus, Alyssum minus subsp. strigosum, Alyssum minus var. micranthum, Alyssum minus var. strigosum, Alyssum minus, Alyssum montanum subsp. atlanticum, Alyssum montanum, Alyssum murale, Alyssum mutabile, Alyssum myagrum, Alyssum obliquum, Alyssum odessanum, Alyssum orphanidis, Alyssum paniculatum, Alyssum parviflorum var. micranthum, Alyssum parviflorum, Alyssum petraeum, Alyssum punctatum, Alyssum rostratum, Alyssum rothmaleri, Alyssum sartorii, Alyssum sativum, Alyssum saxatile, Alyssum saxtile, Alyssum schirwanicum, Alyssum scutigerum, Alyssum sibiricum, Alyssum simplex, Alyssum sinuatum, Alyssum speciosum, Alyssum strigosum, Alyssum subalpinum, Alyssum tortuosum, Alyssum transiens, Alyssum turkestanicum, Alyssum vesicarioides, Alyssum wierzbickii, Alytes obstetricans, Amadina fasciata, Amalia cristata, Amalia gagates, Amalia hessei, Amalia kobelti, Amalia pratensis, Amalia tyrrena, Amandava amandava, Amandava formosa, Amandava subflava, Amanita inopinata, Amara aenea, Amara anthobia, Amara aulica, Amara cursitans, Amara majuscula, Amara montivaga, Amaracus majorana, Amarantellus argentinus, Amaranthoides decumbens, Amaranthoides globosa, Amaranthoides globosus, Amaranthus acutilobus, Amaranthus adscendens, Amaranthus albus var. pubescens, Amaranthus albus, Amaranthus alius, Amaranthus altissimus, Amaranthus ambigens, Amaranthus amboinicus, Amaranthus anacardana, Amaranthus anardana, Amaranthus angustifolius subsp. silvestris, Amaranthus angustifolius var. silvestris, Amaranthus angustifolius, Amaranthus arardhanus, Amaranthus ascendens subsp. polygonoides, Amaranthus ascendens var. polygonoides, Amaranthus ascendens, Amaranthus aschersonianus, Amaranthus atrosanguineus, Amaranthus aureus, Amaranthus batalleri, Amaranthus bellardii, Amaranthus berchtholdii, Amaranthus berchtoldii, Amaranthus berlandieri, Amaranthus bernhardii, Amaranthus bicolor, Amaranthus blitoides, Amaranthus blitonius, Amaranthus blitum subsp. blitum, Amaranthus blitum subsp. emarginatus, Amaranthus blitum var. emarginatus, Amaranthus blitum, Amaranthus bouchonii, Amaranthus bracteosus, Amaranthus bulgaricus, Amaranthus bullatus, Amaranthus capensis subsp. capensis, Amaranthus capensis subsp. uncinatus, Amaranthus capensis, Amaranthus carneus, Amaranthus catechu, Amaranthus caudatus subsp. caudatus, Amaranthus caudatus subsp. saueri, Amaranthus chlorostachys var. powellii, Amaranthus chlorostachys var. pseudoretroflexus, Amaranthus chlorostachys, Amaranthus clementii, Amaranthus crispus, Amaranthus cristatus, Amaranthus cristulatus, Amaranthus cruentus, Amaranthus curvifolius, Amaranthus cuspidatus, Amaranthus deflexus, Amaranthus delilei, Amaranthus diffusus, Amaranthus dinteri var. uncinatus, Amaranthus edulis, Amaranthus emarginatus, Amaranthus esculentus, Amaranthus eugenii, Amaranthus farinaceus, Amaranthus flavescens, Amaranthus flavus, Amaranthus flexuosus, Amaranthus frumentaceus, Amaranthus gangeticus, Amaranthus gracilentus, Amaranthus gracilis, Amaranthus graecizans subsp. graecizans, Amaranthus graecizans subsp. silvestris, Amaranthus graecizans subsp. thellungianus, Amaranthus graecizans var. pubescens, Amaranthus graecizans var. silvestris, Amaranthus graecizans, Amaranthus guadeloupensis, Amaranthus guadelupensis, Amaranthus hecticus, Amaranthus hierichuntinus, Amaranthus huttonii, Amaranthus hybridus bouchonii, Amaranthus hybridus subsp. bouchonii, Amaranthus hybridus subsp. cruentus, Amaranthus hybridus subsp. hybridus, Amaranthus hybridus subsp. hypochondriacus, Amaranthus hybridus subsp. patulus, Amaranthus hybridus subsp. quitensis, Amaranthus hybridus var. aciculatus, Amaranthus hybridus var. cruentus, Amaranthus hybridus var. pseudoretroflexus, Amaranthus hybridus var. quitensis, Amaranthus hybridus x retroflexus, Amaranthus hybridus, Amaranthus hypochondriacus, Amaranthus inamoenus, Amaranthus incarnatus, Amaranthus incomptus, Amaranthus incurvatus, Amaranthus intermedius, Amaranthus japonicus, Amaranthus johnstonii, Amaranthus laetus, Amaranthus lanceolatus, Amaranthus lancifolius, Amaranthus laxiflorus, Amaranthus leucocarpus, Amaranthus littoralis, Amaranthus lividus subsp. ascendens, Amaranthus lividus subsp. lividus, Amaranthus lividus subsp. polygonioides, Amaranthus lividus subsp. polygonoides, Amaranthus lividus var. polygonoides, Amaranthus lividus, Amaranthus macrostachyus, Amaranthus melancholicus, Amaranthus minor, Amaranthus mitchellii var. strictifolius, Amaranthus mitchellii, Amaranthus monstrosus, Amaranthus montevidensis, Amaranthus mucronatus, Amaranthus muricatus, Amaranthus neglectus, Amaranthus nepalensis, Amaranthus oleraceus, Amaranthus pallidus, Amaranthus palmeri var. glomeratus, Amaranthus palmeri, Amaranthus paniculatus, Amaranthus parodii, Amaranthus patulus, Amaranthus perennis, Amaranthus polygamus, Amaranthus polygonoides subsp. berlandieri, Amaranthus polygonoides, Amaranthus powelli subsp. bouchonii, Amaranthus powellii subsp. bouchonii, Amaranthus powellii, Amaranthus prostratus, Amaranthus pseudoretroflexus, Amaranthus pubescens, Amaranthus purgans, Amaranthus purpureus, Amaranthus pyramidalis, Amaranthus quitensis var. stuckertianus, Amaranthus quitensis, Amaranthus recurvatus, Amaranthus retroflexus subsp. quitensis, Amaranthus retroflexus var. powellii, Amaranthus retroflexus var. pseudoretroflexus, Amaranthus retroflexus var. salicifolius, Amaranthus retroflexus, Amaranthus reverchonii, Amaranthus rigidus, Amaranthus rotundifolius, Amaranthus rubescens, Amaranthus ruderalis, Amaranthus rudis, Amaranthus salicifolius, Amaranthus sanguineus, Amaranthus sanguinolentus, Amaranthus silvestris, Amaranthus speciosus, Amaranthus spicatus, Amaranthus spinosus, Amaranthus standleyanus, Amaranthus strictus, Amaranthus taishanensis, Amaranthus tamariscinus, Amaranthus tenuiflorus, Amaranthus tenuifolius, Amaranthus thellungianus, Amaranthus thunbergii, Amaranthus timeroyi, Amaranthus tricolor, Amaranthus tristis, Amaranthus trivialis, Amaranthus tuberculatus var. prostratus, Amaranthus tuberculatus var. subnudus, Amaranthus tuberculatus, Amaranthus verticillatus, Amaranthus viridis, Amaranthus viridus, Amaranthus viscidulus, Amaranthus x alleizettei, Amaranthus x dobrogensis, Amaranthus x galii, Amaranthus x ozanonii, Amaranthus x polgarianus, Amaranthus x ralletii, Amaranthus x soproniensis, Amaranthus x thevenoei, Amaranthus x turicensis, Amaranthus x zobelii, Amarenus badius, Amarenus flavus, Amarenus spadiceus, Amaryllis belladonna, Amaryllis blanda, Amaryllis bulbisperma, Amaryllis capensis, Amaryllis corusca, Amaryllis curvifolia, Amaryllis dubia, Amaryllis fothergilii, Amaryllis fothergillia, Amaryllis jacquinii, Amaryllis longipetala, Amaryllis lutea, Amaryllis moorei, Amaryllis obliqua, Amaryllis pallida, Amaryllis pudica, Amaryllis pulchra, Amaryllis regalis, Amaryllis riparia, Amaryllis rosea, Amaryllis sarniensis, Amaryllis venusta, Amathia gracillima, Amathia verticillata, Amathina tricarinata, Amaurobius similis, Amaurorhinus monizianus, Amazona aestiva, Amazona amazonica, Amazona farinosa, Amazona festiva, Amazona leucocephala, Amazona ochrocephala, Amazona oratrix, Amberboa moschata, Ambigolimax valentianus, Ambiphrya ameiuri, Amblodon niger, Amblogyna polygonoides, Ambloplites rupestris, Amblychloa dura, Amblygonum orientale, Amblyomma exornatum, Amblyomma flavomaculatum, Amblyomma latum, Amblyomma nuttalli, Amblyomma quadricavum, Amblyomma transversale, Amblyomma varanense, Amblyopappus mendocinus, Amblypsilopus exul, Amblyrhynchotes spinosissimus, Amblyseius californicus, Amblyseius cucumeris, Amblyseius degenerans, Ambrina ambrosioides, Ambrina botrys, Ambrina pumilio, Ambrosia aptera, Ambrosia artemisiifolia var. artemisiifolia, Ambrosia artemisiifolia var. elatior, Ambrosia artemisiifolia var. paniculata, Ambrosia artemisiifolia, Ambrosia californica, Ambrosia chilensis, Ambrosia confertiflora, Ambrosia coronopifolia, Ambrosia cumanensis, Ambrosia elata, Ambrosia elatior, Ambrosia glandulosa, Ambrosia hispida, Ambrosia integrifolia, Ambrosia lindheimeriana, Ambrosia maritima, Ambrosia monophylla, Ambrosia paniculata, Ambrosia psilostachya var. californica, Ambrosia psilostachya var. coronopifolia, Ambrosia psilostachya var. lindheimeriana, Ambrosia psilostachya, Ambrosia rugelii, Ambrosia tenuifolia, Ambrosia trifida var. aptera, Ambrosia trifida var. integrifolia, Ambrosia trifida var. texana, Ambrosia trifida var. trifida, Ambrosia trifida, Ambrosiodmus rubricollis, Ambystoma mexicanum, Ameira divagans divagans, Ameira simplex, Ameiurus catus, Ameiurus melas, Ameiurus natalis, Ameiurus nebulosus, Amelanchier alnifolia var. alnifolia, Amelanchier alnifolia var. typica, Amelanchier alnifolia, Amelanchier amelanchier var. acutifolia, Amelanchier amelanchier var. genuina, Amelanchier amelanchier, Amelanchier arborea subsp. laevis, Amelanchier arborea var. cordifolia, Amelanchier arborea var. laevis, Amelanchier austromontana, Amelanchier botryapium, Amelanchier canadensis subsp. confusa, Amelanchier canadensis var. alnifolia, Amelanchier canadensis var. canadensis, Amelanchier canadensis var. intermedia, Amelanchier canadensis var. oblongifolia, Amelanchier canadensis var. subintegra, Amelanchier canadensis, Amelanchier carrii, Amelanchier confusa, Amelanchier cusickii, Amelanchier florida, Amelanchier grandiflora, Amelanchier hybrida, Amelanchier laevis var. cordifolia, Amelanchier laevis var. laevis, Amelanchier laevis var. nitida, Amelanchier laevis, Amelanchier lamarckii, Amelanchier leptodendron, Amelanchier longifolia, Amelanchier lucida, Amelanchier macrocarpa, Amelanchier montana, Amelanchier neumanniana, Amelanchier oblongifera, Amelanchier oblongifolia, Amelanchier ovalis, Amelanchier parvifolia, Amelanchier pumila, Amelanchier racemosa, Amelanchier rotundifolia, Amelanchier sanguinea var. alnifolia, Amelanchier sera, Amelanchier spicata, Amelanchier stolonifera, Amelanchier vulgaris var. genuina, Amelanchier vulgaris, Amelanchier x grandiflora, Amelanchus ovalis, Ameletia acutidens, Ameletia elongata, Ameletia floribunda, Ameletia indica, Ameletia uliginosa, Amelichloa brachychaeta, Amellus carolinianus, Amellus divaricatus, Amellus novae-belgii, Amellus officinalis, Amellus pedunculatus, Amellus speciosus, Amellus vulgaris, American plum line pattern virus, Americus gigantea, Amerina glandulosa, Ametastegia pallipes, Amethystea caerulea, Amethystea corymbosa, Amethystea trifida, Ametropus fragilis, Amia elizabethae, Amidena undulata, Amischa analis, Amitus fuscipennis, Amitus spiniferus, Ammania baccifera, Ammania senegalensis, Ammania verticillata, Ammannia acutidens, Ammannia aegyptiaca, Ammannia alcalina, Ammannia apiculata, Ammannia arenaria, Ammannia attenuata var. latifolia, Ammannia attenuata var. micromerioides, Ammannia attenuata, Ammannia auriculata var. arenaria, Ammannia auriculata var. auriculata, Ammannia auriculata var. elata, Ammannia auriculata var. subsessilis, Ammannia auriculata, Ammannia baccifera subsp. baccifera, Ammannia baccifera subsp. contracta, Ammannia baccifera subsp. viridis, Ammannia baccifera, Ammannia boraei, Ammannia caspia, Ammannia caspica, Ammannia catholica var. philippensis, Ammannia coccinea subsp. longifolia, Ammannia coccinea subsp. purpurea, Ammannia coccinea subsp. robusta, Ammannia coccinea, Ammannia crassissima, Ammannia debilis, Ammannia densiflora, Ammannia dentifera, Ammannia diffusa, Ammannia discolor, Ammannia elongata, Ammannia filiformis, Ammannia floribunda, Ammannia glauca, Ammannia humilis, Ammannia hyrcanica, Ammannia indica, Ammannia latifolia var. octandra, Ammannia linearifolia, Ammannia longifolia, Ammannia longipes, Ammannia monoflora, Ammannia multicaulis, Ammannia nana, Ammannia occidentalis var. pygmaea, Ammannia occidentalis, Ammannia pedunculata, Ammannia peploides, Ammannia polystachya, Ammannia prostrata, Ammannia purpurea, Ammannia pusilla, Ammannia racemosa, Ammannia ramosa, Ammannia ramosior, Ammannia repens, Ammannia retusa, Ammannia robusta, Ammannia rotundifolia, Ammannia sagittata var. angustifolia, Ammannia salicifolia, Ammannia salsuginosa, Ammannia sanguinolenta subsp. longifolia, Ammannia sanguinolenta subsp. purpurea, Ammannia sanguinolenta subsp. robusta, Ammannia sanguinolenta, Ammannia senegalensis var. auriculata, Ammannia senegalensis var. brasiliensis, Ammannia senegalensis var. filiformis, Ammannia senegalensis var. riparia, Ammannia senegalensis, Ammannia stylosa, Ammannia teres, Ammannia texana, Ammannia undulata, Ammannia verticillata, Ammannia vescicatoria, Ammannia viridis, Ammannia wrightii, Ammi boeberi, Ammi broussonetii, Ammi cicutifolium, Ammi copticum, Ammi daucifolium, Ammi daucoides, Ammi dilatatum, Ammi elatum, Ammi glaucifolium, Ammi intermedium, Ammi majus, Ammi pauciradiatum, Ammi pumilum, Ammi topalii, Ammi visnaga, Ammiopsis aristidis, Ammiopsis daucoides, Ammios muricata, Ammocallis rosea, Ammoperdix heyi, Ammophila arenaria var. breviligulata, Ammophila breviligulata, Ammothea hilgendorfi, Ammotragus lervia, Amomum filiforme, Amomum nutans, Amonia agrimonioides, Amoria angulata, Amoria fragifera, Amoria glomerata, Amoria hybrida, Amoria montana, Amoria nigrescens, Amoria repens, Amoria resupinata, Amoria retusa, Amoria spumosa, Amoria suffocata, Amoria tomentosa, Amoria vesiculosa, Amorpha angustifolia, Amorpha bushii, Amorpha croceolanata, Amorpha curtissii, Amorpha dewinkeleri, Amorpha fruticosa var. angustifolia, Amorpha fruticosa var. croceolanata, Amorpha fruticosa var. emarginata, Amorpha fruticosa var. oblongifolia, Amorpha fruticosa var. occidentalis, Amorpha fruticosa var. tennesseensis, Amorpha fruticosa, Amorpha occidentalis var. arizonica, Amorpha occidentalis var. emarginata, Amorpha occidentalis, Amorpha tennesseensis, Amorpha virgata, Ampacus daniellii, Ampedus lepidus, Ampelisca cavicoxa, Ampelisca heterodactyla, Ampelisca rubra, Ampelocissus cirrhata, Ampelocissus major, Ampelodesmos bicolor, Ampelodesmos effusus, Ampelodesmos mauritanica, Ampelodesmos mauritanicus, Ampelodesmos tenax, Ampelodonax bicolor, Ampelopsis haponica, Ampelopsis hederacea var. murorum, Ampelopsis latifolia, Ampelopsis minima, Ampelopsis quinquefolia, Ampelopsis tricuspidata, Amphacanthus javus, Amphacanthus notostictus, Amphacanthus virgatus, Amphiachyris dracunculoides, Amphiareus constrictus, Amphiareus fulvescens, Amphiareus obscuriceps, Amphiascus rostratus, Amphiascus tenuiremis, Amphiascus vararensis, Amphibalanus amphitrite, Amphibalanus eburneus, Amphibalanus improvisus, Amphibalanus reticulatus, Amphibalanus variegatus, Amphibolis coelestis, Amphibromus neesii, Amphibromus recurvatus, Amphicerus cornutus, Amphicorina pectinata, Amphilophis argentea, Amphilophis barbinodis, Amphilophis decipiens, Amphilophis emersa, Amphilophis glabra, Amphilophis haenkei, Amphilophis insculpta, Amphilophis intermedia, Amphilophis ischaemum, Amphilophis leucopogon, Amphilophis odorata, Amphilophis palmeri, Amphilophis perforata, Amphilophis saccharoides, Amphilophis schlumbergeri, Amphilophium buccinatorium, Amphimedon chloros, Amphinome jamaicensis, Amphinome macrotricha, Amphioctopus aegina, Amphiodia (Amphispina) clarki, Amphiodia (Amphispina) obtecta, Amphiodia clarki, Amphiodia obtecta, Amphioplus (Lymanella) laevis, Amphioplus (Lymanella) megapomus, Amphioplus bocki, Amphioplus laevis, Amphioplus megapomus, Amphioplus miyadii, Amphisorus hemprichi, Amphisorus hemprichii, Amphistegina lobifera, Amphitomeus attemsi, Amphiura (Amphioplus) praestans, Amphiura laevis, Amphiura praestans, Amphogona pusilla, Amphorellopsis acuta, Amphorophora tuberculata, Ampithoe bizseli, Ampithoe valida, Amplelygonum perfoliatum, Ampullaria chiquitensis, Ampullaria knorrii, Ampullaria rotula, Amsinckia abbreviata, Amsinckia abramsii, Amsinckia acuticarpa, Amsinckia albicarpa, Amsinckia ammophila, Amsinckia amplexicaulis, Amsinckia andersonii, Amsinckia angulata, Amsinckia angustata, Amsinckia angustifolia, Amsinckia angustisepala, Amsinckia appressa, Amsinckia arenaria, Amsinckia arizonica, Amsinckia arvensis, Amsinckia attenuata, Amsinckia aurantiaca, Amsinckia aurea, Amsinckia australis, Amsinckia bakeri, Amsinckia barbata, Amsinckia basistaminea, Amsinckia borealis, Amsinckia brachycalyx, Amsinckia brachysantha, Amsinckia brandegeeae, Amsinckia brunnescens, Amsinckia bullata, Amsinckia caduca, Amsinckia californica, Amsinckia calycina, Amsinckia campestris, Amsinckia cana, Amsinckia canadensis, Amsinckia canescens, Amsinckia catalinensis, Amsinckia ciliata, Amsinckia collina, Amsinckia communis, Amsinckia condensata, Amsinckia congesta, Amsinckia congruens, Amsinckia conica, Amsinckia conspicua, Amsinckia copelandii, Amsinckia cristata, Amsinckia ctenocarpa, Amsinckia debilis, Amsinckia decumbens, Amsinckia delicata, Amsinckia deltoidea, Amsinckia demissa, Amsinckia densiflora, Amsinckia densifolia, Amsinckia densirugosa, Amsinckia dictyota, Amsinckia divergens, Amsinckia diversifolia, Amsinckia douglasiana, Amsinckia dudleyi, Amsinckia eastwoodiae, Amsinckia eatonii, Amsinckia echinata, Amsinckia elegans, Amsinckia elmeri, Amsinckia helleri, Amsinckia hirticaulis, Amsinckia hispida, Amsinckia hispidissima, Amsinckia humifusa, Amsinckia idahoensis, Amsinckia intactilis, Amsinckia interior, Amsinckia intermedia var. eastwoodiae, Amsinckia intermedia var. echinata, Amsinckia intermedia, Amsinckia johnstonii, Amsinckia jonesii, Amsinckia jucunda, Amsinckia lemmonii, Amsinckia lycopsoides, Amsinckia macrantha, Amsinckia macrosepala, Amsinckia marginata, Amsinckia menziesii var. intermedia, Amsinckia menziesii var. menziesii, Amsinckia menziesii, Amsinckia micrantha, Amsinckia microphylla, Amsinckia mojavensis, Amsinckia nana, Amsinckia obliqua, Amsinckia obvallata, Amsinckia ovaticarpa, Amsinckia parviflora, Amsinckia patagonica, Amsinckia platycarpa, Amsinckia pseudolycopsioides, Amsinckia pustulata, Amsinckia remotifructis, Amsinckia retrorsa, Amsinckia rigida, Amsinckia rostellata, Amsinckia rugosa, Amsinckia salebrosa, Amsinckia sparsiflora, Amsinckia splendens, Amsinckia stenophylla, Amsinckia subintegra, Amsinckia tessellata, Amsinckia turrita, Amsinckia valens, Amsinckia verna, Amsinckia washintonensis, Amsonia glaberrima, Amsonia latifolia, Amsonia tabernaemontana, Amsonia tristis, Amyelois transitella, Amygdalus amara, Amygdalus communis subsp. microphylla, Amygdalus communis subsp. spontanea, Amygdalus communis, Amygdalus dulcis, Amygdalus fragilis, Amygdalus georgica, Amygdalus korshinskyi, Amygdalus lindleyi, Amygdalus nana, Amygdalus persica, Amygdalus ramonensis, Amygdalus sativa, Amygdalus triloba, Amynthas corticis, Amynthas gracilis, Amynthas morrisi, Amynthas rodericensis, Amyrsidea phaeostoma, Anabaena raciborskii, Anacampseros aizoon, Anacampseros albida, Anacampseros alpestris, Anacampseros aprica, Anacampseros arguta, Anacampseros assurgens, Anacampseros aurigerana, Anacampseros beugesiaca, Anacampseros borderi, Anacampseros buxicola, Anacampseros cebennensis, Anacampseros cepaea, Anacampseros chlorotica, Anacampseros collina, Anacampseros conferta, Anacampseros convexa, Anacampseros corsica, Anacampseros delphinensis, Anacampseros dumeticola, Anacampseros erubescens, Anacampseros hybrida, Anacampseros julliana, Anacampseros lapidicola, Anacampseros lugdunensis, Anacampseros maxima, Anacampseros millieri, Anacampseros minor, Anacampseros monticulorum, Anacampseros navieri, Anacampseros pachyphylla, Anacampseros praecelsa, Anacampseros praeruptorum, Anacampseros purpurea, Anacampseros pycnantha, Anacampseros recurva, Anacampseros repens, Anacampseros rhodanensis, Anacampseros rubella, Anacampseros rupifraga, Anacampseros saxifraga, Anacampseros sempervirens, Anacampseros serotina, Anacampseros subalbida, Anacampseros subrotunda, Anacampseros ternata, Anacampseros triphylla, Anacampseros verlotii, Anacampseros viridula, Anacampseros vogesiaca, Anacampseros vulgaris, Anacamptis laxiflora, Anacharis callitrichoides, Anacharis canadensis var. planchonii, Anacharis canadensis, Anacharis crispa, Anacharis densa, Anacharis nuttallii, Anacharis occidentalis, Anachortus articulatus, Anachortus divaricatus, Anachortus oranensis, Anacridium aegyptium, Anactis pilosa, Anacyclus aristulatus, Anacyclus aureus, Anacyclus australis, Anacyclus austriacus, Anacyclus bicolor, Anacyclus candolii, Anacyclus capillifolius, Anacyclus clavatus, Anacyclus depressus, Anacyclus dissimilis, Anacyclus divaricatus, Anacyclus freynii, Anacyclus hirsutus, Anacyclus lanuginosus, Anacyclus mucronulatus, Anacyclus nobilis, Anacyclus officinarum, Anacyclus pallescens, Anacyclus prostratus, Anacyclus pseudopyrethrum, Anacyclus pubescens, Anacyclus pulcher, Anacyclus purpurascens, Anacyclus pyrethrum, Anacyclus radiatus, Anacyclus tinctorius, Anacyclus tomentosus, Anacyclus triumfetti, Anacyclus valentinus, Anacylus clavatus, Anacylus tomentosus, Anacylus valentinus, Anadara broughtonii, Anadara demiri, Anadara inaequivalvis, Anadara inflata, Anadara kagoshimensis, Anadara natalensis, Anadara sulcosa, Anadara transversa, Anadenobolus monilicornis, Anadenobolus vincenti, Anagallis arvensis subsp. caerulea, Anagallis arvensis subsp. foemina, Anagallis arvensis var. caerulea, Anagallis caerulea, Anagallis coerulea, Anagallis collina, Anagallis foemina, Anagallis linifolia, Anagallis maritima, Anagallis monelli subsp. collina, Anagallis monelli subsp. hortensis, Anagallis monelli, Anagallis x doerfleri, Anagalloides procumbens, Anagyrus agraensis, Anagyrus fusciventris, Anagyrus pseudococci, Anagyrus subflaviceps, Anaphalioides bellidioides, Anaphalis angustifolia, Anaphalis cinnamomea, Anaphalis japonica, Anaphalis lanata, Anaphalis margaritacea var. angustior, Anaphalis margaritacea var. intercedens, Anaphalis margaritacea var. occidentalis, Anaphalis margaritacea var. revoluta, Anaphalis margaritacea var. subalpina, Anaphalis margaritacea, Anaphalis occidentalis, Anaphalis prostrata, Anaphalis sierrae, Anaphalis timmua, Anaphes nitens, Anaphothrips (Hemianaphothrips) annulicornis, Anaphothrips graminum, Anaphothrips obscurus, Anaphothrips orchidaceus, Anaphothrips orchidii, Anaphothrips sudanensis, Anarrhinum anarrhinum, Anarrhinum bellidifolium, Anarrhinum crassifolium, Anarrhinum linnaeanum, Anarrhinum lusitanicum, Anarrhinum violaceum, Anarsia lineatella, Anas acuta acuta, Anas acuta, Anas americana, Anas angustirostris, Anas bahamensis, Anas bernicla, Anas canadensis, Anas capensis, Anas castanea, Anas cyanoptera, Anas discors discors, Anas discors orphna, Anas discors, Anas erythrorhyncha, Anas erythrorhynchos, Anas falcata, Anas flavirostris, Anas formosa, Anas georgica, Anas hottentota, Anas leucophrys, Anas penelope, Anas platyrhynchos, Anas poecilorhynca, Anas poecilorhyncha, Anas sibilatrix, Anas strepera, Anas undulata, Anas versicolor, Anastatica hierochuntica, Anastatica syriaca, Anastatus japonicus, Anastatus tenuipes, Anastrangalia reyi, Anastrophus paspaloides, Anatherostipa mucronata, Anatherostipa saltensis, Anatherum glabrum, Anatherum montanum, Anatherum virginicum subvar. tetrastachyum, Anatherum virginicum var. tetrastachyum, Anatherum virginicum, Anatina labiata, Anatina subrostrata, Anatrachyntis badia, Anatrachyntis simplex, Anchiphiloscia balssi, Anchonidium unguiculare, Anchoviella indica, Anchoviella scitula, Anchusa adamii, Anchusa amoena, Anchusa amplexicaulis, Anchusa angustifolia, Anchusa angustissima, Anchusa annua, Anchusa arvalis, Anchusa arvensis subsp. arvensis, Anchusa arvensis subsp. orientalis, Anchusa azurea, Anchusa barrelieri, Anchusa baumgartenii, Anchusa biceps, Anchusa cesatiana, Anchusa clavata, Anchusa coronensis, Anchusa crispa, Anchusa crispata, Anchusa davidovii, Anchusa divaricata, Anchusa dubia, Anchusa echioides, Anchusa gmelinii, Anchusa granatensis, Anchusa hispida, Anchusa hybrida, Anchusa incarnata, Anchusa italica, Anchusa lanata, Anchusa latifolia, Anchusa laxiflora, Anchusa leptophylla, Anchusa leucojifolia, Anchusa licopsipula, Anchusa lucida, Anchusa luschanii, Anchusa lutea, Anchusa lycopsidis, Anchusa macrocalyx, Anchusa macrophylla, Anchusa maculata, Anchusa microcalyx, Anchusa myosotidiflora, Anchusa nonneoides, Anchusa obliqua, Anchusa obtusa, Anchusa ochroleuca subsp. legitima, Anchusa ochroleuca var. legitima, Anchusa ochroleuca, Anchusa officinalis subsp. angustifolia, Anchusa officinalis, Anchusa orientalis, Anchusa osmanica, Anchusa ovata, Anchusa paniculata, Anchusa parnassica, Anchusa pinardii, Anchusa procera, Anchusa pseudochroleuca, Anchusa pulla, Anchusa pustulata, Anchusa rosea, Anchusa sempervirens, Anchusa spicata, Anchusa stylosa, Anchusa subglabra, Anchusa thessala, Anchusa tinctoria, Anchusa undulata subsp. hybrida, Anchusa undulata var. subvelutina, Anchusa undulata, Anchusa velenovskyi, Anchusa ventricosa, Anchusa versicolor, Anchusa vulgaris, Anchusa x baumgarteni, Ancistrosyllis parva, Ancistrosyllis rigida, Ancistrosyllis tentaculata, Ancistrum repens, Ancistrus gibbiceps, Andrachne asperula, Andrachne cretica, Andrachne frutescens, Andrachne nummulariifolia, Andrachne pojarkoviae, Andrachne rotundifolia, Andrachne telephioides subsp. oreocretensis, Andrachne telephioides var. brevifolia, Andrachne telephioides var. rotundifolia, Andrachne telephioides, Andrachne virescens, Andrachne vvedenskyi, Andreoskia cardaminifolia, Andricus corruptrix, Andricus grossulariae, Andricus kollari, Andricus lignicola, Andricus quercuscalicis, Androcera rostrata, Andromeda angustifolia, Andromeda calyculata, Andromeda crispa, Andromeda daboecia, Andromeda daboecii, Andromeda montana, Androniscus dentiger, Andropogon acutiusculus, Andropogon affinis, Andropogon altissimus, Andropogon ambiguus, Andropogon annulatus var. bladhii, Andropogon annulatus var. subrepens, Andropogon annulatus, Andropogon argenteus, Andropogon arundinaceus, Andropogon barbinodis, Andropogon berteronianus, Andropogon bertheroanus, Andropogon besukiensis, Andropogon bicolor, Andropogon bifoveolatus, Andropogon bladhii, Andropogon blakei, Andropogon bouangensis, Andropogon caffrorum, Andropogon capillipes, Andropogon caucasicus, Andropogon chrysatherus, Andropogon collinus, Andropogon contortum, Andropogon contortus subvar. secundus, Andropogon contortus var. glaber, Andropogon contortus, Andropogon controversus, Andropogon curtisianus, Andropogon dalmaticus, Andropogon dealbatus, Andropogon decipiens, Andropogon decolorans, Andropogon digitatus, Andropogon dissitiflorum, Andropogon dissitiflorus, Andropogon distachyos var. pubescens, Andropogon distachyos, Andropogon drummondii, Andropogon dubitatus, Andropogon elegantissimus, Andropogon emersus, Andropogon eriophorus, Andropogon fasciculatus, Andropogon firmus, Andropogon fulvicomus var. approximatus, Andropogon fulvicomus, Andropogon garipensis, Andropogon giganteus, Andropogon glaber, Andropogon glaucescens, Andropogon grisebachii, Andropogon haenkei, Andropogon halepensis subsp. anatherus, Andropogon halepensis var. effusus, Andropogon halepensis var. genuinus, Andropogon halepensis var. muticus, Andropogon halepensis var. sudanensis, Andropogon halepensis, Andropogon hermaphroditum, Andropogon hirsutus var. pubescens, Andropogon hirsutus, Andropogon hirtum, Andropogon hirtus var. glabriglumis, Andropogon hirtus var. glaucus, Andropogon hirtus var. longiaristatus, Andropogon hirtus var. podotrichus, Andropogon hirtus var. pubescens, Andropogon hirtus, Andropogon hirtusb, Andropogon insculptus, Andropogon intermedius subvar. perfossus, Andropogon intermedius var. caucasicus, Andropogon intermedius var. genuinus, Andropogon intermedius var. punctatus, Andropogon intermedius, Andropogon intortum, Andropogon inundatus, Andropogon ischaemum var. americanus, Andropogon ischaemum var. barbinodis, Andropogon ischaemum var. genuinus, Andropogon ischaemum var. ischaemum, Andropogon ischaemum, Andropogon jubatus, Andropogon kunthii, Andropogon leptanthus, Andropogon leucopogon, Andropogon louisianae, Andropogon macer, Andropogon miliaceus, Andropogon miliformis, Andropogon modestus, Andropogon modicus, Andropogon montanus, Andropogon obtusus, Andropogon odoratus, Andropogon palmeri, Andropogon panormitanus, Andropogon patulus, Andropogon perforatus, Andropogon perfossus, Andropogon pertusus subvar. trifoveolatus, Andropogon pertusus var. capensis, Andropogon pertusus var. decipiens, Andropogon pertusus var. insculptus, Andropogon pertusus, Andropogon pichleri, Andropogon pilosus, Andropogon podotrichus, Andropogon pubescens, Andropogon punctatus, Andropogon ravennae, Andropogon reevesii, Andropogon rufus var. fulvicomus, Andropogon rufus var. glabrescens, Andropogon rufus, Andropogon saccharatus, Andropogon saccharoides subsp. genuinus, Andropogon saccharoides subsp. leucopogon, Andropogon saccharoides subvar. saccharoides, Andropogon saccharoides subvar. typicus, Andropogon saccharoides var. barbinodis, Andropogon saccharoides var. genuinus, Andropogon saccharoides var. saccharoides, Andropogon saccharoides var. surius, Andropogon saccharoides, Andropogon saccharoiedes, Andropogon sanguinarius, Andropogon scandens, Andropogon schlumbergeri, Andropogon secundus, Andropogon sericeus, Andropogon sinaicus, Andropogon sorghum subsp. halepensis, Andropogon sorghum subsp. sudanensis, Andropogon sorghum subvar. genuinus, Andropogon sorghum subvar. japonicus, Andropogon sorghum subvar. leiocladus, Andropogon sorghum subvar. muticus, Andropogon sorghum subvar. trachycladus, Andropogon sorghum var. albofuscus, Andropogon sorghum var. bicarinatus, Andropogon sorghum var. bicolor, Andropogon sorghum var. cernuus, Andropogon sorghum var. corymbosus, Andropogon sorghum var. dochna, Andropogon sorghum var. drummondii, Andropogon sorghum var. durra, Andropogon sorghum var. exiguum, Andropogon sorghum var. halepensis, Andropogon sorghum var. hians, Andropogon sorghum var. nervosus, Andropogon sorghum var. perennis, Andropogon sorghum var. saccharatus, Andropogon sorghum var. sativus, Andropogon sorghum var. subglobosus, Andropogon sorghum var. submuticus, Andropogon sorghum var. sudanensis, Andropogon sorghum var. technicus, Andropogon sorghum var. vulgaris, Andropogon sorghum, Andropogon subunifoveclatus, Andropogon sudanensis, Andropogon superciliatus, Andropogon taiwanensis, Andropogon tenuiculus, Andropogon tetrastachyus, Andropogon transvaalensis, Andropogon undulatus, Andropogon vachellii, Andropogon vaginatus, Andropogon vimineum, Andropogon vimineus, Andropogon virginicus f. virginicus, Andropogon virginicus subsp. genuinus, Andropogon virginicus subvar. ditior, Andropogon virginicus var. genuinus, Andropogon virginicus var. scabriglumus, Andropogon virginicus var. tetrastachyus, Andropogon virginicus var. vaginatus, Andropogon virginicus var. viridis, Andropogon virginicus, Andropogon vulgaris, Andropogon x drummondii, Andropogon x sudanensis, Andropogon xanthoblepharis, Andropogon yinduensis, Androsace aquatica, Androsace asprella, Androsace bocconii, Androsace capillaris, Androsace caucasica, Androsace elongata, Androsace fasciculata, Androsace filiformis, Androsace gormanii, Androsace intermedia, Androsace macloviana, Androsace maxima, Androsace nana, Androsace neglecta, Androsace raddeana, Androsace radiata, Androsace tauscheri, Androsace torrepandoi, Androsace turczaninowii, Androsaemum calycinum, Androsaemum foetidum, Androsaemum hircinum, Androsaemum officinale, Androsaemum vulgare, Androsaemum x parviflorum, Androsaemum x urberuagae, Androsaemum xylosteifolium, Andrya cuniculi, Andryala allochroa, Andryala aurea, Andryala corymbosa, Andryala dissecta, Andryala gracilis, Andryala humilis, Andryala integrifolia, Andryala lanata, Andryala laxiflora, Andryala malacitana, Andryala minuta, Andryala mollis, Andryala nemausensis, Andryala parviflora, Andryala reboudiana, Andryala runcinata, Andryala sinuata, Aneilema coreanum, Aneilema keisak, Aneilema nudicaule, Aneilema nudiflorum, Aneilema oliganthum, Aneilema taquetii, Anellaria antillarum, Anemagrostis interrupta, Anemagrostis spica-venti, Anemanthus nemorosus, Anemanthus ranunculoides, Anemarrhena cavaleriei, Anemonanthea nemorosa, Anemonanthea ranunculoides, Anemone alba, Anemone americana, Anemone apennina subsp. blanda, Anemone apennina var. pallida, Anemone apennina, Anemone atragene, Anemone blanda, Anemone canadensis f. canadensis, Anemone canadensis f. dicksonii, Anemone canadensis, Anemone coccinea, Anemone coerulescens, Anemone coronaria, Anemone curta, Anemone cyanea, Anemone dichotoma, Anemone flammula, Anemone glacialis, Anemone hackelii, Anemone halleri, Anemone hepatica, Anemone hupehensis x vitifolia, Anemone hupehensis, Anemone hybrida, Anemone intermedia, Anemone janczewskii, Anemone jenisseensis, Anemone lutea, Anemone messarensis, Anemone nemorosa, Anemone nemorosa-lutea, Anemone nobilis, Anemone pentaphylla, Anemone pinnatifida, Anemone pratensis, Anemone pulsatilla, Anemone pygmaea, Anemone pyrenaica, Anemone ranunculiflora, Anemone ranunculiformis, Anemone ranunculoides, Anemone ranunculoidi-nemorosa, Anemone recta, Anemone rissoana, Anemone rosea, Anemone slavica, Anemone sordida, Anemone sylvestris, Anemone thalictroides, Anemone tomentosa, Anemone transsilvanica, Anemone ventreana, Anemone vitalba, Anemone viticella, Anemone vulgaris, Anemone x hybrida, Anemonella thalictroides, Anemonidium canadense, Anemonidium nemorosum, Anemonoides apennina, Anemonoides blanda, Anemonoides jenisejensis, Anemonoides nemorosa, Anemonoides ranunculoides, Anemonospermos stoechadifolia, Anethum arvense, Anethum graveolens subsp. hortorum, Anethum graveolens, Anethum pinnatum, Anethum pusillum, Anethum segetum, Aneurolepidium karelinii, Aneurolepidium multicaule, Aneurota sulcifrons, Angelica archangelica subsp. archangelica, Angelica archangelica subsp. litoralis, Angelica archangelica var. litoralis, Angelica archangelica, Angelica graveolens, Angelica hultenii, Angelica litoralis, Angelica norvegica, Angelica ostruthium, Angelica pachycarpa, Angelica scotica, Angelica verticillaris, Angiola punctostriata, Anguilla japonica, Anguilla rostrata, Anguillicola australiensis, Anguillicola crassus, Anguillicola novaezelandiae, Anguillicoloides crassus, Anguillula (Rhabdonema) stercoralis, Anguillula (Rhabdonema) strongyloides, Anguillula agrostis, Anguillula arenaria, Anguillula dipsaci, Anguillula intestinalis bovis, Anguillula intestinalis, Anguillula javanica, Anguillula scandens, Anguillula stercoralis, Anguillula strongyloides, Anguillula tritici, Anguillulina (Anguina) agrostis, Anguillulina (Anguina) scandens, Anguillulina (Anguina) tritici, Anguillulina agrostis, Anguillulina allocatus, Anguillulina communis, Anguillulina dipsaci, Anguillulina mahogani, Anguillulina oryzae, Anguillulina scandens, Anguillulina similis, Anguillulina tritici, Anguina agrostis, Anguina funesta, Anguina lolii, Anguina tritici, Anguinum victorialis, Anguis fragilis, Angulus flacca, Anguria citrullus, Anguria pedisecta, Anicetus annulatus, Anidrum flosculosum, Anidrum radians, Anidrum testiculatum, Anilocra pilchardi, Anilocra pilchardip, Anisakis alata, Anisakis catodontis, Anisakis ivanizkii, Anisakis kogiae, Anisakis kuekenthalii, Anisakis kukenthhalii, Anisakis marina, Anisakis patagonica, Anisakis pegreffii, Anisakis rosmari, Anisakis similis, Anisakis simplex, Anisakis simplex_A, Anisakis tridentata, Anisandrus maiche, Anisantha diandra subsp. rigida, Anisantha flabellata, Anisantha madritensis, Anisantha rigens, Anisantha rigida, Anisantha rubens, Anisantha sterilis, Anisantha tectorum, Anisocalyx limnanthiflorus, Anisocentra cardiopetala, Anisodactylus binotatus, Anisodens arvensis, Anisoderis foetida, Anisoderis rhoeadifolia, Anisogonium esculentum, Anisogonium serampurens, Anisolabis annulipes, Anisolabis maritima, Anisomeridium polypori, Anisophyllum chamaesyce, Anisophyllum emarginatum, Anisophyllum granulatum, Anisophyllum humifusum, Anisophyllum humistratum, Anisophyllum hypericifolium, Anisophyllum maculatum, Anisophyllum polygonifolium, Anisophyllum prostratum, Anisophyllum scordiifolium, Anisophyllum serpens, Anisopilothrips venustulus, Anisopteromalus calandrae, Anisorhynchus hespericus, Anisum creticum, Anisum italicum, Anisum odoratum, Anisum officinale, Anisum officinarum, Anisum vulgare, Ankylobus hamosus, Anneslia tweediei, Annona asiatica, Annona cinerea, Annona squamosa, Anobium caelatum, Anobium cylindricum, Anobium domesticum, Anobium frumentarium, Anobium latreillei, Anobium pertinax, Anobium pumilum, Anobium punctatum, Anobium striatum, Anoda acerifolia, Anoda arizonica, Anoda cristata var. brachyantha, Anoda cristata var. digitata, Anoda cristata, Anoda dilleniana, Anoda fernandeziana, Anoda hastata, Anoda incarnata, Anoda lavaterioides, Anoda lavateroides, Anoda populifolia, Anoda strictiflora, Anoda triangularis, Anoda triloba, Anodonta woodiana, Anodontea dasycarpa, Anodontea edentula, Anodontea halimifolia, Anodorhynchus hyacinthinus, Anoectangium gedeanum, Anolis allogus, Anolis carolinensis, Anolis equestris, Anolis porcatus, Anolis sagrei, Anomatheca cruenta, Anomatheca laxa, Anomia chinensis, Anommatus diecki, Anommatus duodecimstriatus, Anoplocephala perfoliata, Anoplodactylus californicus, Anoplodactylus digitatus, Anoplodactylus investigatoris, Anoplodactylus portus, Anoplodactylus saxatilis, Anoplonyx destructor, Anoplophora chinensis, Anoplophora glabripennis, Anotrichium furcellatum, Anotylus nitidifrons, Anotylus nitidulus, Anotylus speculifrons, Anredera cordifolia, Ansatospora acerina, Anser albifrons, Anser anser, Anser brachyrhynchus, Anser caerulescens, Anser canagicus, Anser cygnoides, Anser erythropus, Anser fabalis brachyrhynchus, Anser fabalis, Anser hutchinsii, Anser hyperboreus, Anser indicus, Anser rossii, Anseranas semipalmata, Anserina betifolia, Anserina bonus-henricus, Anserina ficifolia, Anserina opulifolia, Anserina urbica, Ansonia latifolia, Antaxius spinibrachius, Anteaeolidiella foulisi, Anteaeolidiella indica, Anteaeolidiella lurana, Antennaria cinnamomea, Antennaria leontopodium, Antennaria plantaginea, Antennularia arxii, Antenoron filiforme var. filiforme, Anthactinia walkeri, Anthelia juratzkana, Anthema arborea, Anthema cretica, Anthemis abyssinica, Anthemis agrestis, Anthemis altissima, Anthemis anglica, Anthemis arvensis var. agrestis, Anthemis arvensis var. arvensis, Anthemis arvensis, Anthemis aurea, Anthemis austriaca, Anthemis biaristata, Anthemis brachycentros, Anthemis brachyglossa, Anthemis canescens, Anthemis chrysantha, Anthemis clavata, Anthemis coarctata, Anthemis cota, Anthemis cotiformis, Anthemis cotula, Anthemis crassipes, Anthemis dentata, Anthemis discoidea, Anthemis foetida, Anthemis frutescens, Anthemis fuscata, Anthemis granatensis, Anthemis hungarica, Anthemis hyalina, Anthemis inconspicua, Anthemis kitenensis, Anthemis lanuginosa, Anthemis markhotensis, Anthemis millefolia, Anthemis mixta, Anthemis muricata, Anthemis nigrescens, Anthemis nigricans, Anthemis nobilis, Anthemis parnassi, Anthemis platyglossa, Anthemis praecox, Anthemis pseudocota, Anthemis psorosperma, Anthemis punctata, Anthemis purpurascens, Anthemis purpurea, Anthemis pyrethrum, Anthemis ramosa, Anthemis ruthenica, Anthemis sachokiana, Anthemis saguramica, Anthemis sallei, Anthemis santolinoides, Anthemis segetalis, Anthemis talyschensis, Anthemis tinctoria, Anthemis tomentosa, Anthemis triumfettii, Anthemis urvillaeana, Anthemis valentina, Anthemis woronowii, Anthemus hilli, Antheraea pernyi, Antheraea yamamai, Anthericum autumnale, Anthericum bifolium, Anthericum comosum, Anthericum dorsetii, Anthericum esculentum, Anthericum gracile, Anthericum liliago subsp.macrocarpum, Anthericum liliago var. australe, Anthericum liliago var. multiflorum, Anthericum liliago var. sphaerocarpum, Anthericum liliago, Anthericum longituberosum, Anthericum macrocarpum, Anthericum non-scriptum, Anthericum planifolium, Anthericum quamash, Anthericum ramosum, Anthericum sternbergianum, Anthericum sulphureum, Anthericum vallis-trappii, Anthericum williamsii, Anthias jocu, Anthias macrophthalmus, Anthicus crinitus, Anthicus czernohorskyi, Anthicus floralis, Anthicus formicarius, Anthicus tobias, Anthicus tristis, Anthipsimus gonopodos, Anthipsimus gonopodus, Anthochytrum alpinum, Anthocoptes punctidorsa, Anthocoptes transitionalis, Anthocoris butleri, Anthocoris sarothamni, Anthodendron ponticum, Antholyza bicolor, Antholyza floribunda, Antholyza laxiflora, Antholyza paniculata, Antholyza praealta, Antholyza schlechteri, Antholyza x crocosmioides, Anthomeles douglasii, Anthomyia aenescens, Anthomyia calopteni, Anthomyia cana, Anthomyia isura, Anthomyia perrima, Anthomyia platura, Anthomyia pusio, Anthomyia raphani, Anthomyia tinia, Anthomyia trifilis, Anthomyia tuberosa, Anthomyia viana, Anthomyia zeas, Anthonomus eugenii, Anthonomus rectirostris, Anthosachne scabra, Anthostomella trachycarpi, Anthoxanthum aculeatum, Anthoxanthum aetnense, Anthoxanthum angustifolium, Anthoxanthum aristatum subsp. puelii, Anthoxanthum aristatum, Anthoxanthum carrenianum, Anthoxanthum hirtum, Anthoxanthum laxiflorum, Anthoxanthum lloydii, Anthoxanthum maderense, Anthoxanthum myrthense, Anthoxanthum nebrodense, Anthoxanthum nitens, Anthoxanthum odoratum subsp. aristatum, Anthoxanthum odoratum subsp. ovatum, Anthoxanthum odoratum var. altissimum, Anthoxanthum odoratum var. aristatum, Anthoxanthum odoratum var. puelii, Anthoxanthum odoratum, Anthoxanthum ovatum subsp. aristatum, Anthoxanthum ovatum var. aristatum, Anthoxanthum ovatum, Anthoxanthum pauciflorum, Anthoxanthum pilosum, Anthoxanthum puelii var. lloydii, Anthoxanthum puelii, Anthoxanthum sommierianum, Anthoxanthum villosum, Anthrenocerus australis, Anthrenus caucasicus, Anthrenus coloratus, Anthrenus festivus, Anthrenus flavidus, Anthrenus flavipes, Anthrenus fuscus, Anthrenus museorum, Anthrenus oceanicus, Anthrenus olgae, Anthrenus pimpinellae, Anthrenus scrophulariae, Anthrenus verbasci, Anthriscus arvensis, Anthriscus caucalis, Anthriscus cerefolium subsp. longirostris, Anthriscus cerefolium subsp. trichosperma, Anthriscus cerefolium subsp. trichospermus, Anthriscus cerefolium var. cerefolium, Anthriscus cerefolium var. trichocarpus, Anthriscus cerefolium var. trichospermus, Anthriscus cerefolium, Anthriscus chaerophyllus, Anthriscus fumarioides, Anthriscus leptophylla, Anthriscus longirostris, Anthriscus neglecta var. scandix, Anthriscus neglecta, Anthriscus nodiflora, Anthriscus nodosa, Anthriscus sativa, Anthriscus scandicina, Anthriscus scandicinus, Anthriscus scandix, Anthriscus sicula, Anthriscus sylvestris subsp. fumarioides, Anthriscus sylvestris, Anthriscus trachysperma, Anthriscus trichosperma, Anthriscus vandasii, Anthriscus vulgaris, Anthropoides virgo, Anthurus archeri, Anthurus muellerianus var. aseroëformis, Anthyllis affinis, Anthyllis alpestris, Anthyllis arenaria, Anthyllis carpatica, Anthyllis colorata, Anthyllis dillenii, Anthyllis linnaei, Anthyllis lotoides, Anthyllis macrocephala var. schiwereckii, Anthyllis macrocephala, Anthyllis polyphylla, Anthyllis pseudovulneraria, Anthyllis rubicunda, Anthyllis schiwereckii, Anthyllis tricolor, Anthyllis vulgaris, Anthyllis vulneraria subsp. carpatica var. pseudovul, Anthyllis vulneraria subsp. carpatica, Anthyllis vulneraria subsp. corbierei, Anthyllis vulneraria subsp. linnaei, Anthyllis vulneraria subsp. polyphylla, Anthyllis vulneraria subsp. vulgaris, Anthyllis vulneraria subsp. vulneraria, Anthyllis vulneraria var. polyphylla, Anthyllis vulneraria var. schiwereckii, Anthyllis vulneraria var. vulneraria, Anthyllis vulneraria, Anthyllis x rubicunda, Antichorus depressus, Antidesma scandens, Antigona lamellaris, Antigonon amabie, Antigonon cinerascens, Antigonon cordatum, Antigonon leptopus, Antigonon platypus, Antiponemertes pantini, Antirrhinum album, Antirrhinum alpinum, Antirrhinum angustifolium, Antirrhinum angustissimum, Antirrhinum arenarium, Antirrhinum arvense, Antirrhinum asarifolium, Antirrhinum asarina, Antirrhinum asarinum, Antirrhinum assurgens, Antirrhinum barrelieri var. ruscinonense, Antirrhinum bellidifolium, Antirrhinum bipartitum, Antirrhinum caesium, Antirrhinum calycinum var. rubra, Antirrhinum canadense var. assurgens, Antirrhinum canadense, Antirrhinum capitatum, Antirrhinum chalepense, Antirrhinum cirrhosum, Antirrhinum commune, Antirrhinum compositum, Antirrhinum cordatum, Antirrhinum craniolare, Antirrhinum dalmaticum, Antirrhinum dielsianum, Antirrhinum diminutum, Antirrhinum dubium, Antirrhinum elegans, Antirrhinum gallioides, Antirrhinum gebelicum, Antirrhinum gibbosum, Antirrhinum glandulosum, Antirrhinum glaucum, Antirrhinum gracile, Antirrhinum graecum, Antirrhinum graniticum, Antirrhinum hepaticifolium, Antirrhinum hirtum, Antirrhinum humile, Antirrhinum incarnatum, Antirrhinum indicum, Antirrhinum intermedium, Antirrhinum italicum, Antirrhinum jamaicense, Antirrhinum junceum, Antirrhinum lanigerum, Antirrhinum lazari, Antirrhinum leiocalyx, Antirrhinum linaria var. peloria, Antirrhinum linarioides, Antirrhinum linogriseum, Antirrhinum majus subsp. majus, Antirrhinum majus subsp. siculum, Antirrhinum majus subsp. tortuosum, Antirrhinum majus var. algeriense, Antirrhinum majus var. angustifolium, Antirrhinum majus var. dubium, Antirrhinum majus var. ottomanum, Antirrhinum majus var. ramosissimum, Antirrhinum majus var. siculum, Antirrhinum majus var. tortuosum, Antirrhinum majus, Antirrhinum minor, Antirrhinum minus, Antirrhinum monspessulanum, Antirrhinum montevidense, Antirrhinum ochroleucum, Antirrhinum orchidiflorum, Antirrhinum origanifolium, Antirrhinum orontium subsp. calycinum, Antirrhinum orontium var. calycinum, Antirrhinum orontium var. chrysothales, Antirrhinum orontium var. foliosum, Antirrhinum orontium var. grandiflorum, Antirrhinum orontium var. leiocarpum, Antirrhinum orontium, Antirrhinum osyris, Antirrhinum ottomanum, Antirrhinum pallidum, Antirrhinum parviflorum, Antirrhinum pelisserianum, Antirrhinum pilosum, Antirrhinum polygalifolium, Antirrhinum prostratum, Antirrhinum pubescens, Antirrhinum purpureum, Antirrhinum pyrenaicum, Antirrhinum quinquelobatum, Antirrhinum reflexum, Antirrhinum repens var. monspessulanum, Antirrhinum repens, Antirrhinum rhodium, Antirrhinum romanum, Antirrhinum ruscinonense, Antirrhinum saphyrinum var. incarnatum, Antirrhinum saphyrinum, Antirrhinum siculum var. algeriense, Antirrhinum siculum var. elatum, Antirrhinum siculum var. glandulosum, Antirrhinum siculum var. panormitanum, Antirrhinum siculum var. ruscinonense, Antirrhinum siculum var. tortuosum, Antirrhinum siculum, Antirrhinum simplex, Antirrhinum sparteum, Antirrhinum speciosum, Antirrhinum spurium var. integrifolium, Antirrhinum striatum, Antirrhinum ternatum, Antirrhinum theodori, Antirrhinum thuillieri, Antirrhinum tortuosum var. compositum, Antirrhinum tortuosum, Antirrhinum triornithophorum, Antirrhinum vidalianum, Antirrhinum villosum, Antirrhinum violaceum, Antirrhinum viscosum, Antispila oinophylla, Antithamnion algeriense, Antithamnion amphigeneum, Antithamnion applicitum, Antithamnion cristirhizophorum, Antithamnion defectum, Antithamnion densum, Antithamnion diminuatum, Antithamnion glanduliferum, Antithamnion hubbsii, Antithamnion miharae, Antithamnion nipponicum, Antithamnion pectinatum, Antithamnion preissii, Antithamnion pygmaeum, Antithamnion sarniensis, Antithamnion setaceum, Antithamnion sparsum, Antithamnion spirographidis, Antithamnion tenuissima, Antithamnion ternifolium, Antithamnionella boergesenii, Antithamnionella elegans var. boergesenii, Antithamnionella elegans, Antithamnionella glandulifera, Antithamnionella sarniensis, Antithamnionella spirographidis, Antithamnionella sublittorale, Antithamnionella sublittoralis, Antithamnionella ternifolia, Antitragus aculeatus, Antonina crawi, Antonina graminis, Antoschmidtia kalahariensis, Antriscus fetidus, Antropora leucocypha, Anuraphis erratica, Anuraphis mume, Aonchotheca annulosa, Aonidia lauri, Aonidiella aurantii, Aonidiella citrina, Aonidiella lauretorum, Aonidiella taxus, Aonidiella tinerfensis, Aoroides curvipes, Aoroides longimerus, Aoroides semicurvatus, Apalodium lanceolatum, Apalone ferox, Apamea remissa, Apanthura sandalensis, Apargia aurea, Apargia autumnalis, Apargia hirta, Apargia hispida, Apargia setosa, Aparinanthus muralis, Aparinanthus verticillatus, Aparine minima, Aparine parisiensis, Aparine spuria, Aparine tenera, Aparine verrucosa, Aparinella decipiens, Aparinella litigiosa, Aparinella parisiensis, Aparinella ruricola, Apate geayi, Apate monacha, Apate monachus, Apate terebrans, Apedinella radians, Apedinella spinifera, Apera effusa, Apera intermedia, Apera interrupta, Apera longiseta, Apera maritima, Apera palustris, Apera purpurea, Apera spica-venti var. interrupta, Apera spica-venti, Aphaenogaster senilis senilis, Aphaenogaster senilis, Aphanarthrum affine, Aphanarthrum bicinctum, Aphanarthrum bicolor, Aphanarthrum mairei, Aphanarthrum piscatorium, Aphanes arvensis auct., Aphanes arvensis, Aphanes australis, Aphanes delicatula, Aphanes microcarpa, Aphanes occidentalis, Aphanes triloba, Aphanes vulgaris, Aphanochilus stauntonii, Aphanogmus bicolor, Aphanomyces astaci, Aphanomyces euteiches, Aphelenchoides (Chitinoaphelenchus) ritzemabosi, Aphelenchoides besseyi, Aphelenchoides fragariae, Aphelenchoides longicollis, Aphelenchoides olesistus var. longicollis, Aphelenchoides olesistus, Aphelenchoides oryzae, Aphelenchoides pseudolesistus, Aphelenchoides ribes, Aphelenchoides ritzemabosi, Aphelenchoides xylophilus, Aphelenchus fragariae, Aphelenchus longicollis, Aphelenchus olesistus var. longicollis, Aphelenchus olesistus, Aphelenchus ormerodis, Aphelenchus phyllophagus, Aphelenchus pseudolesistus, Aphelenchus ribes, Aphelenchus ritzema-bosi, Aphelinus mali, Aphelinus semiflavus, Aphelonyx cerricola, Aphid aurantii, Aphid nymphaeae, Aphidius colemani, Aphidius smithi, Aphidoletes abietis, Aphis adusta, Aphis africana, Aphis bidentis, Aphis camelliae, Aphis catalpae, Aphis citricola, Aphis coffeae, Aphis consors, Aphis convolvuli, Aphis cooki, Aphis craccivora, Aphis croomiae, Aphis cymbalariae, Aphis cynoglossi, Aphis cytisorum, Aphis deposita, Aphis derelicta, Aphis deutziae, Aphis dianthi, Aphis dubia, Aphis egressa, Aphis eupatorii, Aphis forbesi, Aphis gladioli, Aphis gossypii, Aphis illinoisensis, Aphis iridis, Aphis lanata, Aphis mitsubae, Aphis nerii, Aphis nostras, Aphis obnoxia, Aphis oenotherae oenotherae, Aphis oenotherae, Aphis papaveris, Aphis particeps, Aphis passeriniana, Aphis persicophila, Aphis persola, Aphis pirifoliae, Aphis pseudopomi, Aphis pyriphaga, Aphis rapae, Aphis redundans, Aphis rufomaculata, Aphis salicariae, Aphis spiraecola, Aphis spiraephaga asiatica, Aphis spiraephaga, Aphis spiraephila, Aphis thalictri, Aphis vastator, Aphis viburnicolens, Aphis vulgaris, Aphis vulpiae, Aphodius gracilis, Aphomia gularis, Aphomonix hederacea, Aphrasstasia tsugae, Aphrastasia pectinatae, Aphrodita complanata, Aphyllocalpa regalis, Aphyllon uniflorum, Aphytis abnormis, Aphytis acrenulatus, Aphytis chilensis, Aphytis coheni, Aphytis diaspidis, Aphytis holoxanthus, Aphytis lepidosaphes, Aphytis lingnanensis, Aphytis melinus, Aphytis mytilaspidis, Aphytis yanonensis, Apignomonia errabunda, Apinus cembra, Apinus pinea, Apiognomonia veneta, Apion haematodes, Apionsoma (Apionsoma) misakiana, Apionsoma (Apionsoma) misakianum, Apionsoma (Apionsoma) trichocephalus, Apionsoma (Apionsoma) tricocephalus, Apionsoma misakiana, Apionsoma trichocephala, Apionsoma trichocephalum, Apionsoma trichocephalus, Apios americana var. americana, Apios americana var. turrigera, Apios americana, Apios tuberosa, Apiospora oryzae, Apiospora veneta, Apiosporopsis veneta, Apis hypnorum, Apis mellifera carnica, Apis mellifera ligustica, Apis mellifera mellifera, Apis mellifera, Apistogramma arua, Apium ammi-maius, Apium amomum, Apium anisoides, Apium anisum, Apium biternatum, Apium candollei, Apium catalaunicum, Apium crispum, Apium depressum, Apium dulce, Apium graveolens subsp. dulce, Apium graveolens subsp. rapaceum, Apium graveolens var. dulce, Apium graveolens, Apium junceum, Apium leptophyllum, Apium luteum, Apium nodiflorum, Apium petraeum, Apium petroselinum, Apium pimpinella, Apium podagraria, Apium rapaceum, Apium rivulare, Apium saxifragum, Apium segetum, Apium sisarum, Apium tenuifolium, Apium ternatum, Apium tragoselinum, Apium villosum, Apium visnaga, Aplanobacter insidiosum, Aplanobacter populi, Aplanobacter stewartii, Aplanobacterium populi, Aplarina prostrata, Aplidium accarense, Aplidium pullum, Aplilia laciniata, Aplilia macrophyla, Aplilia pendula, Aplonis metallica, Aplostemon atropurpureum, Apluda distachya, Aplysia concava, Aplysia dactylomela, Aplysia norfolkensis, Aplysia parvula, Apocryptes petersii, Apocynum album, Apocynum ambigens, Apocynum androsaemifolium subsp. pumilum, Apocynum androsaemifolium var. glabrum, Apocynum androsaemifolium var. griseum, Apocynum androsaemifolium var. incanum, Apocynum androsaemifolium var. intermedium, Apocynum androsaemifolium var. pumilum, Apocynum androsaemifolium var. tomentellum, Apocynum androsaemifolium var. woodsonii, Apocynum androsaemifolium, Apocynum arenarium, Apocynum bebbianum, Apocynum bolanderi, Apocynum breweri, Apocynum canadense, Apocynum cannabinum var. angustifolium, Apocynum cannabinum var. glaberrimum, Apocynum cannabinum var. greeneanum, Apocynum cannabinum var. hypericifolium, Apocynum cannabinum var. nemorale, Apocynum cannabinum var. pubescens, Apocynum cannabinum var. suksdorfii, Apocynum cannabinum, Apocynum carolinii, Apocynum cervinum, Apocynum cordigerum, Apocynum cuspidatum, Apocynum densiflorum, Apocynum detonsum, Apocynum dictyotum, Apocynum dimidiatum, Apocynum estellinum, Apocynum farwellii, Apocynum greeneanum, Apocynum hypericifolium, Apocynum isophyllum, Apocynum ithacense, Apocynum laurinum, Apocynum littorale, Apocynum longifolium, Apocynum macounii, Apocynum macranthum, Apocynum missouriense, Apocynum myrianthum, Apocynum nemorale, Apocynum neogeum, Apocynum nevadense, Apocynum oblongum, Apocynum occidentale, Apocynum oliganthum, Apocynum palustre, Apocynum piscatorium, Apocynum platyphyllum, Apocynum procerum, Apocynum pubescens, Apocynum pumilum var. rhomboideum, Apocynum pumilum, Apocynum purpureum, Apocynum salicifolium, Apocynum salignum, Apocynum scopulorum, Apocynum sibiricum var. cordigerum, Apocynum sibiricum var. farwellii, Apocynum sibiricum var. salignum, Apocynum sibiricum, Apocynum subuligerum, Apocynum suksdorfii var. angustifolium, Apocynum suksdorfii, Apocynum suskdorfii, Apocynum thermale, Apocynum tomentulosum, Apocynum venetum, Apocynum volubine, Apodanthera pedisecta, Apodemus sylvaticus, Apogon andhrae, Apogon elizabethae, Apogon evanidus, Apogon fasciatus, Apogon hungi, Apogon monogramma, Apogon nigripinnis, Apogon nigripinsis, Apogon novemstriatus, Apogon pharaonis, Apogon suezii, Apogon thurstoni, Apogonichthyoides nigripinnis, Apogonichthyoides pharaonis, Apogonichthyoides uninotatus, Apogonichthys nigripinnis, Apogonichtys nigripinnis, Apolectus niger, Apomotis cyanellus, Apomyelois ceratoniae, Aponogeton distachyos, Aponomma sphenodonti, Aponychus corpuzae, Apophallus muehlingi, Apoprionospio pygmaea, Aporrectodea caliginosa, Aporrectodea rosea subsp. bimastoides, Aporrectodea rosea, Aporrectodea trapezoides, Aposeris foetida, Appendiseta robiniae, Apple scar skin viroid, Aproaerema anthyllidella, Aproceros leucopoda, Aprostocetus ceroplastae, Aprostocetus diplosidis, Aprostocetus hagenowii, Aprostocetus microcosmus, Aprostocetus sicarius, Aptenia cordifolia, Aptenia lancifolia, Aptenodytes patagonicus, Apterygothrips hispanicus, Apterygothrips pinicolus, Aptinothrips elegans, Aptinothrips mediterraneus, Aptinothrips rufus, Aquifolium ilex, Aquila chrysaetos x aquila nipalensis, Aquila chrysaetos, Aquila nipalensis, Aquilaspio sexoculata, Aquilegia alpina, Aquilegia aragonensis, Aquilegia atrata, Aquilegia atroviolacea, Aquilegia beata, Aquilegia depauperata, Aquilegia dichroa, Aquilegia flavescens, Aquilegia pyrenaica, Aquilegia viscosa, Aquilegia vulgaris subsp. dichroa, Aquilegia vulgaris subsp. vulgaris, Aquilegia vulgaris, Aquilina pyrenaea, Aquilonastra burtoni, Ara ararauna, Ara macao, Ara militaris, Ara milstaris, Ara nobilis, Ara rubrogenys, Ara severa, Ara severus, Arabidium alpestre, Arabidium alpinum, Arabidium saxeticolum, Arabidopsis arenosa, Arabidopsis halleri, Arabidopsis pumila, Arabidopsis suecica, Arabidopsis thaliana, Arabis albida, Arabis alpina subsp. caucasica, Arabis alpina var. albida, Arabis alpina var. glabrata, Arabis alpina, Arabis arcuata, Arabis arenosa, Arabis arvensis, Arabis auriculata, Arabis austriaca, Arabis billardieri, Arabis cadmea, Arabis canescens, Arabis cantabrica, Arabis caucasica, Arabis chinensis, Arabis ciliata, Arabis clusiana, Arabis collina, Arabis corymbiflora, Arabis crispata, Arabis dacica, Arabis elongata, Arabis eriocarpa, Arabis flavescens, Arabis flaviflora, Arabis gerardii, Arabis glareosa, Arabis grandiflora, Arabis halleri, Arabis heterophylla, Arabis incana, Arabis janitrix, Arabis kochii, Arabis lateripendens, Arabis lechenfeldiana, Arabis leptocarpaea, Arabis linneana, Arabis longisiliqua, Arabis longistyla, Arabis lusitanica, Arabis major, Arabis malinvaldiana, Arabis merinoi, Arabis minor, Arabis monticola, Arabis moschata, Arabis multicaulis, Arabis muralis, Arabis nasturtium, Arabis nemoralis, Arabis nemorensis, Arabis nova, Arabis obtusifolia, Arabis ochroleuca, Arabis orientalis, Arabis pendula, Arabis pieninica, Arabis planisiliqua subsp. nemorensis, Arabis planisiliqua, Arabis praecox, Arabis procera, Arabis procurrens, Arabis pubicalyx, Arabis pubigera, Arabis purpurascens, Arabis recta, Arabis rigidula, Arabis rosea, Arabis rubricaulis, Arabis rugosa, Arabis segetalis, Arabis sinaica, Arabis sophia, Arabis stolonifera, Arabis suecica, Arabis supina, Arabis thaliana, Arabis thyrsoidea, Arabis turrita, Arabis turriti, Arabis undulata, Arabis virescens, Arabis viscosa, Arachis hypogaea subsp. nambyquarae, Arachis hypogaea subsp. oleifera, Arachis hypogaea var. hypogaea, Arachis hypogaea var. nambyquarae, Arachis hypogaea, Arachis nambyquarae, Arachnidium lacourti, Arachnites musciflorus, Arachnoidea protecta, Arachnoidella protecta, Arachnopeziza aranea, Arachnospermum laciniatum, Aracium alpinum, Aracium aureum, Araecerus coffeae, Araecerus fasciculatus, Araecerus grisescens, Araeopteron ecphaea, Aralia californica, Aralia canescens, Aralia chinensis, Aralia elata var. mandshurica, Aralia elata, Aralia emeiensis, Aralia georgica, Aralia hupehensis, Aralia japonica, Aralia leroana, Aralia longipes, Aralia mairei, Aralia mandschurica, Aralia mandshurica, Aralia papyrifera, Aralia planchoniana, Aralia quinquefolia, Aralia racemosa, Aralia sieboldii, Aralia sololensis, Aralia spinosa, Aralia subcapitata, Aramigus fulleri, Aratinga acuticauda, Aratinga acuticaudata, Aratinga aurea, Aratinga cactorum, Aratinga erythrogenys, Aratinga finschi, Aratinga holochlora, Aratinga leucophthalma, Aratinga leucophthalmus, Aratinga leucopthalmus, Aratinga mitrata, Aratinga pertinax, Aratinga wagleri, Araucaria araucana, Araucaria bidwillii, Araucaria dombeyi, Araucaria heterophylla, Araucaria imbricata, Araujia albens, Araujia calycina, Araujia sericifera, Arbopercula tenella, Arbutus andrachne, Arbutus cassinifolia, Arbutus crispa, Arbutus croomii, Arbutus idaea, Arbutus intermedia, Arbutus laurifolia, Arbutus lucida, Arbutus microphylla, Arbutus mucronata, Arbutus nothocomaros, Arbutus pavarii, Arbutus procumbens, Arbutus salicifolia, Arbutus sieberi, Arbutus turbinata, Arbutus unedo, Arbutus vulgaris, Arca amygdalum, Arca decussata, Arca inaequivalvis, Arca kagoshimensis, Arca multistriata, Arca striata, Arca trapezina, Archachatina aequatorialis, Archachatina marginata, Archangelica litoralis, Archangelica officinalis subsp. litoralis, Archelix apalolena, Archiboreoiulus pallidus, Archontophoenix cunninghamiana, Arcion majus, Arcion minus, Arcion tomentosum, Arcitalitrus dorrieni, Arctapodema australis, Arctiodracon camtschatcensis, Arctiodracon japonicum, Arctium bardana, Arctium chabertii, Arctium chaorum, Arctium conglomeratum, Arctium euminus, Arctium glabrescens, Arctium grandiflorum, Arctium lappa x minus, Arctium lappa, Arctium leiospermum, Arctium leptophyllum, Arctium macrospermum, Arctium minus subsp. nemorosum, Arctium minus, Arctium montanum, Arctium nemorosum, Arctium newbouldii, Arctium pubens, Arctium ruderale, Arctium tenellum, Arctium tomentosum, Arctium vulgare, Arctium x ambiguum, Arctium x cimbricum, Arctium x maassii, Arctium x mixtum, Arctium x neumannii, Arctium x nothum, Arctocrania canadensis, Arctogentia aurea, Arctotheca calendula, Arctotheca calendulacea, Arctotheca calendulaceum, Arctotis calendula, Arctotis calendulacea, Arctotis elegans, Arctotis grandis, Arctotis hypochondriaca, Arctotis rosea, Arctotis speciosa, Arctotis staticefolia, Arctotis stoechadifolia var. grandis, Arctotis stoechadifolia, Arctotis sulphurea, Arctotis superba, Arctotis tristis, Arctotis venusta, Arcuatula perfragilis, Arcuatula senhousia, Arcyphyllum caribaeum, Arecastrum romanzoffianum, Aremonia agrimonoides subsp. agrimonoides, Aremonia agrimonoides, Arenaria apetala, Arenaria arvensis, Arenaria balearica, Arenaria biflora subsp. pancicii, Arenaria biflora, Arenaria caespitosa, Arenaria caucasica, Arenaria corsica, Arenaria gayana, Arenaria glomerata, Arenaria holosteoides, Arenaria laricifolia, Arenaria linearifolia, Arenaria mediterranea, Arenaria montana, Arenaria pentandra, Arenaria pyrenaica, Arenaria rotundifolia subsp. pancicii, Arenaria rotundifolia var. pancicii, Arenaria rotundifolia, Arenaria salina, Arenaria segetalis, Arenaria umbellata, Arenaria verna, Arenaria viscidula, Arenipses sabella, Arenophilus peregrinus, Aresha setigera, Aresha shelkovnikovi, Aretia auriculata, Aretia elongata, Aretia maxima, Argania sideroxylon, Argania spinosa, Argas persicus, Argas reflexus, Arge berberidis, Argemone barclayana, Argemone intermedia, Argemone leiocarpa, Argemone mexicana var. ochroleuca, Argemone mexicana, Argemone ochroleuca var. stenophylla, Argemone ochroleuca, Argemone sulphurea, Argentacer saccharinum, Argentina rupestris, Argentina supina, Argiope trifasciata, Argonemertes dendyi, Argorips alba, Argorips cerulea, Argulus japonicus, Argusia sibirica, Argyranthemum frutescens, Argyresthia blastotere cupressella, Argyresthia cupressella, Argyresthia laevigatella, Argyresthia thuiella, Argyresthia trifasciata, Argyrochaeta bipinnatifida, Argyrochaeta parviflora, Argyrocome manglesii, Argyrops filamentosus, Arhopalus mexicanus, Arhopalus obscurus, Arhopalus paganum, Arhopalus rusticus obsoletus, Arhopalus rusticus, Arhynchite arhynchite, Aria graeca, Aria hybrida, Aria intermedia, Aria latifolia, Aria mougeotii var. austriaca, Aria mougeotii, Aria nivea subsp. scandica, Aria nivea, Aria suecica, Aria torminalis, Arianta arbustorum, Aricia fusciceps, Aridius bifasciatus, Aridius nodifer, Aridius norvegicus, Aridius subfasciatus, Aridius vannidecki, Arietellus pavoninus, Ariolimax columbianus, Arion bourguignati, Arion circumscriptus armoricanus, Arion circumscriptus var. silvatica, Arion circumscriptus, Arion distinctus, Arion empiricorum, Arion fasciatus, Arion flagellus, Arion hortensis, Arion intermedius, Arion leucophaeus, Arion lusitanicus, Arion marginatus, Arion minimus, Arion nilssoni, Arion rufus, Arion silvaticus, Arion sylvaticus, Arion vulgaris, Arisaema loureiroi, Arisaema macrourum, Arisaema ternatum, Arisarum australe, Arisarum azoricum, Arisarum balansat, Arisarum crassifolium, Arisarum forbesi, Arisarum jacquini, Arisarum latifolium, Arisarum libani, Arisarum proboscideum, Arisarum serpentrium, Arisarum sibthorpii, Arisarum subalpinum, Arisarum veslingi, Arisarum vulgare subsp. veslingi, Arisarum vulgare subsp. vulgare, Arisarum vulgare var. veslingi, Arischrada molucellae, Aristea cyanea, Aristea dichotoma, Aristea ecklonii, Aristea lastii, Aristea maitlandii, Aristea paniculata, Aristea stipitata, Aristella bromoides, Aristella longiflora, Aristichthys nobilis, Aristida adscensionis f. modestina, Aristida adscensionis f. viridis, Aristida adscensionis subsp. guineensis, Aristida adscensionis subvar. condensata, Aristida adscensionis var. abortiva, Aristida adscensionis var. adscensionis, Aristida adscensionis var. breviseta, Aristida adscensionis var. bromoides, Aristida adscensionis var. canariensis, Aristida adscensionis var. coarctata, Aristida adscensionis var. condensata, Aristida adscensionis var. decolorata, Aristida adscensionis var. humilis, Aristida adscensionis var. interrupta, Aristida adscensionis var. mexicana, Aristida adscensionis var. modesta, Aristida adscensionis var. nigrescens, Aristida adscensionis var. normalis, Aristida adscensionis var. scabriflora, Aristida adscensionis var. typica, Aristida adscensionis, Aristida alopecuroides, Aristida americana var. bromoides, Aristida avenacea, Aristida bromoides, Aristida canariensis, Aristida coarctata, Aristida congesta, Aristida debilis, Aristida densispica, Aristida dispersa var. bromoides, Aristida dispersa var. coarctata, Aristida dispersa var. humilis, Aristida dispersa var. nana, Aristida dispersa var. nigrescens, Aristida dispersa, Aristida elytrophoroides, Aristida fasciculata, Aristida festucoides, Aristida gracilis var. depauperata, Aristida gracilis, Aristida grisebachiana var. decolorata, Aristida grisebachiana var. grisebachiana, Aristida grisebachiana, Aristida guineensis, Aristida hordeacea, Aristida humilis, Aristida interrupta, Aristida laxa, Aristida longespica var. longespica, Aristida longicauda, Aristida longispica var. longispica, Aristida longispica, Aristida maritima, Aristida nana, Aristida nigrescens, Aristida peruviana, Aristida pseudohordacea, Aristida pungens, Aristida rangei, Aristida schaffneri, Aristida simpliciflora var. texana, Aristida steudeliana, Aristida stricta var. decolorata, Aristida stricta var. grisebachiana, Aristida tunetana, Aristida vulgaris var. canariensis, Aristolochia altissima, Aristolochia atlantica, Aristolochia clematitis, Aristolochia durior, Aristolochia fontanesii, Aristolochia frutescens, Aristolochia grandifolia, Aristolochia hitchcockii, Aristolochia infesta, Aristolochia longa, Aristolochia macrophylla, Aristolochia multinervi, Aristolochia rotunda var. grandiflora, Aristolochia rotunda, Aristolochia sempervirens, Aristolochia sipho, Aristolochia tenuis, Aristolochia undata, Aristotelea spiralis, Arius capellonis, Arius granulatus, Arius parkii, Arkopoda luteola, Armadillidium album, Armadillidium assimile, Armadillidium kossuthi, Armadillidium nasatum, Armadillidium vulgare, Armadillo officinalis, Armeniaca tomentosa, Armeniaca triloba, Armeniaca vulgaris, Armeria ambifaria, Armeria arenaria, Armeria bottendorfensis, Armeria bupleuroides, Armeria campestris, Armeria drummondii, Armeria duriuscula, Armeria elongata, Armeria expansa, Armeria halleri, Armeria intermedia, Armeria maritima subsp. elongata, Armeria maritima subsp. halleri, Armeria maritima subsp. intermedia, Armeria maritima, Armeria miscella, Armeria montana, Armeria planifolia, Armeria plantaginea, Armeria pubescens, Armeria rhenana, Armeria vulgaris, Armillaria edodes, Armillaria odorata, Armoracia austriaca, Armoracia glastifolia, Arnebia calycina, Arnebia cornuta, Arnebia decumbens, Arnebia echioides, Arnebia orientalis, Arnebia tubata, Arnebia vivianii, Arnica austriaca, Arnica bellidiastrum, Arnica bernardina, Arnica bruceae, Arnica celsa, Arnica chamissonis subsp. chamissonis var. chamissonis, Arnica chamissonis subsp. chamissonis var. interior, Arnica chamissonis subsp. chamissonis, Arnica chamissonis subsp. foliosa var. andina, Arnica chamissonis subsp. foliosa var. bernardina, Arnica chamissonis subsp. foliosa var. incana, Arnica chamissonis subsp. foliosa var. maguirei, Arnica chamissonis subsp. foliosa, Arnica chamissonis subsp. genuina, Arnica chamissonis subsp. incana, Arnica chamissonis var. andina, Arnica chamissonis var. bernardina, Arnica chamissonis var. chamissonis, Arnica chamissonis var. foliosa, Arnica chamissonis var. incana, Arnica chamissonis var. interior, Arnica chamissonis var. jepsoniana, Arnica chamissonis var. maguirei, Arnica chamissonis, Arnica cordata, Arnica doronicum, Arnica exigua, Arnica foliosa var. incana, Arnica foliosa, Arnica helvetica, Arnica kodiakensis, Arnica lanulosa, Arnica macilenta, Arnica montana, Arnica scorpioides, Arnica tussilaginea, Arnica wulfeniana, Arnoglossum alpinum, Arnoglossum gramineum, Arnoglossum incanum, Arnoglossum maritimum, Arnoglossum subulatum, Arnopogon picroides, Arnoseris clavata, Arnoseris foetida, Arnoseris minima, Arnoseris pusilla, Arocatus longiceps, Arodes aethiopicum, Aromia bungii, Aromia moschata, Aron colocasium, Aron dracunculum, Aronia affinis, Aronia alnifolia, Aronia amelanchier, Aronia aquatica, Aronia arbutifolia var. atropurpurea, Aronia arbutifolia var. glabra, Aronia arbutifolia var. nigra, Aronia arbutifolia, Aronia atropurpurea, Aronia botryapium var. racemosa, Aronia botryapium, Aronia canadensis, Aronia densa, Aronia floribunda, Aronia glabrescens, Aronia japonica, Aronia melanocarpa, Aronia nebrodensis, Aronia nigra, Aronia ovalis, Aronia prunifolia, Aronia pubens, Aronia pumila, Aronia pyrifolia, Aronia rotundifolia, Aronia rupestris, Aronia x densiflora, Arrhenatherum americanum, Arrhenatherum avenaceum var. bulbosum, Arrhenatherum avenaceum var. nodosum, Arrhenatherum avenaceum, Arrhenatherum biaristatum, Arrhenatherum bromoides, Arrhenatherum bulbosum var. variegatum, Arrhenatherum bulbosum, Arrhenatherum elatius f. bulbosum, Arrhenatherum elatius ssp. bulbosum, Arrhenatherum elatius subsp. bulatus, Arrhenatherum elatius var. biaristatum, Arrhenatherum elatius var. bulbosum, Arrhenatherum elatius var. elatius, Arrhenatherum elatius var. nodosum, Arrhenatherum elatius var. tuberosum, Arrhenatherum elatius, Arrhenatherum elatus tuberosum, Arrhenatherum pratense, Arrhenatherum pubescens, Arrhenatherum sempervirens, Arrhenatherum tuberosum, Arrostia altissima, Arrostia paniculata, Arsace arborea, Artedia muricata, Artema atlanta, Artemia franciscana, Artemisia abrotanum Savi, Artemisia abrotanum, Artemisia absinthia, Artemisia absinthium var. absinthium, Artemisia absinthium var. insipida, Artemisia absinthium, Artemisia affinis, Artemisia afra, Artemisia alba, Artemisia altaica, Artemisia altissima, Artemisia anethifolia, Artemisia angustifolia, Artemisia annua, Artemisia aprica, Artemisia araneosa, Artemisia arborescens, Artemisia argyi, Artemisia aromatica, Artemisia australis, Artemisia austriaca, Artemisia baldaccii, Artemisia balsamita, Artemisia biennis var. biennis, Artemisia biennis var. diffusa, Artemisia biennis, Artemisia brittonii, Artemisia campestris ssp. caudata, Artemisia campestris subsp. campestris, Artemisia campestris subsp. caudata, Artemisia campestris subsp. maritima, Artemisia campestris var. caudata, Artemisia campestris, Artemisia canariensis, Artemisia canescens, Artemisia cannabifolia, Artemisia capillaris, Artemisia caudata var. calvens, Artemisia caudata, Artemisia cernua, Artemisia cernuiflora, Artemisia chamomilla, Artemisia changaica, Artemisia chiarugii, Artemisia chinensis, Artemisia chrysantha, Artemisia clausonis, Artemisia clemensiana, Artemisia coarctata, Artemisia codonocephala, Artemisia crithmifolia, Artemisia cuneata, Artemisia discolor, Artemisia diversifolia, Artemisia dniproica, Artemisia doonense, Artemisia dracunculoides var. dracunculina, Artemisia dracunculoides, Artemisia dracunculus subsp. dracunculus, Artemisia dracunculus subsp. glauca, Artemisia dracunculus var. glauca, Artemisia dracunculus, Artemisia dubia, Artemisia elatior, Artemisia elegans, Artemisia eriophora, Artemisia eschscholtziana, Artemisia flodmanii, Artemisia foeniculacea, Artemisia forwoodii, Artemisia gayana, Artemisia glabrata, Artemisia glauca dracunculus, Artemisia glauca var. dracunculina, Artemisia glauca, Artemisia gnaphalodes, Artemisia gracilis, Artemisia grandiflora, Artemisia grisea, Artemisia handel-mazzettii, Artemisia herbacea, Artemisia herriotii, Artemisia humilis, Artemisia inconspicua, Artemisia inodora, Artemisia integrifolia, Artemisia involucrata, Artemisia jeniscensis, Artemisia krascheninnikoviana, Artemisia kulbadica, Artemisia latifolia, Artemisia lercheana, Artemisia lindheimeriana, Artemisia lobelii, Artemisia ludoviciana subsp. ludoviciana, Artemisia ludoviciana subsp. typica, Artemisia ludoviciana var. americana, Artemisia ludoviciana var. brittonii, Artemisia ludoviciana var. gnaphalodes, Artemisia ludoviciana var. latifolia, Artemisia ludoviciana var. pabularis, Artemisia ludoviciana, Artemisia matricarioides, Artemisia michauxii, Artemisia microcephala, Artemisia minima, Artemisia muelleri, Artemisia nilotica, Artemisia nivea, Artemisia nutans, Artemisia nutantiflora, Artemisia odoratissima, Artemisia orbicularis, Artemisia pabularis, Artemisia pallida, Artemisia paniculata, Artemisia paucicephala, Artemisia pendula, Artemisia petraea, Artemisia piperita, Artemisia platyphylla, Artemisia pontica, Artemisia procera, Artemisia proceriformis, Artemisia pseudofragrans, Artemisia punctata, Artemisia purshiana, Artemisia pyromacha, Artemisia ramosa, Artemisia repens, Artemisia rhaetica, Artemisia rhizomata, Artemisia rubripes, Artemisia sachaliensis, Artemisia samamisica, Artemisia saxatilis, Artemisia schrenkiana, Artemisia scoparia, Artemisia selengensis, Artemisia seriphium, Artemisia serotina, Artemisia shansiensis, Artemisia sieversiana, Artemisia stelleriana, Artemisia stemutatoria, Artemisia tenuifolia, Artemisia tenuissima, Artemisia thuscula, Artemisia tongtchouanensis, Artemisia tournefortiana, Artemisia trichophylla, Artemisia tristis, Artemisia umbrosa, Artemisia venusta, Artemisia verlotiorum x vulgaris, Artemisia verlotiorum, Artemisia violacea, Artemisia virens, Artemisia vulgaris subsp. ludoviciana, Artemisia vulgaris subsp. mexicana, Artemisia vulgaris subsp. selengensis, Artemisia vulgaris var. coarctata, Artemisia vulgaris var. glabra, Artemisia vulgaris var. kamtschatica, Artemisia vulgaris var. latiloba, Artemisia vulgaris var. ludoviciana, Artemisia vulgaris var. selengensis, Artemisia vulgaris var. vulgaris, Artemisia vulgaris, Artemisia wallichiana, Artemisia willdenowii, Artemisia wurzellii, Arthratherum pungens, Arthrochortus loliaceus, Arthrocladiella mougeotii, Arthrolobium ebracteatum, Arthrolobium pinnatum, Arthrolobium scorpioides, Arthrolobium tauricum, Arthrolobus perennis, Arthrolobus rugosus, Arthromyzus tulipaellus, Arthurdendyus triangulatus, Articulina alticostata, Articulina antillarum, Articulina mayori, Articulina pacifica, Artioposthia exulans, Artioposthia triangulata, Arum bulbosum, Arum calyptrale, Arum dracunculus, Arum esculentum, Arum facchini, Arum foetidum, Arum fornicatum, Arum gracile, Arum guttatum, Arum heldreichii, Arum immaculatum, Arum italicum f. majoricens, Arum italicum f. purpurascen, Arum italicum subsp. gaibolens, Arum italicum subsp. italicum, Arum italicum subspmajoricens, Arum italicum subvar. Immaculatum, Arum italicum var. concolor, Arum italicum var. facchinii, Arum italicum var. immaculatum, Arum italicum var. intermedium, Arum italicum var. maculatum, Arum italicum var. parvulum, Arum italicum var. yvesii, Arum italicum, Arum macrourum, Arum maculatum f. parvulum, Arum maculatum, Arum majoricense, Arum malyi, Arum modicense, Arum numidicum, Arum ponticum, Arum proboscideum, Arum provinciale, Arum pyrenaeum, Arum subulatum, Arum ternatum, Arum trapezuntinum, Arum vernale, Arum vulgare, Arum zelebori, Aruncus aethusifolius, Aruncus allegheniensis, Aruncus americanus, Aruncus aruncus, Aruncus asiaticus, Aruncus barbacaprae, Aruncus capribarba, Aruncus dioicus subsp. vulgaris, Aruncus dioicus var. aethusifolius, Aruncus dioicus var. asiaticus, Aruncus dioicus var. dioicus, Aruncus dioicus var. kamtschaticus, Aruncus dioicus, Aruncus kamtschaticus var. tomentosus, Aruncus kamtschaticus, Aruncus silvester, Aruncus sylvester var. kamtschaticus, Aruncus sylvester var. tenuifolius, Aruncus sylvester var. tomentosus, Aruncus sylvester var. triternatus, Aruncus sylvester var. vulgaris, Aruncus sylvester, Aruncus sylvestris var. vulgaris, Aruncus sylvestris, Aruncus vulgaris, Arundarbor argenteostriata, Arundarbor fortunei, Arundarbor kurilensis, Arundarbor pygmaea, Arundinaria agrestis, Arundinaria akebono, Arundinaria albomarginata, Arundinaria anceps, Arundinaria angustifolia, Arundinaria argenteostriata, Arundinaria brachyclada, Arundinaria chikatsuafumiana, Arundinaria chino, Arundinaria chrysantha, Arundinaria communis, Arundinaria confusa, Arundinaria decipiens, Arundinaria dimorpha, Arundinaria distichophylla, Arundinaria exsaniosa, Arundinaria fastuosa, Arundinaria fortunei, Arundinaria hisauchii, Arundinaria incantans, Arundinaria japonica, Arundinaria jaunsarensis, Arundinaria kisoensis, Arundinaria komiyamana, Arundinaria kunimiana, Arundinaria kurilensis, Arundinaria laydeckeri, Arundinaria matake, Arundinaria matsushimensis, Arundinaria metake, Arundinaria musashiensis, Arundinaria nakashimana, Arundinaria narihira, Arundinaria nikkoensis, Arundinaria nitida, Arundinaria okadana, Arundinaria otayana, Arundinaria palmata, Arundinaria pumila, Arundinaria pygmaea, Arundinaria quadrangularis, Arundinaria ramosa, Arundinaria sakaii, Arundinaria sawadae, Arundinaria shibuyana, Arundinaria simonii, Arundinaria spathacea, Arundinaria stolonifera, Arundinaria sugimotoi, Arundinaria suwekoana, Arundinaria tomikusensis, Arundinaria toyomurensis, Arundinaria trichophila, Arundinaria tsukubensis, Arundinaria tsurumatiana, Arundinaria usawae, Arundinaria uyenoensis, Arundinaria vagans, Arundinaria vaginata, Arundinaria veitchii, Arundinaria velutina, Arundinaria yonoskei, Arundo ampelodesmos, Arundo australis, Arundo bicolor, Arundo bifaria, Arundo biflora, Arundo ciliata, Arundo clarionis, Arundo colorata, Arundo dioeca, Arundo dioica, Arundo donax subsp. plinii, Arundo donax var. angustifolia, Arundo donax var. lanceolata, Arundo donax, Arundo epigeios, Arundo epigejos, Arundo festucoides, Arundo glauca, Arundo halleri, Arundo kakao, Arundo kila, Arundo latifolia, Arundo mauritanica, Arundo mediterranea, Arundo micrantha, Arundo montana, Arundo plinii, Arundo plumosa, Arundo richardii, Arundo riparia, Arundo saccharifera, Arundo sativa, Arundo schwabii, Arundo selloana, Arundo speciosa, Arundo stricta, Arundo sylvatica, Arundo tenax, Asarina cordifolia, Asarina erubescens, Asarina lobelii, Asarina procumbens, Asarina scandens, Asarum europaeum, Asarum officinale, Asarum renifolium, Asarum reniforme, Asarum rotundifolium, Ascalenia acaciella, Ascalonicum sativum, Ascalonicum scorodoprasum, Ascaridia dissimilis, Ascaris cati, Ascaris circumflexa, Ascaris equorum, Ascaris filicollis, Ascaris filiformis, Ascaris leonina, Ascaris marginata, Ascaris megalocephala, Ascaris procyonis, Ascaris simplex, Ascaris triquetra, Ascaris vulpis, Ascidia atra, Ascidia cannelata, Ascidia capillata, Ascidia cavernosa, Ascidia cuvieri, Ascidia manhattensis, Ascidia nigra, Ascidia patata, Ascidia phusca, Ascidia plicata, Ascidia somalensis, Ascidia somaliensis, Ascidia styeloides, Ascidia variabilis, Ascidiella aspersa, Ascidiella styeloides, Asclepias angustifolia, Asclepias brasiliensis, Asclepias cornuta, Asclepias crinita, Asclepias curassavica, Asclepias fruticosa, Asclepias glabra, Asclepias intermedia, Asclepias kansana, Asclepias nivea curassavica, Asclepias physocarpa, Asclepias procera, Asclepias speciosa, Asclepias syriaca var. kansana, Asclepias syriaca, Asclepias virgata, Ascobolus trifolii, Ascocalyx abietina, Ascochyta aquilegiae, Ascochyta chrysanthemi, Ascochyta dianthi, Ascochyta doronici, Ascochyta gossypii, Ascochyta grossulariae, Ascochyta lappae, Ascochyta lycopersici, Ascochyta padi, Ascochyta petroselini, Ascochyta pinodes, Ascochyta pisi, Ascochyta pisicola, Ascochyta robiniae, Ascochyta rufomaculans, Ascochyta sorghi, Ascochyta sorghina, Ascochyta suberosa, Ascochyta syringae, Ascochyta trifolii, Ascochytella grossulariae, Ascochytula grossulariae, Ascomyces bullatus, Ascomyces deformans var. deformans, Ascomyces deformans, Ascomyces juglandis, Ascomyces pruni, Ascophora mucedo, Ascophylla laevigatum, Ascophyllum mackayi, Ascophyllum nodosum, Ascospora aegopodii, Ascospora nicholsonii, Ascosporium bullatum, Ascosporium deformans, Ascyrum calycinum, Asellus communis, Asellus coxalis, Aseroe rubra, Ashtoret lunaris, Ashworthius sidemi, Aspalathus arborescens, Aspalthium bituminosum, Aspalthium palaestinum, Asparagopsis aethiopica, Asparagopsis armata, Asparagopsis densiflora, Asparagopsis lancea, Asparagopsis rufolanosa, Asparagopsis setacea, Asparagopsis taxiformis, Asparagus aculeatus, Asparagus aethiopicus, Asparagus asiaticus var. amharicus, Asparagus asparagoides, Asparagus densiflorus, Asparagus draco, Asparagus kuisibensis, Asparagus laetus, Asparagus lanceus, Asparagus lujae, Asparagus maximus, Asparagus medeoloides, Asparagus myriocladus, Asparagus officinalis subsp. officinalis, Asparagus officinalis, Asparagus plumosus var. tenuissimus, Asparagus plumosus, Asparagus sarmentosus var. comatus, Asparagus sarmentosus var. densiflorus, Asparagus setaceus, Asparagus sprengeri, Asparagus zanzibaricus, Aspera muralis, Asperella digitaria, Asperella oryzoides, Asperisporium sequoiae, Asperogronops inaequalis, Asperugo alba, Asperugo divaricata, Asperugo erecta, Asperugo procumbens, Asperugo vulgaris, Asperula alpigena, Asperula alpina, Asperula arenicola, Asperula arvensis, Asperula azurea, Asperula bazargiciensis, Asperula besserana, Asperula besseriana, Asperula campanulata, Asperula capillacea, Asperula caucasica, Asperula cincinnata, Asperula cynanchica, Asperula debilis, Asperula dissitiflora, Asperula dubia, Asperula fallax, Asperula galioidea, Asperula galioides, Asperula ghautensis, Asperula glauca, Asperula humifusa, Asperula laevigata, Asperula macroclada, Asperula minor, Asperula multiflora, Asperula orientalis, Asperula propinqua, Asperula rotundifolia, Asperula rubeola, Asperula rubioides, Asperula semiamicta, Asperula sherardia, Asperula strictissima, Asperula subalpina, Asperula taurina, Asperula tenuiflora, Asperula tinctoria, Asperula trabutii, Asperula trinervia, Asphodeline lutea, Asphodelus albus, Asphodelus deseglisei, Asphodelus fistulosus, Asphodelus luteus, Asphodelus sibiricus, Asphodelus simplex, Asphodelus sphaerocarpus, Asphodelus tenuifolius, Asphondylia borzi, Asphondylia buddleia, Asphonydlia buddleia, Aspidapion radiolus, Aspidapion validum, Aspidimorpha nigropunctata, Aspidiotiphagus citrinus, Aspidiotus acuminatus, Aspidiotus buxi, Aspidiotus chaemaeropsis, Aspidiotus chamaeropsis, Aspidiotus destructor, Aspidiotus dictyospermi arecae, Aspidiotus echinocacti, Aspidiotus elaeidis, Aspidiotus hederae, Aspidiotus lataniae, Aspidiotus myrthi, Aspidiotus myrti, Aspidiotus nerii, Aspidiotus palmarum, Aspidiotus proteus, Aspidiotus rapax, Aspidiotus rossi, Aspidiotus spinosus, Aspidiotus transparens, Aspidiphorus lareyniei, Aspidium braunii, Aspidium bulbiferum, Aspidium clypeolarium, Aspidium cordifolium, Aspidium coriaceum, Aspidium exaltatum, Aspidium falcatum, Aspidium lobatum, Aspidium lonchitis, Aspidium molle, Aspidium munitum, Aspidium nymphale, Aspidium politum, Aspidium punctilobum, Aspidium tuberosum, Aspidomorpha fabricii, Aspidoshiphon mexicanus, Aspidosiphon (Akrikos) mexicanus, Aspidosiphon (Aspidosiphon) elegans, Aspius aspius aspius, Aspius aspius, Asplenium altajense, Asplenium ambiguum, Asplenium ceterach, Asplenium deflexum, Asplenium esculentum, Asplenium fontanum subsp. foresiacum, Asplenium foresiacum, Asplenium foreziense, Asplenium forisiense, Asplenium halleri var. foresiacum, Asplenium lanceolatum subsp. foresiacum, Asplenium lasiopteris, Asplenium malabaricum, Asplenium moritzii, Asplenium petersenii, Asplenium pubescens, Asplenium scolopendrium, Asplenium thwaitesii, Asplenium toppingianum, Asplenium vitiense, Asprella digitata, Asprella oryzoides, Aspris capillaris, Aspris caryophyllea, Asproparthenis punctiventris, Assaracus capax var. plenus, Assaracus capax, Assaracus reflexus, Assonia wallichii, Astacolus insolitus, Astacolus sublegumen, Astacus astacus, Astacus leptodactylus, Astegopteryx javensis, Aster abbreviatus, Aster acmellus, Aster adulterinus, Aster aestivus, Aster albus, Aster alpinus, Aster amelloides, Aster amellus, Aster angustatus, Aster annuus, Aster archerianus, Aster argutus, Aster artemisiaeflorus, Aster attenuatus, Aster atticus, Aster auriculatus, Aster avicenniifolius, Aster bangii, Aster behringensis, Aster bellidiastrum, Aster bellidiflorus, Aster bellis, Aster bicolor, Aster boykinii, Aster brachyactis, Aster breyninus, Aster britannicus, Aster brumalis, Aster bubonium, Aster caespitosus, Aster camptosorus, Aster canadensis, Aster carmesinus, Aster carneus, Aster castaneus, Aster chasei, Aster chinensis, Aster chrysocomoides, Aster chrysogonii, Aster claytoni, Aster claytonii, Aster collinus, Aster concinnus, Aster cordidifolius, Aster cordifolius morantus, Aster cordifolius subsp. laevigatus, Aster cordifolius subsp. sagittifolius, Aster cordifolius var. cordifolius, Aster cordifolius var. furbishiae, Aster cordifolius var. incisus, Aster cordifolius var. laevigatus, Aster cordifolius var. lanceolatus, Aster cordifolius var. moratus, Aster cordifolius var. polycephalus, Aster cordifolius var. racemiflorus, Aster cordifolius var. sagittifolius, Aster cordifolius, Aster coridifolius, Aster corymbosus, Aster crenifolius var. arcuans, Aster curvescens, Aster cylleneus, Aster divaricatus var. sandwicensis, Aster divaricatus, Aster dracunculoides, Aster dumosus cordidifolius, Aster dumosus var. coridifolius, Aster dumosus var. dumosus, Aster dumosus var. gracilentus, Aster dumosus, Aster dysentericus, Aster eminens, Aster ensifolius, Aster ericoides, Aster erigeron, Aster excavatus, Aster exilis var. australis, Aster fallax, Aster finkii var. moratus, Aster flexilis, Aster flexilus, Aster floribundus, Aster foliaceus var. arcuans, Aster foliaceus var. sublinearis, Aster forsteri, Aster frutetorum, Aster garibaldii, Aster germanicus, Aster glabellus, Aster glaber, Aster glomeratus, Aster graminifolius, Aster helenium, Aster heterophyllus, Aster hiemalis, Aster hirsutus, Aster hirtus, Aster hispanicus, Aster hungaricus, Aster ianthinus, Aster johannensis, Aster junceus, Aster korshinskyi, Aster lacinians, Aster laevigatus, Aster laevis var. concinnus, Aster laevis x novi-belgii, Aster laevis, Aster lanceolatus x novi-belgii, Aster lanceolatus, Aster lateralis, Aster lateriflorus, Aster latissimifolius var. serotinus, Aster laxiflorus, Aster laxifolius, Aster laxus, Aster leiophyllus, Aster linosyris, Aster longifolius, Aster lowrieanus var. incisus, Aster lowrieanus var. lanceolatus, Aster lowrieanus, Aster luxurians, Aster macrophyllus var. apricensis, Aster macrophyllus var. excelsior, Aster macrophyllus var. ianthinus, Aster macrophyllus var. macrophyllus, Aster macrophyllus var. pinguifolius, Aster macrophyllus var. sejunctus, Aster macrophyllus var. velutinus, Aster macrophyllus, Aster miser, Aster multiformis, Aster mutabilis, Aster nivalis, Aster nobilis, Aster noeanus, Aster novae-angliae, Aster novi-belgii subsp. floribundus, Aster novi-belgii subsp. johannensis, Aster novi-belgii subsp. laevigatus, Aster novi-belgii subsp. novi-belgii, Aster novi-belgii subsp.laevigatus, Aster novi-belgii var. johannensis, Aster novi-belgii var. novi-belgii, Aster novi-belgii var. rosaceus, Aster novi-belgii var. stenolepis, Aster novi-belgii, Aster oculus-christi, Aster onustus, Aster orientalis, Aster ottomanum, Aster patulus, Aster pilosus, Aster plumarius, Aster pseudoamellus, Aster pulchellus, Aster pulicaria, Aster pulicarius, Aster purpureus, Aster rafinesquii, Aster recurvatus, Aster richardsonii, Aster riciniatus, Aster rolandii, Aster roscidus, Aster rubricaulis, Aster rugosus, Aster sagittifolius, Aster salicifolius, Aster salicinus, Aster salignus, Aster sandwicensis, Aster saxatilis, Aster scabris, Aster schreberi, Aster serotinus, Aster shortii, Aster sibiricus subsp. richardsonii, Aster sibiricus var. giganteus, Aster sibiricus var. sibiricus, Aster sibiricus, Aster squamatus, Aster squarrosulus, Aster squarrosus, Aster stenactis, Aster stilettiformis, Aster strictus, Aster subintegerrimus, Aster subulatus var. australis, Aster subulatus var. sandwicensis, Aster tardiflorus, Aster tenebrosus, Aster tenellus, Aster thyrsiflorus, Aster tradescantii var. saxatilis, Aster tradescantii, Aster traversii, Aster vaurealis, Aster versicolor, Aster vimineus var. saxatilis, Aster violaris, Aster virgineus, Aster wolfii, Aster x salignus, Asteracanthion distichum, Asteracanthion rubens, Asteracanthion violaceus, Asteranthemum stellatum, Asteranthemum vulgare var. uniflorum, Asteranthemum vulgare, Asterias attenuata, Asterias clathrata, Asterias disticha, Asterias dorsatus, Asterias echinites, Asterias echinus, Asterias fabricii, Asterias gigantea, Asterias glacialis, Asterias holsatica, Asterias hybrida, Asterias lutea, Asterias minuta, Asterias murrayi, Asterias nodosa, Asterias pallida, Asterias planci, Asterias rubens violacea, Asterias rubens, Asterias solaris, Asterias spinosa, Asterias stimpsoni, Asterias violacea, Asterias vulgaris, Asterina burtoni burtoni, Asterina burtoni, Asterina wega, Asterionella glacialis, Asterionellopsis glacialis, Asteriscium australasiae, Asteriscodes chinense, Asteriscus aquaticus subsp. nanus, Asteriscus aquaticus var. nanus, Asteriscus aquaticus, Asteriscus citriodorus, Asteriscus nanus, Asteroaphelenchoides besseyi, Asterocarpa humilis, Asterocephalus acutiflorus, Asterocephalus ambiguus, Asterocephalus bipinnatus, Asterocephalus caucasicus, Asterocephalus columbaria, Asterocephalus dichotomus, Asterocephalus elegans, Asterocephalus flavescens, Asterocephalus integrifolius, Asterocephalus mollissimus, Asterocephalus montanus, Asterocephalus pumilus, Asterocephalus pyrenaicus, Asterocephalus webbianus, Asterococcus muratae, Asterodiaspis variolosa, Asterolecanium fimbriatum, Asterolecanium variolosum, Asterolinon linum-stellatum, Asterolinon serpyllifolium, Asterolinon stellatum, Asteroma ulmeum, Asteromella aesculicola, Asteromphalus sarcophagus, Asterophyllum galium, Asterophyllum scherardianum, Asteropterus tenellus, Asterosedum spurium, Asterosedum stoloniferum, Astichus trifasciatipennis, Astilbe arendsii, Astilbe aruncus, Astilbe barbata, Astilbe chinensis, Astilbe davidii, Astilbe divaricata, Astilbe japonica, Astilbe rivularis, Astilbe rubra, Astilbe taquetii, Astilbe thunbergii var. aethusifolius, Astilbe x arendsii, Astilboides tabularis, Astragalus abbas-riazi, Astragalus aegyptiacus, Astragalus africanus, Astragalus alopecuroides subsp. alopecuroides, Astragalus alopecuroides var. glabrescens, Astragalus alopecuroides, Astragalus ambiguus, Astragalus ancistron, Astragalus arenarius var. multijugus, Astragalus arenicola, Astragalus arnoceras, Astragalus asterias subsp. polyactinus, Astragalus atlanticus, Astragalus baeticus, Astragalus boeticus var. siliquosus, Astragalus boeticus var. subinflatus, Astragalus boeticus, Astragalus borysthenicus, Astragalus brachyceras, Astragalus buceras, Astragalus canaliculatus, Astragalus castellanus, Astragalus chlorocarpus, Astragalus cicer var. angustifolius, Astragalus cicer var. dieffenbachii, Astragalus cicer var. heldaviensis, Astragalus cicer var. major, Astragalus cicer var. microphyllus, Astragalus cicer var. pseudo-cicer, Astragalus cicer var. speciosus, Astragalus cicer, Astragalus circassicus, Astragalus clandestinus, Astragalus corrugatus, Astragalus cruciatus var. algeriensis, Astragalus cruciatus var. canariensis, Astragalus cruciatus var. polyactinus, Astragalus cruciatus, Astragalus cruentus, Astragalus cymbicarpos, Astragalus cymbiformis, Astragalus dacicus, Astragalus dorcoceras, Astragalus embergeri, Astragalus falcatus, Astragalus filicaulis subsp. rytilobus, Astragalus filicaulis, Astragalus galegifolius, Astragalus galegiformis, Astragalus geniculatus, Astragalus glyciphyllos, Astragalus glycophyllos, Astragalus glycyphylloides var. petrovici, Astragalus glycyphylloides var. serbicus, Astragalus glycyphylloides, Astragalus glycyphyllos subsp. glycyphylloides, Astragalus glycyphyllos subsp. glycyphyllos, Astragalus glycyphyllos var. rotundifolius, Astragalus glycyphyllos, Astragalus hamosus subsp. brachyceras, Astragalus hamosus subsp. embergeri, Astragalus hamosus subsp. verus, Astragalus hamosus var. ancistron, Astragalus hamosus var. brachyceras, Astragalus hamosus var. brevipes, Astragalus hamosus var. buceras, Astragalus hamosus var. macrocarpus, Astragalus hamosus var. microcarpus, Astragalus hamosus var. multiflorus, Astragalus hamosus var. pumilus, Astragalus hamosus var. subcurvatus, Astragalus hamosus var. volubilitanus, Astragalus hamosus, Astragalus hybridus, Astragalus lehmannianus, Astragalus linearifolius, Astragalus marianorum, Astragalus microphyllus, Astragalus mucronatus, Astragalus narbonensis subsp. atlanticus, Astragalus narbonensis var. africanus, Astragalus narbonensis var. glabrescens, Astragalus narbonensis, Astragalus nawabianus, Astragalus odoratus, Astragalus oncocarpus, Astragalus onobrychis var. albiflorus, Astragalus onobrychis var. alpinus, Astragalus onobrychis var. banaticus, Astragalus onobrychis var. brevifoliatus, Astragalus onobrychis var. chlorocapus, Astragalus onobrychis var. linearifolius, Astragalus onobrychis var. multijugus, Astragalus onobrychis var. rigidus, Astragalus onobrychis var. rochelianus, Astragalus onobrychis var. skorpili, Astragalus onobrychis var. sofianus, Astragalus onobrychis var. stenophyllus, Astragalus onobrychis var. varnensis, Astragalus onobrychis var. wagneri, Astragalus onobrychis, Astragalus oxyglottis var. psiloglottis, Astragalus oxyglottis, Astragalus pancicii, Astragalus paui, Astragalus pelecinus subsp. pelecinus, Astragalus pelecinus, Astragalus penduliflorus, Astragalus petroviccii, Astragalus petrovici, Astragalus pilosus, Astragalus polyactinus, Astragalus propinquus, Astragalus psedonobrychis, Astragalus pseudo-cicer, Astragalus psiloglottis, Astragalus rochelianus, Astragalus rotundifolius, Astragalus rytilobus, Astragalus scorpioides, Astragalus serbicus, Astragalus sesameus var. ambiguus, Astragalus skorpilii, Astragalus sofianus, Astragalus stella var. acutifolius, Astragalus stella var. minor, Astragalus stella, Astragalus stellatus, Astragalus stribrnyi, Astragalus taeckholmianus, Astragalus tenuirugis, Astragalus tribuloides var. medians, Astragalus trichocarpus, Astragalus troizkii, Astragalus uncinatus, Astragalus varnensis, Astragalus vesicarius, Astragalus volubilitanus, Astrantia australis, Astrantia candida, Astrantia caucasica, Astrantia epipactis, Astrantia europaea, Astrantia helleborifolia, Astrantia heterophylla, Astrantia intermedia, Astrantia major, Astrantia maxima, Astrantia montana, Astrantia nigra, Astrantia pallida, Astrantia saniculifolia, Astrantia speciosa, Astrantia vulgaris, Astrapaea wallichii, Astrocarpus clusii, Astrocarpus sesamoides var. erecta, Astrochiton vaporariorum, Astrodaucus orientalis, Astrolobium scorpioides, Astronotus ocellatus, Astrosphaeriella trochus, Astylus petraea, Asychis gotoi, Asynonychus cervinus, Asynonychus godmani, Asynonychus godmanni, Asystasia coromandeliana, Asystasia gangetica, Atactodea glabrata, Atactodea striata, Ataliothrips reuteri, Atelerix albiventris, Atelerix algirus, Atergatis roseus, Athalia rosae, Athamanta ajowan, Athamanta caucasica, Athamanta collina, Athamanta daucoides, Athamanta lasiantha, Athamanta libanotis, Athamanta meum, Athamanta oreoselinum, Athamanta pubescens, Athamanta ramosissima, Athamanta riviniana, Athamanta sibirica, Athamanta sicula, Athanasia cuneiformis, Athanasia glabra, Athanasia scariosa, Athanasia tricuspis, Athanasia tridentata, Athanasia trifurcata, Athelia rolfsii, Athene noctua, Atherigona varia, Atherina anterina, Atherina boïeri, Atherina bonapartii, Atherina boyeri caspia, Atherina boyeri, Atherina caspia, Atherina forskalii, Atherina hyalosoma, Atherina lacustris, Atherina mochon aegyptia, Atherina mochon caspia, Atherina mochon pontica, Atherina mochon riqueti, Atherina mochon, Atherina pontica, Atherina presbyter caspia, Atherina presbyter pontica, Atherina riqueti, Atherina risso, Atherina rissoi, Atherina sarda, Atherina sardinella, Atherinomorus forskali, Atherinomorus forskalii, Athernotus pyramidalis, Atherurus ternatus, Atheta acuticollis, Atheta amicula, Atheta atramentaria, Atheta castanoptera, Atheta coriaria, Atheta dilutipennis, Atheta divisa, Atheta fungi, Atheta gregaria, Atheta harwoodi, Atheta luridipennis, Atheta mucronata, Atheta nigra, Atheta nigricornis, Atheta oblita, Atheta palustris, Atheta sordida, Atheta triangulum, Atheta trinotata, Atheta vaga, Athous haemorrhoidalis, Athrerigona soccata, Athrips rancidella, Athyriopsis lasiopteris, Athyriopsis petersenii, Athyrium ambigua, Athyrium bulbiferum, Athyrium congruum, Athyrium copelandii, Athyrium esculentum, Athyrium oshimense, Athyrium toppingianum, Atirbesia bracteata, Atlantoxerus getulus, Atocion armeria, Atomaria apicalis, Atomaria bella, Atomaria consanguinea, Atomaria fuscata, Atomaria fuscipes, Atomaria hislopi, Atomaria lewisi, Atomaria lohsei, Atomaria munda, Atomaria nitidula, Atomaria punctithorax, Atomaria pusilla, Atomaria strandi, Atomaria testacea, Atomaria turgida, Atractobolus resinarius, Atractolytocestus huronensis, Atractylis lanata, Atractylis leucocephala, Atractylis lutea, Atragene alpina, Atragene alpinum, Atragene sibirica, Atragene speciosa, Atragene tianschanica, Atrema testiculatum, Atrichum crispum, Atriplex amaranthoides, Atriplex amblyostegia, Atriplex ambrosioides, Atriplex arenaria, Atriplex argentea, Atriplex aucheri, Atriplex australasica, Atriplex bonus-henricus, Atriplex botrys, Atriplex bracteosa, Atriplex calotheca, Atriplex campanulata, Atriplex centralasiatica var. megalotheca, Atriplex centralasiatica, Atriplex deltoidea, Atriplex denticulata, Atriplex desertorum, Atriplex diffusa, Atriplex dimorphostegia, Atriplex eardleyae, Atriplex fera, Atriplex flagellaris, Atriplex foliolosa, Atriplex graeca, Atriplex halimoides, Atriplex halimus, Atriplex hastata subsp. polonicum, Atriplex hastata var. calotheca, Atriplex hastata, Atriplex heterosperma, Atriplex holocarpa, Atriplex laciniata, Atriplex laevis, Atriplex latifolia, Atriplex lenticularis, Atriplex leptocarpa, Atriplex lindleyi, Atriplex littoralis var. patens, Atriplex littoralis, Atriplex lucida, Atriplex marina, Atriplex maritima, Atriplex megalotheca, Atriplex micrantha, Atriplex muelleri, Atriplex neurivalvis, Atriplex nitens subsp. aucheri, Atriplex nitens subsp. desertorum, Atriplex nitens, Atriplex oblongifolia, Atriplex olivieri, Atriplex oppositifolia, Atriplex patens, Atriplex patula subsp. hastata, Atriplex patula var. hastata, Atriplex patula var. littoralis, Atriplex patula var. triangularis, Atriplex patutum, Atriplex platensis, Atriplex platysepala, Atriplex polonica, Atriplex polysperma, Atriplex portulacoides, Atriplex prostrata subsp. calotheca, Atriplex prostrata subsp. deltoidea, Atriplex prostrata subsp. latifolia, Atriplex prostrata subsp. polonica, Atriplex prostrata subsp. triangularis, Atriplex prostrata var. triangularis, Atriplex prostrata, Atriplex pseudocampanulata, Atriplex pterocarpa, Atriplex rosea subsp. foliolosa, Atriplex rosea, Atriplex sabulosa, Atriplex sagittata, Atriplex schugnanica, Atriplex semibaccata, Atriplex semibracteata, Atriplex semilunaris, Atriplex serrata, Atriplex sibirica, Atriplex sphaeromorpha, Atriplex stuckertii, Atriplex suberecta, Atriplex tatarica, Atriplex transcaspica, Atriplex triangularis, Atriplex tricostata, Atriplex urbica, Atriplex veneta, Atriplex x northusiana, Atropa bella-donna, Atropa origanifolia, Atropa physalodes, Atropis airoides, Atropis anisoclada, Atropis californica, Atropis canbyi, Atropis carinata, Atropis chilochloa, Atropis dolicholepis, Atropis gigantea, Atropis hauptiana, Atropis laevis, Atropis nuttalliana, Atropis poecilantha, Atropis procumbens, Atropis scabrella, Atropis sclerodes, Atropis stricta, Atropis tenuifolia, Atropis tenuissima, Atta testacea, Attagenus bifasciatus, Attagenus brunneus, Attagenus cyphonoides, Attagenus diversepubescens, Attagenus fasciatus, Attagenus gobicola, Attagenus lynx, Attagenus megatoma, Attagenus museorum, Attagenus pellio, Attagenus quadrimaculatus, Attagenus rossi, Attagenus simplex, Attagenus smirnovi, Attagenus trifasciatus, Attagenus unicolor japonicus, Attagenus unicolor, Attagenus woodroffei, Attegenus brunneus, Attegenus cyphonoides, Atyaephyra desmarestii, Atys curta, Atys cylindrica, Atys cylindricus, Atys lineata, Atys macandrewii, Auberteterus alternecoloratus, Aubrieta columnae, Aubrieta deltoidea, Aubrieta floribunda, Aubrieta graeca, Aubrieta integrifolia, Aubrieta intermedia, Aubrieta italica, Aubrieta xcultorum, Aucuba japonica, Aucuba luteocarpa, Audibertia parviflora, Audouinella codicola, Audouinella robusta, Audouinella sargassicola, Audouinella spathoglossi, Audouinella subseriata, Audouinia anchylochaeta, Audouinia maculata, Audouinia semicincta, Aulacaspis flacourtiae, Aulacaspis major, Aulacaspis pentagona, Aulacaspis tubercularis, Aulacomnium gaudichaudii, Aulacomya ater, Aulacomya atra, Aulacorthum circumflexum, Aulacorthum pelargonii, Aulacorthum pseudorosaefolium, Aulacorthum solani solani, Aulacorthum solani, Aulacorthum viride, Auladoria arrowi, Aulographina eucalypti, Aulographum eucalypti, Aulonium ruficorne, Aulonopygus aculeatus, Aurantium medicum, Aurantium x acre, Aurantium x bigarella, Aurantium x corniculatum, Aurantium x coronatum, Aurantium x distortum, Aurantium x humile, Aurantium x myrtifolium, Aurantium x orientale, Aurantium x silvestre, Aurantium x sinense, Aurantium x variegatum, Aurantium x vulgare, Aurantothrips orchidaceus, Aurelia aurita, Aurelia coerulea, Aurelia solida, Aurelia squarrosa, Aureobasidion zeae, Aureobasidium caulivorum, Aureobasidium lini, Aureothrips marigoldae, Auricula hortensis, Auricula lutea, Auricula-ursi auricula, Aurinia edentula, Aurinia petraea, Aurinia saxatilis, Aurinia sinuata, Australoheros facetus, Australopacifica coxii, Australoplana sanguinea, Australorbis bahiensis, Austrocylindropuntia cylindrica, Austrocylindropuntia exaltata, Austrocylindropuntia intermedia, Austrocylindropuntia subulata, Austrodanthonia racemosa var. racemosa, Austrodanthonia racemosa, Austrodanthonia setacea, Austrodanthonia tenuior, Austroderia richardii, Austromenidia bonariensis, Austromenopon echinatum, Austrominius modestus, Austropeplea viridis, Austropotamobius pallipes, Austropotamobius torrentium, Austrostipa nitida, Austrostipa scabra, Austrostipa verticillata, Authistes argenteus, Authistes puta, Autisthes argenteus, Autisthes puta, Autogenes x biflorus, Autographa gamma, Autolytus cornutus, Avellinia festucoides, Avellinia michelii, Avena agadiriana, Avena agraria, Avena albicans, Avena almeriensis, Avena alpina, Avena alta, Avena ambigua, Avena amethystina, Avena arduensis, Avena arvensis, Avena atheranthera, Avena atlantica, Avena avenaceum, Avena barbata subvar. hirsuta, Avena barbata, Avena brevis, Avena bromoides subsp. gouanii, Avena bromoides, Avena bulbosa, Avena caespitosa, Avena canariensis, Avena candollei, Avena canescens, Avena capillaris, Avena carmeli, Avena carmelii, Avena caryophyllea, Avena cespitosa, Avena chlorantha, Avena clauda, Avena compacta, Avena condensata, Avena cristata, Avena cypria, Avena damascena, Avena deusta, Avena dubia, Avena elata, Avena elatior subsp. bulbosa, Avena elatior var. bulbosa, Avena elatior var. elatior, Avena elatior var. tuberosa, Avena elatior, Avena eriantha, Avena fallax, Avena fatua subsp. septentrionalis, Avena fatua x sativa, Avena fatua, Avena fertilis, Avena festucoides, Avena filiformis, Avena flavescens, Avena fragilis, Avena gallecica, Avena glabrescens, Avena glumosa, Avena hirsuta, Avena hirtula, Avena hoppeana, Avena hybrida, Avena japonica, Avena laevigata, Avena lagascae, Avena lendigera, Avena letourneuxii, Avena lucida, Avena lusitanica, Avena malzevii, Avena matritensis, Avena maxima, Avena mollis, Avena muralis, Avena myriantha, Avena neglecta, Avena nervosa, Avena noeana, Avena notarisii, Avena nuda subsp. brevis, Avena nuda subsp. strigosa, Avena nuda, Avena odorata, Avena paludosa, Avena panicea, Avena panormitana, Avena parviflora, Avena pauciflora, Avena peruviana, Avena pourretii, Avena pratensis subsp. bromoides, Avena pratensis subsp. hippelliana, Avena pratensis, Avena pubescens subsp. amethystina, Avena pubescens, Avena purpurascens, Avena rufescens, Avena ruprechtii, Avena sallentiana, Avena sativa subsp. brevis, Avena sativa subsp. nuda, Avena sativa subsp. sativa, Avena sativa subsp. strigosa, Avena sativa var. barbata, Avena sativa var. brevis, Avena sativa var. strigosa, Avena sativa x A. sterilis, Avena sativa, Avena secalina, Avena sempervirens subsp. notarisii, Avena sempervirens, Avena serrulatiglumis, Avena sesquitertia, Avena sikkimensis, Avena spica-venti, Avena spicata, Avena spiciformis, Avena splendens, Avena sterilis subsp. sterilis, Avena striata, Avena strigosa subsp. barbata, Avena strigosa subsp. brevis, Avena strigosa subsp. glabrescens, Avena strigosa var. glabrescens, Avena strigosa, Avena sylvatica, Avena tenuis, Avena triaristata, Avena tuberosa, Avena uniflora, Avena wiestii, Avena x marquandii, Avenastrum bromoides, Avenastrum elatius, Avenastrum flavescens, Avenastrum laevigatum, Avenastrum pratense, Avenastrum pubescens, Avenastrum sempervirens, Avenochloa bromoides, Avenochloa laevigata, Avenochloa letourneuxii, Avenochloa pratensis, Avenochloa pubescens, Avenula alpina, Avenula bromoides, Avenula letourneuxii, Avenula pratensis, Avenula pubescens, Avenula sempervirens, Avetianella longoi, Avian influenza virus, Avicula vexillum, Avicularia avicularia, Avocado sun blotch avsunviroid, Avocado sun blotch viroid, Avocado sunblotch viroid, Avrainvillea amadelpha, Axinaea arabica, Axinotarsus marginalis, Axis axis, Axolopha althaeoides, Axolopha hirsuta, Axonopus affinis, Axonopus ater, Axonopus compressus var. affinis, Axonopus fissifolius var. coronatus, Axonopus fissifolius var. fissifolius, Axonopus fissifolius, Axonopus paniculatus, Axonopus stragulus, Axyris amaranthoides, Aythya americana, Aythya ferina, Aythya novaeseelandiae, Aythya nyroca, Azadinium spinosum, Azalea arborea, Azalea baetica, Azalea burgeri, Azalea calycina, Azalea crispiflora, Azalea danielsiana, Azalea decumbens, Azalea ferruginea, Azalea flava, Azalea indica, Azalea japonica, Azalea macrantha, Azalea obtusa, Azalea pontica, Azarolus aria, Azarolus crataegoides var. dulcis, Azarolus crataegoides var. florifera, Azarolus crataegoides var. intermedia, Azarolus crataegoides var. macrocarpa, Azarolus crataegoides var. malus, Azarolus crataegoides var. pyriformis, Azarolus crataegoides var. torulosa, Azarolus crataegoides, Azarolus hybrida, Azarolus intermedia, Azarolus maroccana, Azarolus oliveriana, Azarolus platyphylla, Azarolus torminalis, Azedara speciosa, Azedarach commelinii, Azedarach deleteria, Azedarach fraxinifolia, Azedarach odoratum, Azedarach sempervirens, Azolla caroliniana, Azolla filiculoides, Azolla mexicana, Azosma punctum, Azukia radiata, Babiana aurea, Babka gymnotrachelus, Bacanius rhombophorus, Bacanius rombophorus, Baccharis halimifolia var. angustior, Baccharis halimifolia var. halimifolia, Baccharis halimifolia, Baccharis hieracifolia, Baccharis ivifolia, Baccharis trifurcata, Bacillaria sigmoidea, Bacillius rossius, Bacillus amylovorus, Bacillus rossius, Bacopa caroliniana, Bacopa micromonnieria, Bacopa monnieri var. cuneifolia, Bacopa monnieri var. micromonnieria, Bacopa monnieri, Bacopa monnieria var. cuneifolia, Bacopa nobsiana, Bacopa obovata, Bacopa rotundifolia, Bacopa simulans, Bacteriastrum hyalinum, Bactericera tremblayi, Bacterium amylovorum, Bacterium exitiosum, Bacterium flaccumfaciens, Bacterium michiganense, Bacterium salicis, Bacterium solanacearum, Bacterium stewartii, Bacterium tabacum, Bacterium vesicatorium, Bactrocera oleae, Badonnelia titei, Badumna longinqua, Baeocrara japonica, Baeolidia moebii, Baeothryon flavescens, Baeumerta nasturtium-aquaticum, Bagnalliella yuccae, Bagous exilis, Bahia lanata, Baikalicus erygraphus, Bakerophoma tracheiphila, Balanococcus diminutus, Balanococcus kwoni, Balantidium sigani, Balantium antarcticum, Balanus albicostatus, Balanus albiostacus, Balanus eburneus, Balanus glandula, Balanus improvisus, Balanus reticulatus, Balanus trigonus, Balanus variegatus, Balbisia canescens, Balbisia divaricata, Balbisia elongata, Balbisia pedunculata, Baldellia ranunculoides, Baldingera arundinacea var. picta, Baldingera arundinacea var. variegata, Baldingera arundinacea, Baldingera colorata, Balea biplicata, Balearica pavonina, Balearica regulorum, Baleopsina caucasica, Balinotella libanotis, Balistes conspicillum, Balistoides conspicillum, Ballerus sapa, Ballimon muricatulum, Ballistura filifera, Ballosporum segetum, Ballota acetabulosa, Ballota acuta, Ballota africana, Ballota alba var. borealis, Ballota alba, Ballota borealis, Ballota cinerea, Ballota foetida, Ballota hirsuta var. hispida, Ballota hirsuta, Ballota hispanica subsp. hispida, Ballota hispanica, Ballota italica, Ballota nigra subsp. foetida, Ballota nigra subsp. meridionalis, Ballota nigra subsp. nigra, Ballota nigra var. alba, Ballota nigra var. aurea, Ballota nigra var. foetida, Ballota nigra var. variegata, Ballota nigra, Ballota pseudodictamnus, Ballota ruderalis, Ballota rupestris, Ballota saxatilis, Ballota sicula, Ballota silvestris, Balmisa vulgari., Balsamiflua euphratica, Balsamiflua illicitana, Balsamina angustifolia, Balsamina capensis, Balsamina coccinea, Balsamina cornuta, Balsamina cristata, Balsamina foeminea, Balsamina fulva, Balsamina hortensis, Balsamina lacca, Balsamina lutea, Balsamina minutiflora, Balsamina mollis, Balsamina noli-tangere, Balsamina odorata, Balsamina parviflora, Balsamina racemosa, Balsamina salicifolia, Balsamina tricornis, Balsamita major var. major, Balsamita major var. tanacetoides, Balsamita major, Bambara contorta, Bambara fusca, Bambusa albo-marginata, Bambusa angustifolia, Bambusa argenteostriata, Bambusa aurea, Bambusa castilloni, Bambusa chino, Bambusa duquilioi, Bambusa edulis, Bambusa fastuosa, Bambusa fortunei, Bambusa heterocycla, Bambusa japonica, Bambusa kurilensis, Bambusa laydeckeri, Bambusa marliacea, Bambusa maximowiczii, Bambusa mazelii, Bambusa nigra, Bambusa ontakensis, Bambusa palmata, Bambusa puberula, Bambusa pubescens, Bambusa pygmaea, Bambusa quadrangularis, Bambusa ramosa, Bambusa reticulata, Bambusa sieberi, Bambusa simonii, Bambusa sulfurea, Bambusa sulphurea, Bambusa surinamensis, Bambusa thouarsii, Bambusa veitchii, Bambusa viridiglaucescens, Bambusa viridiglaucesens, Bambusa vulgaris var. aureovariegata, Bambusa vulgaris var. vittata, Bambusa vulgaris, Bambusaspis bambusae, Bambusicola thoracica, Bambusicola thoracicus, Bambusiomyces shiraianus, Bankia fimbriata, Bankia fimbriatula, Banksia acicularis, Banksia asplenifolia, Banksia glauca, Banksia integrifolia var. dentata, Banksia integrifolia var. integrifolia, Banksia integrifolia var. major, Banksia integrifolia var. minor, Banksia integrifolia, Banksia reticulata, Banksia saligna, Banksia spicata, Banksia tenuifolia, Barbarea arcuata, Barbarea australis, Barbarea barbarea, Barbarea brevistyla, Barbarea ceretana, Barbarea croatica, Barbarea derchiensis, Barbarea erysimoides, Barbarea gautieri, Barbarea hirsuta, Barbarea intermedia x vulgaris, Barbarea intermedia, Barbarea lepuznica, Barbarea lippizensis, Barbarea longisiliqua, Barbarea lyrata, Barbarea ma
Keywords: GBIF; biodiversity; species occurrences